Adjuvant treatment with pegylated interferon α-2a versus low-dose interferon α-2a in patients with high-risk melanoma: a randomized phase III DeCOG trial - Eigentler, T. K.; Gutzmer, R.; Hauschild, A.; Heinzerling, Lucie; Schadendorf, D.; Nashan, D.; Hoelzle, E.; Kiecker, F.; Becker, J.; Sunderkoeter, C.; Moll, I.; Richtig, E.; et al. (Annals of Oncology, 2016)
BACKGROUND: Adjuvant treatment with interferon (IFN)-α-2a improved disease-free survival (DFS) and showed a trend for improving overall survival (OS) in melanoma. This trial was designed to examine whether PEG-IFN is superior to IFN with regard to distant metastasis-free survival (DMFS), DFS and OS. PATIENTS AND METHODS: In this multicenter, open-label, prospective randomized phase III trial, patients with resected cutaneous melanoma stage IIA(T3a)-IIIB (AJCC 2002) were randomized to receive PEG-IFN (180 μg subcutaneously 1×/week; 24 months) or IFN α-2a (3MIU subcutaneously 3×/week; 24 months). Randomization was stratified for stage, number of metastatic nodes, age and previous IFN treatment. The primary end point was DMFS; secondary end points were OS, DFS, quality of life (QoL) and tolerability. RESULTS: A total of 909 patients were enrolled (451 PEG-IFN versus 458 IFN). Neither 5-year DMFS [PEG-IFN 61.0% versus IFN 67.3%; hazard ratio (HR) 1.16, P = 0.21] nor 5-year OS (PEG-IFN 73.2% versus IFN 75.2%; HR 1.05, P = 0.70) nor 5-year DFS (PEG-IFN 57.3% versus IFN 60.9%; HR 1.09, P = 0.40) showed significant differences. Subgroup analyses in patients ± ulcerated primaries and of different tumor stages did not find differences in DMFS, OS or DFS between the treatment groups. One hundred and eighteen patients (26.2%) in the PEG-IFN and 61 patients (13.3%) in the IFN population did not receive the full dosage and length of treatment due to adverse events (P < 0.001). Leukopenia and elevation of liver enzymes were more common in the PEG-IFN arm (56% versus 23.5% LCP; 19.1% versus 9.4% AST; 33.0% versus 16.5% ALT). QoL was identical for nearly all domains. CONCLUSION: PEG-IFN did not improve the outcome over IFN. A higher percentage of patients under PEG-IFN discontinued treatment due to toxicity. CLINICAL TRIALSGOV IDENTIFIER: NCT00204529.
EVALuna2:33941

Adverse events 2.0-Let us get SERIOs New reporting for adverse event outcomes needed in the era of immunooncology - Heinzerling, Lucie; Ascierto, Paolo A.; Dummer, Reinhard; Gogas, Helen; Grob, Jean-Jacques; Lebbe, Celeste; Long, Georgina V.; Mcarthur, Grant; Moslehi, Javid J.; Neilan, Tomas G.; Ribas, Antoni; Robert, Caroline; et al. (European Journal of Cancer, 2019)
CRIS-Team WoS Importer:2019-05-17

Age as a Key Factor in the Pattern, Extent and timing Process of Distant Metastasis in Patients with malignant Melanoma. A Study by the German Central Register of Malignant Melanoma - Gassenmaier, M.; Leiter, U.; Eigentler, T.; Roecken, M.; Keim, U.; Gesierich, A.; Moritz, R.; Heinzerling, Lucie; Tueting, T.; Wollina, U.; Garbe, C. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Age as key factor for pattern, timing, and extent of distant metastasis in patients with cutaneous melanoma: A study of the German Central Malignant Melanoma Registry - Gassenmaier, Maximilian; Keim, Ulrike; Leiter, Ulrike; Eigentler, Thomas K.; Roecken, Martin; Gesierich, Anja; Moritz, Rose K. C.; Heinzerling, Lucie; Tueting, Thomas; Wollina, Uwe; Garbe, Claus (Journal of the American Academy of Dermatology, 2019)
Background: Melanoma incidence rates rise as people age, but the impact of aging on distant metastasis is unclear.
CRIS-Team WoS Importer:2019-04-23

Agranulocytosis with Immune Checkpoint-Blockade - a retrospective, multicenter Evaluation - Zaremba, A.; Martaki, A.; Salzmann, M.; Baroudjian, B.; Sachse, M. M.; Gesierich, A.; Reinhardt, L.; Meier, F.; Hassel, J. C.; Ugurel, S.; Roesch, A.; Schadendorf, D.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

ALK Inhibitors Do Not Increase Sensitivity to Radiation in EML4-ALK Non-small Cell Lung Cancer - Fleschutz, Kathrin; Walter, Lisa; Leistner, Rumo; Heinzerling, Lucie (Anticancer Research, 2020)
BACKGROUND/AIM: ALK inhibitors like Crizotinib, Ceritinib and Alectinib are targeted therapies used in patients with anaplastic lymphoma kinase (ALK)-positive, advanced non-small cell lung cancer (NSCLC). Since in this tumor entity radiotherapy is employed sequentially or concomitantly, potential synergistic effects were investigated, which may support the hypothesis of induced radiosensitization by using ALK inhibitors. MATERIALS AND METHODS: Two cell lines expressing wild-type (WT) or echinoderm microtubule-associated protein-like 4 (EML4)-ALK were treated with ALK inhibitors, followed by irradiation. Cell survival, cell death, cell cycle and phosphorylation of H2A histone family, member X (H2AX) were examined. RESULTS: Combined treatment with ALK-inhibitors plus 10 Gy-irradiation led to effects similar to those of sole radiotherapy, but was more effective than sole drug treatment. CONCLUSION: There is no clear evidence of sensitization to radiation by treating EML4-ALK mutated cells with ALK inhibitors.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Alectinib; ALK inhibitors; anaplastic lymphoma kinase; Ceritinib; Crizotinib; NSCLC; radiation

A multicenter DeCOG study on predictors of vemurafenib therapy outcome in melanoma: pretreatment impacts survival - Ugurel, S.; Loquai, C.; Kaehler, K.; Hassel, J.; Berking, C.; Zimmer, L.; Haubitz, I.; Satzger, I.; Mueller-Brenne, T.; Mikhaimer, N. C.; Becker, J. C.; Kilian, K. J.; et al. (Annals of Oncology, 2015)
Kinase inhibitors targeting the BRAF V600 mutation have become standard in the treatment of metastatic melanoma. Albeit in wide clinical use, the patterns associated with therapy outcome are not fully elucidated. The present study was aimed to identify predictive factors of therapy response and survival under the BRAF inhibitor vemurafenib.This multicenter retrospective study analyzed patient, tumor, and pretreatment characteristics collected in BRAF V600-mutated stage IV melanoma patients before single-agent therapy with the BRAF inhibitor vemurafenib.A total of 300 patients from 14 centers were included into this study with a median follow-up time of 13.0 months. Median progression-free survival (PFS) was 5.1 months; median overall survival (OS) was 7.6 months. Best response under vemurafenib was associated with serum lactate dehydrogenase (LDH; <= versus >upper normal limit; P = 0.0000001), Eastern Cooperative Oncology Group (ECOG) overall performance status (OPS) (0 versus >= 1; P = 0.00089), and BRAF mutation subtype (V600E versus V600K; P = 0.016). Multivariate analysis identified ECOG OPS >= 1 [hazard ratio (HR) = 1.88; P = 0.00005], immunotherapy pretreatment (HR = 0.53; P = 0.0067), elevated serum LDH (HR = 1.45; P = 0.012), age >55 years (HR = 0.72; P = 0.019), and chemotherapy pretreatment (HR = 1.39; P = 0.036) as independent predictors of PFS. For OS, elevated serum LDH (HR = 1.99; P = 0.00012), ECOG OPS >= 1 (HR = 1.90; P = 0.00063), age >55 years (HR = 0.65; P = 0.011), kinase inhibitor pretreatment (HR = 1.86; P = 0.014), immunotherapy pretreatment (HR = 0.57; P = 0.025), chemotherapy pretreatment (HR = 2.17; P = 0.039), and male gender (HR = 0.70; 95% confidence interval 0.50-0.98; P = 0.039) were found as predictors.Our data demonstrate that the type of pretreatment strongly influences the outcome of vemurafenib therapy, with a precedent immunotherapy showing a positive, and a prior chemotherapy and kinase inhibitors showing a negative impact on survival, respectively. Moreover, we show that the patient's OPS, serum LDH, age, and gender independently impact vemurafenib therapy outcome. These findings should be taken into account for the future design of therapy sequencing in BRAF V600 mutation-positive melanoma patients.
EVALuna2:19580

Anti-PD-1 Therapy in SUFU mutant Patients with Gorlin-Goltz Syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34776

Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

A phase I dose escalation and expansion study of intratumorally administered CV8102 as a single-agent or in combination with anti-PD-1 antibodies in patients with advanced solid tumors - Eigentler, Thomas; Krauss, Juergen; Schreiber, Jutta; Weishaupt, Carsten; Terheyden, Patrick; Heinzerling, Lucie; Mohr, Peter; Weide, Benjamin; Ochsenreither, Sebastian; Becker, Juergen; Bauernfeind, Franz-Georg; Brossart, Peter; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2019)
CRIS-Team WoS Importer:2019-11-29

A phase I dose-escalation and expansion trial of intratumorally administered CV8102, alone and in combination with anti-PD-1 in patients with advanced solid tumours - Krauss, J.; Eigentler, T.; Schreiber, J.; Weishaupt, C.; Terheyden, P.; Heinzerling, Lucie; Mohr, P.; Weide, B.; Ochsenreither, S.; Gutzmer, R.; Becker, J. C.; Kiecker, F.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

A review of serious adverse effects under treatment with checkpoint inhibitors - Heinzerling, Lucie; Goldinger, Simone M. (Current Opinion in Oncology, 2017)
PURPOSE OF REVIEW: The aim of this article is to raise awareness of physicians for the serious side-effects of immune-checkpoint blocking antibodies. As checkpoint inhibitors can induce severe side-effects and are increasingly being used also in subspecialties besides dermatology and oncology, with less experience with these drugs available, knowledge has to be spread. Early recognition and adequate management is essential. RECENT FINDINGS: Recent reports on side-effects document cases of serious side-effects involving all organ systems. These include formerly little referenced and life-threatening side-effects such as cardiotoxicity and neurotoxicity. Furthermore, important additional findings are the inclusion of CMV reactivation in the differential diagnosis or the side-effect profile in special patient populations, that is, in transplant patients, patients with autoimmune disease or previous toxicity to ipilimumab. SUMMARY: Checkpoint inhibitor treatment induces a wide range of serious side-effects. However, with prompt diagnosis and adequate treatment these can mostly be safely managed. Documentation and reporting of serious side-effects remains important to share knowledge and thus ensure optimal patient care.
EVALuna2:34336

Assessment of sorafenib induced changes in tumor perfusion of uveal melanoma metastases with dynamic contrast-enhanced ultrasound (DCE-US) - Wildner, Dane; Heinzerling, Lucie; Scheulen, Max E.; Kämpgen, Eckhart; Schuler, Gerold; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Sturm, Jörg; Knieling, Ferdinand (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose Dynamic contrast-enhanced ultrasound (DCE-US) was used to monitor early response to sorafenib therapy in patients with liver metastases from uveal melanoma. Methods In total, 21 patients with liver metastases were recruited within a prospective trial and underwent daily sorafenib therapy. DCE-US of a target lesion was performed before initiation of treatment, on day 15 and 56. Two independent blinded investigators performed software analysis for DCE-US parameters and inter-observer-correlation was calculated. Response to treatment was evaluated on day 56. DCE-US parameters were correlated with clinical response and RECIST1.1 criteria. Results Inter-observer-correlation (r) of DCE-US parameters [time-to-peak (TTP), mean-transit-time (MTT), peak intensity (PI), regional blood volume (RBV), regional blood flow (RBF)] at baseline, day 15, and day 56 was highly significant (r-range 0.73-0.97, all p < 0.001). Out of 17 evaluable patients, 12 patients survived day 56 (clinical responders, cRE), whereas, five patients died before day 56 and were classified as non-responders (cNR). TTP values significantly increased in the cRE group 15 days after initiation of treatment for investigator 1 (p = 0.034) and at day 56 for both investigators (p = 0.028/0.028). MTT had increased significantly in the cRE group on day 56 (p = 0.037/0.022). In the cNR group changes for TTP and MTT remained insignificant. Thus, increase of the DCE-US parameters TTP and MTT are associated with response to treatment and prognosis. Conclusion An increase of TTP and MTT at frequent intervals could serve as a surrogate marker for early response evaluation to anti-angiogenic treatment of metastatic uveal melanoma.
CRIS-Team WoS Importer:2021-06-04

Association of an initial Exanthem with Vemurafenib and Cobimetinib for a better Therapeutic Success in metastatic Melanoma Patients - Kaehler, K.; Bohne, A. S.; Gutzmer, R.; Satzger, I.; Meier, F.; Reinhardt, L.; Zimmer, L.; Schadendorf, D.; Heppt, M.; Gesierich, A.; Thoms, K. M.; Utikal, J.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Author Correction: Non-professional phagocytosis: a general feature of normal tissue cells (Scientific Reports, (2019), 9, 1, (11875), 10.1038/s41598-019-48370-3) - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-06-16

Autoimmune Colitis and Subsequent CMV-induced Hepatitis After Treatment With Ipilimumab - Uslu, Ugur; Agaimy, Abbas; Hundorfean, Gheorghe; Harrer, Thomas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2015)
Ipilimumab, a humanized CTLA-4 antibody, improves overall survival in patients with metastatic melanoma. However, immune-related adverse effects occur in about 65% of ipilimumab-treated patients and have to be adequately managed. A 55-year-old patient developed grade 3 autoimmune colitis 7 weeks after initiation of ipilimumab treatment and subsequently hepatitis with grade 3 elevation of transaminases and ?-glutamyl transferase. Colitis manifested with up to 18 watery and bloody stools per day and severe attacks of abdominal pain. After exclusion of infectious causes, immunosuppression with corticosteroids was initiated. Because of recurrent abdominal pain, spontaneous perforation of the colon had to be excluded. Elevated liver function tests (grade 3 CTCAE) occurred and differential diagnosis included immune-mediated, toxic, and viral hepatitis. It is interesting to note that, not an immune-mediated but a cytomegalovirus-induced hepatitis was diagnosed by serum blood tests and liver biopsy and was subsequently successfully treated. Careful elaboration of the patient under immunotherapy was essential as further immunosuppression mandatory for autoimmune hepatitis would have worsened the viral hepatitis. In conclusion, cytomegalovirus reactivation should be included in the differential in patients under immunotherapy with checkpoint inhibitors and has to be considered as a cause for morbidity.
EVALuna2:1966

A web platform for the network analysis of high-throughput data in melanoma and its use to investigate mechanisms of resistance to anti-PD1 immunotherapy - Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Jaitly, Tanushree; Walter, Lisa; Wittmann, Jürgen; Gupta, Shailendra; Khan, Faiz M.; Wolkenhauer, Olaf; Puetzer, Brigitte M.; Jäck, Hans-Martin; Heinzerling, Lucie; et al. (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2018)
Cellular phenotypes are established and controlled by complex and precisely orchestrated molecular networks. In cancer, mutations and dysregulations of multiple molecular factors perturb the regulation of these networks and lead to malignant transformation. High-throughput technologies are a valuable source of information to establish the complex molecular relationships behind the emergence of malignancy, but full exploitation of this massive amount of data requires bioinformatics tools that rely on network-based analyses. In this report we present the Virtual Melanoma Cell, an online tool developed to facilitate the mining and interpretation of high-throughput data on melanoma by biomedical researches. The platform is based on a comprehensive, manually generated and expert-validated regulatory map composed of signaling pathways important in malignant melanoma. The Virtual Melanoma Cell is a tool designed to accept, visualize and analyze user-generated datasets. It is available at: https://www.vcells.net/melanoma. To illustrate the utilization of the web platform and the regulatory map, we have analyzed a large publicly available dataset accounting for anti-PD1 immunotherapy treatment of malignant melanoma patients.
EVALuna2:34379
Keywords: Therapy resistance; Databases; Network genomics; Systems biology; Immunotherapy; Melanoma

Baseline Biomarkers for Outcome of Melanoma Patients Treated with Pembrolizumab - Weide, Benjamin; Martens, Alexander; Hassel, Jessica C.; Berking, Carola; Postow, Michael A.; Bisschop, Kees; Simeone, Ester; Mangana, Johanna; Schilling, Bastian; Di Giacomo, Anna Maria; Brenner, Nicole; Kaehler, Katharina; et al. (Clinical Cancer Research, 2016)
PURPOSE: Biomarkers for outcome after immune-checkpoint blockade are strongly needed as these may influence individual treatment selection or sequence. We aimed to identify baseline factors associated with overall survival (OS) after pembrolizumab treatment in melanoma patients. EXPERIMENTAL DESIGN: Serum lactate dehydrogenase (LDH), routine blood count parameters, and clinical characteristics were investigated in 616 patients. Endpoints were OS and best overall response following pembrolizumab treatment. Kaplan-Meier analysis and Cox regression were applied for survival analysis. RESULTS: Relative eosinophil count (REC) ≥1.5%, relative lymphocyte count (RLC) ≥17.5%, ≤2.5-fold elevation of LDH, and the absence of metastasis other than soft-tissue/lung were associated with favorable OS in the discovery (n = 177) and the confirmation (n = 182) cohort and had independent positive impact (all P < 0.001). Their independent role was subsequently confirmed in the validation cohort (n = 257; all P < 0.01). The number of favorable factors was strongly associated with prognosis. One-year OS probabilities of 83.9% versus 14.7% and response rates of 58.3% versus 3.3% were observed in patients with four of four compared to those with none of four favorable baseline factors present, respectively. CONCLUSIONS: High REC and RLC, low LDH, and absence of metastasis other than soft-tissue/lung are independent baseline characteristics associated with favorable OS of patients with melanoma treated with pembrolizumab. Presence of four favorable factors in combination identifies a subgroup with excellent prognosis. In contrast, patients with no favorable factors present have a poor prognosis, despite pembrolizumab, and additional treatment advances are still needed. A potential predictive impact needs to be further investigated. Clin Cancer Res; 22(22); 5487-96. ©2016 AACR.
EVALuna2:19606

BRAF and MEK inhibitors affect dendritic cell maturation and T cell stimulation - Hoyer, Stefanie; Eberlein, V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

BRAF and MEK Inhibitors Affect Dendritic-Cell Maturation and T-Cell Stimulation - Hoyer, Stefanie; Eberlein, Valentina; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (International Journal of Molecular Sciences, 2021)
BRAF and MEK inhibitor (BRAFi/MEKi) combinations are currently the standard treatment for patients with BRAFV600 mutant metastatic melanoma. Since the RAS/RAF/MEK/ERK-pathway is crucial for the function of different immune cells, we postulated an effect on their function and thus interference with anti-tumor immunity. Therefore, we examined the influence of BRAFi/MEKi, either as single agent or in combination, on the maturation of monocyte-derived dendritic cells (moDCs) and their interaction with T cells. DCs matured in the presence of vemurafenib or vemurafenib/cobimetinib altered their cytokine secretion and surface marker expression profile. Upon the antigen-specific stimulation of CD8+ and CD4+ T cells with these DCs or with T2.A1 cells in the presence of BRAFi/MEKi, we detected a lower expression of activation markers on and a lower cytokine secretion by these T cells. However, treatment with any of the inhibitors alone or in combination did not change the avidity of CD8+ T cells in peptide titration assays with T2.A1 cells. T-helper cell/DC interaction is a bi-directional process that normally results in DC activation. Vemurafenib and vemurafenib/cobimetinib completely abolished the helper T-cell-mediated upregulation of CD70, CD80, and CD86 but not CD25 on the DCs. The combination of dabrafenib/trametinib affected DC maturation and activation as well as T-cell activation less than combined vemurafenib/cobimetinib did. Hence, for a potential combination with immunotherapy, our data indicate the superiority of dabrafenib/trametinib treatment.
Keywords: vemurafenib; dabrafenib; cobimetinib; trametinib; BRAF inhibitor; MEK inhibitor; DCs; T cells; immunotherapy; melanoma

BRAF and MEK inhibitors change human immune cell phenotype and function; possible consequences for combination therapy - Hoyer, S.; Eberlein, V.; Babalija, L.; Gerer, K.; Walter, L.; Schuler, Gerold; Schaft, Niels; Heinzerling, Lucie; Dörrie, Jan (2018)
EVALuna2:34394

BRAF and MEK inhibitors influence human immune cell phenotype and function - Hoyer, S.; Eberlein, V.; Babalija, L.; Gerer, K. F.; Walter, L.; Schuler, Gerold; Schaft, Niels; Heinzerling, Lucie; Dörrie, Jan (2017)
EVALuna2:34310

BRAF and MEK Inhibitors Influence the Function of Reprogrammed T Cells: Consequences for Adoptive T-Cell Therapy - Dörrie, Jan; Babalija, Lek; Hoyer, Stefanie; Gerer, Kerstin F.; Schuler, Gerold; Heinzerling, Lucie; Schaft, Niels (International Journal of Molecular Sciences, 2018)
BRAF and MEK inhibitors (BRAFi/MEKi), the standard treatment for patients with BRAFV600 mutated melanoma, are currently explored in combination with various immunotherapies, notably checkpoint inhibitors and adoptive transfer of receptor-transfected T cells. Since two BRAFi/MEKi combinations with similar efficacy are approved, potential differences in their effects on immune cells would enable a rational choice for triple therapies. Therefore, we characterized the influence of the clinically approved BRAFi/MEKi combinations dabrafenib (Dabra) and trametinib (Tram) vs. vemurafenib (Vem) and cobimetinib (Cobi) on the activation and functionality of chimeric antigen receptor (CAR)-transfected T cells. We co-cultured CAR-transfected CD8⁺ T cells and target cells with clinically relevant concentrations of the inhibitors and determined the antigen-induced cytokine secretion. All BRAFi/MEKi reduced this release as single agents, with Dabra having the mildest inhibitory effect, and Dabra + Tram having a clearly milder inhibitory effect than Vem + Cobi. A similar picture was observed for the upregulation of the activation markers CD25 and CD69 on CAR-transfected T cells after antigen-specific stimulation. Most importantly, the cytolytic capacity of the CAR-T cells was significantly inhibited by Cobi and Vem + Cobi, whereas the other kinase inhibitors showed no effect. Therefore, the combination Dabra + Tram would be more suitable for combining with T-cell-based immunotherapy than Vem + Cobi.
EVALuna2:34407

Braf inhibitors and radiation do not act synergistically to inhibit WT and V600E BRAF human melanoma - Walter, Lisa; Heinzerling, Lucie (Anticancer Research, 2018)
Keywords: Radiotherapy; V600E mutant BRAF; Dabrafenib; Melanoma; Vemurafenib; BRAF inhibitor; BRAF

BRAF Inhibitors and Radiation Do Not Act Synergistically to Inhibit WT and V600E BRAF Human Melanoma - Walter, Lisa; Heinzerling, Lucie (Anticancer Research, 2018)
BACKGROUND/AIM: Recent evidence suggests that melanoma patients treated with BRAF inhibitors experience radiosensitization with an increased frequency of side-effects. This could also imply increased effectiveness when treating melanoma. MATERIALS AND METHODS: To test whether the BRAF inhibitors dabrafenib and vemurafenib together with ionizing radiation more effectively inhibit melanoma cells, primary human melanoma tumor cell lines expressing wild-type (WT) or mutant V600E BRAF were analyzed by cell survival, cell death, and cell-cycle testing. RESULTS: All melanoma cell lines examined were radioresistant in these assays. BRAF inhibitor treatment alone suppressed cell survival more effectively than radiation in all the mutant V600E BRAF cell lines, and vemurafenib, but not dabrafenib, also inhibited cell survival in the WT BRAF cell lines at clinically relevant concentrations. However, when cells were treated with BRAF inhibitor followed by radiation, there was no increased effect on the suppression of cell survival. Vemurafenib induced more necrosis than radiation in most melanoma cell lines, irrespective of BRAF status, but this effect was not additive with the combination treatment. BRAF inhibitors and radiation had variable, but independent effects on the induction of cell-cycle arrest. CONCLUSION: These results suggest that BRAF inhibitors and ionizing radiation do not act synergistically to inhibit the growth of primary human melanoma cells.
EVALuna2:34396
Keywords: Radiotherapy; V600E mutant BRAF; Dabrafenib; Melanoma; Vemurafenib; BRAF inhibitor; BRAF

Can checkpoint inhibitor therapy improve response to chemotherapy? - Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie; Schilling, Bastian; Haferrkamp, Sebastian; Kirchberger, MC (2017)
EVALuna2:4767

Can checkpoint inhibitor therapy improve response to chemotherapy? - Kirchberger, Michael Constantin; Schilling, Bastian; Haferkamp, Sebastian; Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2018)
EVALuna2:34410

Cardiotoxicity associated with CTLA4 and PD1 blocking immunotherapy - Heinzerling, Lucie; Ott, Patrick A.; Hodi, F. Stephen; Husain, Aliya N.; Tajmir-Riahi, Azadeh; Tawbi, Hussein; Pauschinger, Matthias; Gajewski, Thomas F.; Lipson, Evan J.; Luke, Jason J. (Journal for ImmunoTherapy of Cancer, 2016)
Immune-checkpoint blocking antibodies have demonstrated objective antitumor responses in multiple tumor types including melanoma, non-small cell lung cancer (NSCLC), and renal cell cancer (RCC). In melanoma, an increase in overall survival has been demonstrated with anti-CTLA-4 and PD-1 inhibition. However, a plethora of immune-mediated adverse events has been reported with these agents. Immune-mediated cardiotoxicity induced by checkpoint inhibitors has been reported in single cases with variable presentation, including myocarditis and pericarditis. Among six clinical cancer centers with substantial experience in the administration of immune-checkpoint blocking antibodies, eight cases of immune-related cardiotoxicity after ipilimumab and/or nivolumab/pembrolizumab were identified. Diagnostic findings, treatment and follow-up are reported. A large variety of cardiotoxic events with manifestations such as heart failure, cardiomyopathy, heart block, myocardial fibrosis and myocarditis was documented. This is the largest case series to date describing cardiotoxicity of immune-checkpoint blocking antibodies. Awareness, monitoring of patients with pre-existing cardiac disorders and prompt evaluation by the treatment team is essential. Treatment including application of steroids is critical for patient safety.
EVALuna2:33930

Centrosomal protein TRIM43 restricts herpesvirus infection by regulating nuclear lamina integrity - Full, Florian; Van Gent, Michiel; Sparrer, Konstantin M. J.; Chiang, Cindy; Zurenski, Matthew A.; Scherer, Myriam; Brockmeyer, Norbert H.; Heinzerling, Lucie; Stürzl, Michael; Korn, Klaus; Stamminger, Thomas; Enßer, Armin; et al. (Nature Microbiology, 2019)
Tripartite motif (TRIM) proteins mediate antiviral host defences by either directly targeting viral components or modulating innate immune responses. Here we identify a mechanism of antiviral restriction in which a TRIM E3 ligase controls viral replication by regulating the structure of host cell centrosomes and thereby nuclear lamina integrity. Through RNAi screening we identified several TRIM proteins, including TRIM43, that control the reactivation of Kaposi's sarcoma-associated herpesvirus. TRIM43 was distinguished by its ability to restrict a broad range of herpesviruses and its profound upregulation during herpesvirus infection as part of a germline-specific transcriptional program mediated by the transcription factor DUX4. TRIM43 ubiquitinates the centrosomal protein pericentrin, thereby targeting it for proteasomal degradation, which subsequently leads to alterations of the nuclear lamina that repress active viral chromatin states. Our study identifies a role of the TRIM43-pericentrin-lamin axis in intrinsic immunity, which may be targeted for therapeutic intervention against herpesviral infections.
EVALuna2:35255

Characteristics of immune checkpoint inhibitor-induced encephalitis and comparison with HSV-1 and anti-LGI1 encephalitis: A retrospective multicentre cohort study - Müller-Jensen, Leonie; Zierold, Sarah; Versluis, Judith M.; Boehmerle, Wolfgang; Huehnchen, Petra; Endres, Matthias; Mohr, Raphael; Compter, Annette; Blank, Christian U.; Hagenacker, Tim; Meier, Friedegund; Reinhardt, Lydia; et al. (European Journal of Cancer, 2022)
Aim: Immune checkpoint inhibitor-induced encephalitis (ICI-iE) is a rare but life-threatening toxicity of immune checkpoint inhibitor treatment. We aim to identify the characteristics of ICI-iE and describe factors that discriminate it from herpes simplex virus (HSV)-1 encephalitis and anti-leucine-rich glioma-inactivated 1 (anti-LGI1) encephalitis, as two alternative entities of encephalitis. Methods: In this retrospective multicentre cohort study, we collected patients with ICI-iE reported to the Side Effect Registry Immuno-Oncology from January 2015 to September 2021 and compared their clinical features and outcome with 46 consecutive patients with HSV-1 or anti-LGI1 encephalitis who were treated at a German neurological referral centre. Results: Thirty cases of ICI-iE, 25 cases of HSV-1 encephalitis and 21 cases of anti-LGI1 encephalitis were included. Clinical presentation of ICI-iE was highly variable and resembled that of HSV-1 encephalitis, while impairment of consciousness (66% vs. 5%, p = .007), confusion (83% vs. 43%; p = .02), disorientation (83% vs. 29%; p = .007) and aphasia (43% vs. 0%; p = .007) were more common in ICI-iE than in anti-LGI1 encephalitis. Antineuronal antibodies (17/18, 94%) and MRI (18/30, 60%) were mostly negative in ICI-iE, but cerebrospinal fluid (CSF) showed pleocytosis and/or elevated protein levels in almost all patients (28/29, 97%). Three patients (10%) died of ICI-iE. Early immunosuppressive treatment was associated with better outcome (r = 0.43). Conclusions: ICI-iE is a heterogeneous entity without specific clinical features. CSF analysis has the highest diagnostic value, as it reveals inflammatory changes in most patients and enables the exclusion of infection. Early treatment of ICI-iE is essential to prevent sequelae and death.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Anti-LGI1 encephalitis; Encephalitis; Herpetic encephalitis; Immune checkpoint inhibitor; Immune-related adverse events; Immunotherapy; Neurotoxicity

Characterization of Checkpoint Inhibitor-associated Diabetes mellitus - Experience in 12 Patients - Satzger, I.; Momma, M.; Thoms, K. M.; Eigentler, T.; Schultz, E.; Loquai, C.; Zimmer, L.; Heinzerling, Lucie; Kaehler, K.; Herbst, R.; Utikal, J.; Hassel, J.; et al. (2018)
EVALuna2:34771

Characterization of Patients with inoperable malignant Stage IIIB-D Melanoma - Zaremba, A.; Weishaupt, C.; Glutsch, V.; Schilling, B.; Loquai, C.; Rafei-Shamsabadi, D.; Meiss, F.; Gutzmer, R.; Haferkamp, S.; Kaehler, K.; Moreira, Alvaro; Heinzerling, Lucie; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Characterization of tanning behavior assessed via online survey: Attitudes, habits, and preventive measures with focus on sunscreen use - Schneiderbanger, Constanze K.; Schuler, Gerold; Heinzerling, Lucie; Kirchberger, Michael C. (Photodermatology Photoimmunology & Photomedicine, 2019)
Background/purpose: Incidence of melanoma is increasing globally. Exposure to ultraviolet radiation (UVR) as important risk factor for developing skin cancer can be influenced by tanning behavior. Only a few studies are available concerning sun tanning behavior and protective measures. Methods: An online survey was distributed via social media to assess tanning habits and examine associated demographic and behavioral factors. Results: In total, 403 questionnaires were distributed, and mean age of respondents was 32. Having a tanned skin, feeling warm and relaxed were the most common motivations for tanning. The use of sunscreen varied and seemed to depend on the occasion of UVR exposure, constantly applied during vacation and during tanning, less commonly applied in daily life and during work. Avoiding painful solar dermatitis was more important as motivation for the use of sunscreen than skin cancer prevention. Skin aging as reason for the use of sunscreen was especially important for females younger than 26 years. The most common applied sun protection factor was 16-49. The main reason opposing the use of sunscreen was a too laborious usage, which was significantly associated with male. Beauty was the only association related to tanned skin the majority (62%) agreed with. Conclusion: The motivation for tanning and reasons for avoiding sunscreen strongly varies. Knowledge about these factors could be used for improving campaigns with respect to target groups. Clarifying the appropriate application of sunscreen, developing convenient sunscreen formulations and providing information about UVR-induced skin aging could lead to an increased usage of sunscreen and therefore to an improved UVR protection.
CRIS-Team Scopus Importer:2019-07-30
Keywords: melanoma; sunscreen; tanning; ultraviolet radiation

Characterization of the impact of immune checkpoint inhibitors on platelet activation and aggregation - Schlüter, Julian; Cunningham, Sarah; Zimmermann, Robert; Achenbach, Susanne; Kramer, Rafaela; Erdmann, Michael; Beckmann, Matthias; Heinzerling, Lucie; Hackstein, Holger (Immunobiology, 2023)
Immune checkpoint inhibitors (ICIs) are effective oncological drugs which block cellular check-point receptors typically targeted by tumor immune evasion strategies. Despite their benefits, clinicians have reported treatment-associated thromboembolism during ICI therapy in recent years. Though several theories on this ICI-associated pathogenesis exist, the direct effects of ICIs on platelets remains unknown. We therefore investigated the potential direct and indirect effect of PD-1, PD-L1 and CTLA-4-targeting ICIs on platelet functionality in multifaceted in vitro experiments. Interestingly, we could not observe a clear effect of ICI on platelet aggregation and primary hemostasis in whole blood and platelet concentrate-based assays. Furthermore, the presence of ICIs in toll-like receptor stimulation had no significant impact on platelet surface marker expression. In a second approach, we investigated the indirect immunological impact of ICIs on platelet activation by exposing platelets to supernatants from ICI- and Staphylococcal enterotoxin B-exposed PBMCs. Whereas ICIs affected IL-2 levels in supernatants, we could not detect clear differences in the secretion of pro-thrombogenic factors and platelet responses. The obtained data suggest that the direct influence of ICIs on platelet activation or the influence of altered T cell function on platelet activation cannot be considered a major factor in the development of thrombotic events.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Immune checkpoint inhibitors; Platelet activation; Platelet function tests; Platelets; Thrombosis

Checkpoint-Inhibition bei Tumorerkrankungen - Ben Khaled, Najib; Piseddu, Ignazio; Boehmer, Daniel F. R.; Zierold, Sarah; Heinzerling, Lucie; Mayerle, Julia; De Toni, Enrico N. (Onkologe, 2021)
Background: The introduction of immune checkpoint inhibitors (ICI) into the therapeutic landscape in oncology over the last decade represents a fundamental advancement in cancer immunotherapy. Objectives: We review the mechanism of action of ICI and their current use in the systemic therapy of various cancers. Materials and methods: Relevant articles were identified in the PubMed database. Clinical trial information was extracted from the Clinicaltrials.gov registry; information on drug approvals were obtained from the European Medicines Agency and the U.S. Food and Drug Administration databases. Conclusions: Although substantial improvements in the treatment of many types of cancer have been achieved by ICI, durable responses and long-term survival can only be observed in a small number of patients. The development of predictive biomarkers to maximize efficacy and minimize immune-related toxicity, in addition to new combination regimens, may help unleash the full potential of ICI in cancer immunotherapy.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Biomarkers; Cancer treatment; CTLA-4-Inhibitor; Immunotherapy; PD-1-PD-L1 blockade

Checkpoint inhibitor-induced eosinophilic fasciitis following high eosinophilia associated with complete response - Toussaint, Frédéric; Hammon, Matthias; Erdmann, Michael; Moreira, Alvaro; Kirchberger, Michael C.; Schuler, Gerold; Schett, Georg; Heinzerling, Lucie (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-10-01

Checkpoint Inhibitors - Heinzerling, Lucie; De Toni, Enrico N.; Schett, Georg; Hundorfean, Gheorghe; Zimmer, Lisa (Deutsches Ärzteblatt international, 2019)
BACKGROUND: Treatment with checkpoint inhibitors such as anti-programmed death-1 (anti-PD-1), anti-PD-ligand 1 (anti-PD-L1), and anti-cytotoxic T-lymphocyte antigen-4 (anti-CTLA-4) antibodies can prolong the survival of cancer patients, but it also induces autoimmune side effects in 86-96% of patients by activating the immune system. In 17-59% of patients, these are severe or even life-threatening. METHODS: This review is based on pertinent articles retrieved by a search in PubMed and on an evaluation of a side-effect registry. RESULTS: Checkpoint-inhibitor-induced autoimmune side effects manifest themselves in all organ systems, most commonly as skin lesions (46-62%), autoimmune colitis (22-48%), autoimmune hepatitis (7-33%), and endocrinopathies (thyroiditis, hypophysitis, adrenalitis, diabetes mellitus; 12-34%). Rarer side effects include pneumonitis (3-8%), nephritis (1-7%), cardiac side effects including cardiomyositis (5%), and neurological side effects (1-5%). Severe (sometimes lethal) side effects arise in 17-21%, 20-28%, and 59% of patients undergoing anti-PD-1 and anti- CTLA-4 antibody treatment and the approved combination therapy, respectively. With proper monitoring, however, these side effects can be recognized early and, usually, treated with success. Endocrine side effects generally require long-term hormone substitution. Patients who have stopped taking checkpoint inhibitors because of side effects do not show a poorer response of their melanoma or shorter survival in comparison to patients who continue to take checkpoint inhibitors. CONCLUSION: The complex management of checkpoint-inhibitor-induced side effects should be coordinated in experienced centers. The creation of an interdisciplinary "tox team" with designated experts for organ-specific side effects has proven useful. Prospective registry studies based on structured documentation of side effects in routine clinical practice are currently lacking and urgently needed.
EVALuna2:69389

Checkpoint Inhibitors The Diagnosis and Treatment of Side Effects - Heinzerling, Lucie; De Toni, Enrico N.; Schett, Georg; Hundorfean, Gheorghe; Zimmer, Lisa (Deutsches Ärzteblatt international, 2019)
Background: Treatment with checkpoint inhibitors such as anti-programmed death-1 (anti-PD-1), anti-PD-ligand 1 (anti-PD-L1), and anti-cytotoxic T-Iymphocyte antigen-4 (anti-CTLA-4) antibodies can prolong the survival of cancer patients, but it also induces autoimmune side effects in 86-96% of patients by activating the immune system. In 17-59% of patients, these are severe or even life-threatening.
CRIS-Team WoS Importer:2019-04-12

Clinical characteristics and outcome of 60 pediatric patients with malignant melanoma registered with the German Pediatric Rare Tumor Registry (STEP) - Offenmüller, Sonja; Leiter, Ulrike; Bernbeck, Benedikt; Garbe, Claus; Eigentler, Thomas; Borkhardt, Arndt; Classen, Carl Friedrich; Corbacioglu, Selim; Dirksen, Uta; Ebetsberger-Dachs, Georg; Heinzerling, Lucie; Jorch, Norbert; et al. (Klinische Pädiatrie, 2017)
Background Malignant melanoma (MM) is a common malignancy in adults while it is rare in children. Thus, information on clinical behavior of pediatric MM is incomplete. Patients The German Pediatric Rare Tumor Registry (STEP) presents a prospective analysis of 60 childhood MM cases diagnosed between June 2006 and December 2014. Method Patients' ages ranged between 0 and 17 years at initial diagnosis (median age 9.6 years). Information on patient's and tumor characteristics was obtained by standardized documentation. Three-year overall survival (OS) and event-free survival (EFS) were estimated by the Kaplan-Meier test. Results Follow-up ranged from 0 to 116 months with a median of 36.5 months, however, univariate analysis was performed for 46 cases with a follow-up > 3 months, only. Cases with spitzoid histotype (40%) did not show a significantly different outcome compared to cases with non-spitzoid MM. Breslow thickness ≤ 2.00 mm was identified in 30% of the cases and 18% were Clark level I to III. Adjuvant therapy was used in 45% of cases. OS at 3 years was 100%, EFS 95.2%. Conclusion We present a series of cases with a high number of spitzoid malignant melanoma and advanced pediatric melanoma, but surprisingly good overall survival rates. Spitzoid and non-spitzoid MM do not differ in clinical behavior and survival.
EVALuna2:34327

Clinical characteristics and therapy response in unresectable melanoma patients stage IIIB-IIID with in-transit and satellite metastases - Zaremba, Anne; Philip, Manuel; Hassel, Jessica C.; Glutsch, Valerie; Fiocco, Zeno; Loquai, Carmen; Rafei-Shamsabadi, David; Gutzmer, Ralf; Utikal, Jochen; Haferkamp, Sebastian; Reinhardt, Lydia; Kähler, Katharina C.; et al. (European Journal of Cancer, 2021)
Introduction: Cutaneous melanoma is notorious for the development of in-transit metastases (ITM). For unknown biological reasons, ITM remain the leading tumour manifestation without progression to distant sites in some patients. Methods: In total, 191 patients with initially unresectable stage III ITM and satellite metastases from 16 skin cancer centres were retrospectively evaluated for their tumour characteristics, survival and therapy response. Three groups according to disease kinetics (no distant progress, slow (>6 months) and fast (<6 months) distant progression) were analysed separately. Results: Median follow-up time was 30.5 (range 0.8–154.0) months from unresectable ITM. Progression to stage IV was observed in 56.5% of cases. Patients without distant metastasis were more often female, older (>70 years) and presented as stage III with lymph node or ITM at initial diagnosis in 45.7% of cases. Melanoma located on the leg had a significantly better overall survival (OS) from time of initial diagnosis compared to non-leg localised primaries (hazard ratio [HR] = 0.61, 95% confidence interval [CI] 0.40–0.91; p = 0.017), but not from diagnosis of unresectable stage III (HR = 0.67, 95% CI 0.45–1.02; p = 0.06). Forty percent of patients received local therapy for satellite and ITM. Overall response rate (ORR) to all local first-line treatments was 38%; disease control rate (DCR) was 49%. In total, 72.3% of patients received systemic therapy for unresectable stage IIIB-D. ORR for targeted therapy (n = 19) was highest with 63.2% and DCR was 84.2% compared to an ORR of 31.4% and a DCR of 54.3% in PD-1 treated patients (n = 70). Patients receiving PD-1 and intralesional talimogene laherparepvec (n = 12) had an ORR of 41.7% and a DCR of 75%. Conclusion: Patients with unresectable ITM and without distant progression are more often female, older, and have a primary on the leg. Response to PD-1 inhibitors in this cohort was lower than expected, but further investigation is required to elucidate the biology of ITM development and the interplay with the immune system.
CRIS-Team Scopus Importer:2021-07-23
Keywords: Immune checkpoint blockade; In-transit; Intralesional therapy; Melanoma; Prognosis; Satellite; Survival; Targeted therapy

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical outcome of concomitant vs interrupted BRAF inhibitor therapy during radiotherapy in melanoma patients - Hecht, Markus; Meier, Friedegund; Zimmer, Lisa; Polat, Bulent; Loquai, Carmen; Weishaupt, Carsten; Forschner, Andrea; Gutzmer, Ralf; Utikal, Jochen S.; Goldinger, Simone M.; Geier, Michael; Hassel, Jessica C.; et al. (British Journal of Cancer, 2018)
This corrects the article DOI: 10.1038/bjc.2017.85.
EVALuna2:34392

Combined immune checkpoint blockade (anti-PD-1/anti-CTLA-4): Evaluation and management of adverse drug reactions - Hassel, Jessica C.; Heinzerling, Lucie; Aberle, Jens; Baehr, Oliver; Eigentler, Thomas K.; Grimm, Marc-Oliver; Gruenwald, Victor; Leipe, Jan; Reinmuth, Niels; Tietze, Julia K.; Trojan, Joerg; Zimmer, Lisa; et al. (Cancer Treatment Reviews, 2017)
BACKGROUND: Combined immune checkpoint blockade (ICB) provides unprecedented efficacy gains in numerous cancer indications, with PD-1 inhibitor nivolumab plus CTLA-4 inhibitor ipilimumab in advanced melanoma as first-ever approved therapies for combined ICB. However, gains in efficacy must be balanced against a higher frequency and severity of adverse drug reactions (ADR). Because delays in diagnosis and management might result in symptom worsening and further complications, clinicians shall be well trained to identify ADR promptly and monitor patients adequately. This paper reviews safety data assessed by the European Medicines Agency for the anti-PD-1/CTLA-4 combination and provides a literature overview on published case reports for rare ADR with suspected potential underreporting. Incidences and kinetics of immune-related ADR are described. Recommendations for the evaluation and management of ADR are convened by an interdisciplinary expert panel focusing on rare but clinically important side effects arising from combined ICB. Pooled safety data from 1551 patients with advanced melanoma, treated either with 3mg/kg ipilimumab plus 1mg/kg nivolumab (N=407), or nivolumab alone (N=787), or ipilimumab alone (N=357) demonstrate that immune-related ADR occur more frequently for the combination, with a shorter time-to-onset, and tend to be more severe. The majority of events is reversible after systemic use of glucocorticoids, notably methylprednisolone or equivalents; in certain cases of long-lasting and refractory immune toxicities, non-steroidal immunosuppressants may be used, once ICB is interrupted or terminated. Combined ICB has considerable toxicities, therefore close monitoring and high experience in diagnosis and treatment of ADR is necessary.
EVALuna2:34333

Combined immune checkpoint blockade for metastatic uveal melanoma: a retrospective, multi-center study - Heppt, Markus V.; Amaral, Teresa; Kähler, Katharina C.; Heinzerling, Lucie; Hassel, Jessica C.; Meissner, Markus; Kreuzberg, Nicole; Loquai, Carmen; Reinhardt, Lydia; Utikal, Jochen; Dabrowski, Evelyn; Gesierich, Anja; et al. (Journal for ImmunoTherapy of Cancer, 2019)
BACKGROUND: Uveal melanoma (UM) is highly refractory to treatment with dismal prognosis in advanced stages. The value of the combined checkpoint blockade with CTLA-4 and PD-1 inhibition in metastatic UM is currently unclear. METHODS: Patients with metastatic or unresectable UM treated with ipilimumab in combination with a PD-1 inhibitor were collected from 16 German skin cancer centers. Patient records of 64 cases were analyzed for response, progression-free survival (PFS), overall survival (OS), and safety. Clinical parameters and serum biomarkers associated with OS and treatment response were determined with Cox regression modelling and logistic regression. RESULTS: The best overall response rate to combined checkpoint blockade was 15.6% with 3.1 and 12.5% complete and partial response, respectively. The median duration of response was 25.5 months (range 9.0-65.0). Stable disease was achieved in 21.9%, resulting in a disease control rate of 37.5% with a median duration of the clinical benefit of 28.0 months (range 7.0-65.0). The median PFS was 3.0 months (95% CI 2.4-3.6). The median OS was estimated to 16.1 months (95% CI 12.9-19.3). Regarding safety, 39.1% of treated patients experienced a severe, treatment-related adverse event according to the CTCAE criteria (grade 3: 37.5%; grade 4: 1.6%). The most common toxicities were colitis (20.3%), hepatitis (20.3%), thyreoiditis (15.6%), and hypophysitis (7.8%). A poor ECOG performance status was an independent risk factor for decreased OS (p = 0.007). CONCLUSIONS: The tolerability of the combined checkpoint blockade in UM may possibly be better than in trials on cutaneous melanoma. This study implies that combined checkpoint blockade represents the hitherto most effective treatment option available for metastatic UM available outside of clinical trials.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Biomarker; Combined immune checkpoint blockade; Ipilimumab; Nivolumab; Uveal melanoma

Combined low-dose ipilimumab and pembrolizumab after sequential ipilimumab and pembrolizumab failure in advanced melanoma - Kirchberger, Michael C.; Hauschild, Axel; Schuler, Gerold; Heinzerling, Lucie (European Journal of Cancer, 2016)
With the wide use of anti-PD-1 therapy, an increasing number of patients progress under treatment. Combined immunotherapy with anti-CTLA-4 and anti-PD-1 antibodies induces higher response rates as first-line treatment in comparison to single-agent therapy, however, with substantial toxicity since the combination of ipilimumab (3 mg/kg) and nivolumab (1 mg/kg) induced 55% grade 3/4 treatment-related adverse events and treatment discontinuation rates of 39%. In this case series, we investigated the efficacy and toxicity of the combined immunotherapy with low-dose ipilimumab (1 mg/kg) plus pembrolizumab (2 mg/kg) in patients with metastatic melanoma with progressive disease under sequential monotherapy with both agents. All patients had received at least three lines of treatment, 78% of patients were M1c, and 67% had brain metastases. Stable disease was observed in 3 out of 9 patients with a median overall survival of 8 months after double checkpoint inhibition. No treatment-related grade 3/4 adverse events occurred, and none of the patients needed to discontinue the treatment due to toxicity. Further trials are needed to investigate combined immunotherapy as rescue treatment in heavily pretreated melanoma patients to find optimal dosage in regard to outcome and toxicity.
EVALuna2:19622

Comparative transcriptomics of immune checkpoint inhibitor myocarditis identifies guanylate binding protein 5 and 6 dysregulation - Finke, Daniel; Heckmann, Markus B.; Salatzki, Janek; Riffel, Johannes; Herpel, Esther; Heinzerling, Lucie; Meder, Benjamin; Voelkers, Mirko; Mueller, Oliver J.; Frey, Norbert; Katus, Hugo A.; Leuschner, Florian; et al. (Cancers, 2021)
Immune checkpoint inhibitors (ICIs) are revolutionizing cancer treatment. Nevertheless, their increasing use leads to an increase of immune-related adverse events (irAEs). Among them, ICI-associated myocarditis (ICIM) is a rare irAE with a high mortality rate. We aimed to characterize the transcriptional changes of ICIM myocardial biopsies and their possible implications. Patients suspected for ICIM were assessed in the cardio-oncology units of University Hospitals Heidelberg and Kiel. Via RNA sequencing of myocardial biopsies, we compared transcriptional changes of ICIM (n = 9) with samples from dilated cardiomyopathy (DCM, n = 11), virus-induced myocarditis (VIM, n = 5), and with samples of patients receiving ICIs without any evidence of myocarditis (n = 4). Patients with ICIM (n = 19) showed an inconsistent clinical presentation, e.g., asymptomatic elevation of cardiac biomarkers (hs-cTnT, NT-proBNP, CK), a drop in left ventricular ejection fraction, or late gadolinium enhancement in cMRI. We found 3784 upregulated genes in ICIM (FDR < 0.05). In the overrepresented pathway ‘response to interferon-gamma’, we found guanylate binding protein 5 and 6 (compared with VIM: GBP5 (log2 fc 3.21), GBP6 (log2 fc 5.37)) to be significantly increased in ICIM on RNA-and protein-level. We conclude that interferon-gamma and inflammasome-regulating proteins, such as GBP5, may be of unrecognized significance in the pathophysiology of ICIM.
CRIS-Team Scopus Importer:2021-06-04
Keywords: CD8; Comparative transcriptomics; CTLA4; ICI-associated myocarditis; ICIM; PD1; PDL-1; Virus myocarditis

Concealed complete response in melanoma patients under therapy with immune checkpoint inhibitors: two case reports - Schliep, Stefan; Agaimy, Abbas; Kiesewetter, Franklin; Schuler, Gerold; Heinzerling, Lucie; Cavallaro, Alexander Josef (Journal for ImmunoTherapy of Cancer, 2018)
BACKGROUND: The assessment of tumor size by RECIST using CT scans and MRIs is considered to be standard of care for staging cancer patients. Despite radiologic evidence of widespread disease, we document for the first time that patients were completely free of viable tumor. CASE PRESENTATION: Two patients with metastatic melanoma were treated with immune checkpoint inhibitors (ipilimumab/ nivolumab) and progressive metastases were detected on CT-scans performed shortly before histologic examinations. In both patients histologic assessment revealed a complete response with necrotic and scarred lesions free of tumor. One of the patients had started immunotherapy 20 months before with an initial partial response. CONCLUSIONS: This phenomenon of a concealed complete response can lead to overtreatment or unnecessary change in treatment. Thus, it is essential to raise awareness for it. Correct identification of responders to immune checkpoint inhibitor therapy is crucial to spare patients immune-mediated side effects and unnecessary as well as expensive treatment. Regression of metastases without decline in size, in these cases manifesting as complete responses, are probably more common than expected and identified to date. Until such responses can be readily identified by new imaging techniques, we recommend liberal biopsies for histologic assessment of progressive metastases in patients during and/or after immune checkpoint inhibitor therapy.
EVALuna2:34405

Cost-effectiveness of Response-Adapted De-escalation of Immunotherapy in Advanced Melanoma - Cartun, Zachary; Kunz, Wolfgang G.; Heinzerling, Lucie; Tomsitz, Dirk; Guertler, Anne; Westphalen, C. Benedikt; Ricke, Jens; Weir, William; Unterrainer, Marcus; Mehrens, Dirk (JAMA Dermatology, 2022)
IMPORTANCE Combination immunotherapy with nivolumab and ipilimumab has markedly improved outcomes for patients with advanced melanoma. However, these therapies pose a considerable financial burden to both patients and the health care system. The ADAPT-IT trial demonstrated comparable progression-free and overall survival for patients with response-adapted ipilimumab discontinuation compared with standard of care (SOC).
CRIS-Team WoS Importer:2022-11-04

C-reactive protein as an early marker of immune-related adverse events - Abolhassani, Amir-Reza; Schuler, Gerold; Kirchberger, Michael Constantin; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2019)
Purpose Immune checkpoint inhibitors (ICIs) are effective against a wide variety of cancers. However, they also induce a plethora of unique immune-related adverse events (irAEs). Since for many organ systems symptoms can be unspecific, differential diagnosis with progression of disease or infection may be difficult. C-reactive protein (CRP) has been suggested as a marker for infection. The purpose of this study was to evaluate the diagnostic value of CRP in differentiating infectious causes from autoimmune side effects induced by ICIs. Methods In order to investigate the role of CRP in irAEs, we screened our patient data base. Only events with full infectious workup were included. In total 88 events of irAEs in 37 melanoma patients were analyzed. CRP levels before and during irAEs were evaluated. Statistical analyses were conducted using the Chi-square test for categorical variables. Results At the onset of irAE, CRP rose in 93% of cases to a mean of 52.7 mg/L (CI 35.1-70.3) from 8.4 mg/L at baseline (normal < 5 mg/L) (P < 0.0001). Other causes of CRP elevation including infectious diseases were excluded, and procalcitonin (PCT) levels were normal in 92% of events. Importantly, in 42% of cases CRP elevations preceded clinical symptoms. Conclusion CRP elevation can predict the onset of irAEs in patients treated with ICIs in the absence of infectious disease.
CRIS-Team WoS Importer:2019-10-04

c-Rel is a cell cycle modulator in human melanoma cells - Priebe, Marie K.; Dewert, Nadin; Amschler, Katharina; Erpenbeck, Luise; Heinzerling, Lucie; Schoen, Michael P.; Seitz, Cornelia S.; Lorenz, Verena N. (Experimental Dermatology, 2019)
Melanoma progression and resistance to therapy are associated with faulty regulation of signalling molecules including the central transcription factor NF-kappa B. Increased expression of the c-Rel subunit of NF-kappa B has been described in progressing melanoma, though mechanistic implications of this upregulation remain unclear. To elucidate the functional role of c-Rel in melanoma biology, we have assessed its expression in human melanoma as well as in melanoma cell lines. Suppression of c-Rel expression in four melanoma cell lines resulted in reduced growth and altered cell cycle regulation, namely G2/M and polyploid phase induction. Moreover, mitotic spindle morphology was profoundly altered in three of the cell lines with a predominance of monopolar structures. These findings suggest that c-Rel is involved in G2/M phase regulation, prevention of polyploidy and, consequently, chromosomal stability. Our results highlight a novel tumor-promoting function of c-Rel in human melanoma cells through governing cell cycle regulation.
CRIS-Team WoS Importer:2019-02-21

Cutaneous, gastrointestinal, hepatic, endocrine, and renal side-effects of anti-PD-1 therapy - Hofmann, Lars; Forschner, Andrea; Loquai, Carmen; Goldinger, Simone M.; Zimmer, Lisa; Ugurel, Selma; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death receptor-1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma as well as for other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects affect skin, gastrointestinal tract, liver, endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centers were treated with pembrolizumab or nivolumab; 242 side-effects were described in 138 patients. In 116 of the 138 patients, side-effects affected the skin, gastrointestinal tract, liver, endocrine, and renal system. Rare side-effects included diabetes mellitus, lichen planus, and pancreas insufficiency due to pancreatitis.Anti-PD1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19570

Dataset of a retrospective multicenter cohort study on characteristics of immune checkpoint inhibitor-induced encephalitis and comparison with HSV-1 and anti-LGI1 encephalitis - Müller-Jensen, Leonie; Zierold, Sarah; Versluis, Judith M.; Boehmerle, Wolfgang; Huehnchen, Petra; Endres, Matthias; Mohr, Raphael; Compter, Annette; Blank, Christian U.; Hagenacker, Tim; Meier, Friedegund; Reinhardt, Lydia; et al. (Data in Brief, 2022)
Over the past decade, cancer immunotherapy with immune checkpoint inhibitors (ICIs) has significantly improved the outcome of many malignancies. However, with the broad use of ICIs, neurological immune related adverse events (irAE) are increasingly recognized. ICI-induced encephalitis (ICI-iE) is a particularly severe irAE, often leading to treatment termination, long-term sequalae or death. Despite its high morbidity and mortality, data on clinical features and diagnostic criteria are limited. We aimed to define clinical, radiologic and laboratory characteristics of ICI-iE and identify factors that discriminate it from anti-leucine-rich glioma-inactivated (anti-LGI)-1 encephalitis and herpes simplex virus (HSV)-1 encephalitis – two alternative causes of encephalitis – to increase the awareness of ICI-iE and improve its diagnosis and management. To that end, we retrospectively collected 30 cases of ICI-iE that were reported to the Side Effect Registry Immuno-Oncology (SERIO) and 46 cases of anti-LGI1 encephalitis or herpes simplex virus (HSV)-1 encephalitis that presented to a large German neurological referral center (Charité Universitätsmedizin Berlin) between January 2015 and September 2021. Signs and symptoms, imaging and electroencephalogram features, laboratory findings and outcome measures were assessed using standardized case report forms as well as patients’ medical records and compared between the groups. The data reported here represents the largest primary cohort of patients with ICI-iE to date and the first comparison with other types of encephalitis. As all three disorders – ICI-iE, HSV-1 encephalitis and anti-LGI1 encephalitis – are rare neurological entities, this dataset can be used as a reference in future clinical studies on ICI-induced neurotoxicity, neurological autoimmune disorders, and central nervous system infections.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Anti-LGI1 encephalitis; Cancer; Encephalitis; Herpetic encephalitis; Immune related adverse events; Immunotherapy; Neurotoxicity

Dedifferentiated and Undifferentiated Melanomas: Report of 35 New Cases with Literature Review and Proposal of Diagnostic Criteria - Agaimy, Abbas; Stöhr, Robert; Hornung, Annkathrin; Popp, Judith; Erdmann, Michael; Heinzerling, Lucie; Hartmann, Arndt (American Journal of Surgical Pathology, 2021)
Dedifferentiated melanoma (DM) and undifferentiated melanoma (UM) is defined as a primary or metastatic melanoma showing transition between conventional and undifferentiated components (DM) or lacking histologic and immunophenotypic features of melanoma altogether (UM). The latter is impossible to verify as melanoma by conventional diagnostic tools alone. We herein describe our experience with 35 unpublished cases to expand on their morphologic, phenotypic, and genotypic spectrum, along with a review of 50 previously reported cases (total: 85) to establish the diagnostic criteria. By definition, the dedifferentiated/undifferentiated component lacked expression of 5 routinely used melanoma markers (S100, SOX10, Melan-A, HMB45, Pan-melanoma). Initial diagnoses (known in 66 cases) were undifferentiated/unclassified pleomorphic sarcoma (n=30), unclassified epithelioid malignancy (n=7), pleomorphic rhabdomyosarcoma (n=5), other specific sarcoma types (n=6), poorly differentiated carcinoma (n=2), collision tumor (n=2), atypical fibroxanthoma (n=2), and reactive osteochondromatous lesion (n=1). In only 11 cases (16.6%) was a diagnosis of melanoma considered. Three main categories were identified: The largest group (n=56) comprised patients with a history of verified previous melanoma who presented with metastatic DM or UM. Axillary or inguinal lymph nodes, soft tissue, bone, and lung were mainly affected. A melanoma-compatible mutation was detected in 35 of 48 (73%) evaluable cases: BRAF (n=20; 40.8%), and NRAS (n=15; 30.6%). The second group (n=15) had clinicopathologic features similar to group 1, but a melanoma history was lacking. Axillary lymph nodes (n=6) was the major site in this group followed by the lung, soft tissue, and multiple site involvement. For this group, NRAS mutation was much more frequent (n=9; 60%) than BRAF (n=3; 20%) and NF1 (n=1; 6.6%). The third category (n=14) comprised primary DM (12) or UM (2). A melanoma-compatible mutation was detected in only 7 cases: BRAF (n=2), NF1 (n=2), NRAS (n=2), and KIT exon 11 (n=1). This extended follow-up study highlights the high phenotypic plasticity of DM/UM and indicates significant underrecognition of this aggressive disease among general surgical pathologists. The major clues to the diagnosis of DM and UM are: (1) presence of minimal differentiated clone in DM, (2) earlier history of melanoma, (3) undifferentiated histology that does not fit any defined entity, (4) locations at sites that are unusual for undifferentiated/unclassified pleomorphic sarcoma (axilla, inguinal, neck, digestive system, etc.), (5) unusual multifocal disease typical of melanoma spread, (6) detection of a melanoma-compatible gene mutation, and (7) absence of another genuine primary (eg, anaplastic carcinoma) in other organs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: BRAF; chondrosarcoma; dedifferentiated melanoma; giant cell tumor; KIT; NRAS; osteosarcoma; pleomorphic sarcoma; rhabdomyosarcoma; undifferentiated melanoma

Detection and Assessment of epidermotropic, pigmented Melanoma Metastases under Therapy using 3D Whole-Body Photography - Erdmann, M.; Toussaint, Frédéric; Hornung, Annkathrin; Heinzerling, Lucie; Berking, Carola; Schliep, S. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Detection and Characterization of Circulating Tumor Cells in Patients with Merkel Cell Carcinoma - Riethdorf, Sabine; Hildebrandt, Lina; Heinzerling, Lucie; Heitzer, Ellen; Fischer, Nicole; Bergmann, Sonja; Mauermann, Oliver; Waldispuehl-Geigl, Julie; Coith, Cornelia; Schoen, Gerhard; Peine, Sven; Schuler, Gerold; et al. (Clinical Chemistry, 2019)
BACKGROUND: Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer with increasing incidence and high mortality rates. MCC has recently become the subject of immune checkpoint therapy, but reliable biomarkers for estimating prognosis, risk stratification, and prediction of response are missing.
CRIS-Team WoS Importer:2019-03-15

Development of brain metastases and survival outcomes upon first-line systemic therapy in BRAF mutant and BRAF wildtype melanoma patients: a multicenter DeCOG study on 1704 patients from the prospective skin cancer registry ADOREG - Franklin, C.; Mohr, P.; Meier, F.; Weichenthal, M.; Grimmel-Mann, I.; Gutzmer, R.; Utikal, J. S.; Terheyden, P.; Herbst, R.; Haferkamp, S.; Pfohler, C.; Leiter-Stoppke, U.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Dual mtor/dna-pk inhibitor cc-115 induces cell death in melanoma cells and has radiosensitizing potential - Bürkel, Felix; Jost, Tina; Hecht, Markus; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
CC-115 is a dual inhibitor of the mechanistic target of rapamycin (mTOR) kinase and the DNA-dependent protein kinase (DNA-PK) that is currently being studied in phase I/II clinical trials. DNA-PK is essential for the repair of DNA-double strand breaks (DSB). Radiotherapy is frequently used in the palliative treatment of metastatic melanoma patients and induces DSBs. Melanoma cell lines and healthy-donor skin fibroblast cell lines were treated with CC-115 and ionizing irradiation (IR). Apoptosis, necrosis, and cell cycle distribution were analyzed. Colony forming assays were conducted to study radiosensitizing effects. Immunofluorescence microscopy was performed to determine the activity of homologous recombination (HR). In most of the malign cell lines, an increasing concentration of CC-115 resulted in increased cell death. Furthermore, strong cytotoxic effects were only observed in malignant cell lines. Regarding clonogenicity, all cell lines displayed decreased survival fractions during combined inhibitor and IR treatment and supra-additive effects of the combination were observable in 5 out of 9 melanoma cell lines. CC-115 showed radiosensitizing potential in 7 out of 9 melanoma cell lines, but not in healthy skin fibroblasts. Based on our data CC-115 treatment could be a promising approach for patients with metastatic melanoma, particularly in the combination with radiotherapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA repair; DNA-PK; Homologous recombination (HR); Kinase inhibitor; Melanoma; MTOR; Non-homologous end-joining (NHEJ); Radiosensitivity

Early Exanthema Upon Vemurafenib Plus Cobimetinib Is Associated With a Favorable Treatment Outcome in Metastatic Melanoma: A Retrospective Multicenter DeCOG Study - Kaehler, Katharina C.; Gutzmer, Ralf; Meier, Friedegrund; Zimmer, Lisa; Heppt, Markus; Gesierich, Anja; Thoms, Kai-Martin; Utikal, Jochen; Hassel, Jessica C.; Loquai, Carmen; Pfoehler, Claudia; Heinzerling, Lucie; et al. (Frontiers in Oncology, 2021)
Background: The combination of BRAF and MEK inhibitors has become standard of care in the treatment of metastatic BRAF V600-mutated melanoma. Clinical factors for an early prediction of tumor response are rare. The present study investigated the association between the development of an early exanthema induced by vemurafenib or vemurafenib plus cobimetinib and therapy outcome. Methods: This multicenter retrospective study included patients with BRAF V600-mutated irresectable AJCC-v8 stage IIIC/D to IV metastatic melanoma who received treatment with vemurafenib (VEM) or vemurafenib plus cobimetinib (COBIVEM). The development of an early exanthema within six weeks after therapy start and its grading according to CTCAEv4.0 criteria was correlated to therapy outcome in terms of best overall response, progression-free (PFS), and overall survival (OS). Results: A total of 422 patients from 16 centers were included (VEM, n=299; COBIVEM, n=123). 20.4% of VEM and 43.1% of COBIVEM patients developed an early exanthema. In the VEM cohort, objective responders (CR/PR) more frequently presented with an early exanthema than non-responders (SD/PD); 59.0% versus 38.7%; p=0.0027. However, median PFS and OS did not differ between VEM patients with or without an early exanthema (PFS, 6.9 versus 6.0 months, p=0.65; OS, 11.0 versus 12.4 months, p=0.69). In the COBIVEM cohort, 66.0% of objective responders had an early exanthema compared to 54.3% of non-responders (p=0.031). Median survival times were significantly longer for patients who developed an early exanthema compared to patients who did not (PFS, 9.7 versus 5.6 months, p=0.013; OS, not reached versus 11.6 months, p=0.0061). COBIVEM patients with a mild early exanthema (CTCAEv4.0 grade 1-2) had a superior survival outcome as compared to COBIVEM patients with a severe (CTCAEv4.0 grade 3-4) or non early exanthema, respectively (p=0.047). This might be caused by the fact that 23.6% of patients with severe exanthema underwent a dose reduction or discontinuation of COBIVEM compared to only 8.9% of patients with mild exanthema. Conclusions: The development of an early exanthema within 6 weeks after treatment start indicates a favorable therapy outcome upon vemurafenib plus cobimetinib. Patients presenting with an early exanthema should therefore be treated with adequate supportive measures to provide that patients can stay on treatment.
CRIS-Team Scopus Importer:2021-06-18
Keywords: BRAF/MEK inhibition; cobimetinib; melanoma; skin toxicity; therapy outcome; vemurafenib

ECP as prognostic Marker for Melanoma - Moreira, Alvaro; Krueckel, A.; Schuler, Gerold; Utikal, J.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Effective anti-programmed death-1 therapy in a SUFU-mutated patient with Gorlin-Goltz syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (British Journal of Dermatology, 2018)
We present the case of a 77-year-old male patient with more than 50 basal cell carcinomas on the head and upper trunk. The patient did not respond to several lines of treatment, including surgery, imiquimod, retinoids, itraconazole and therapy with the hedgehog inhibitor vismodegib. The patient responded well to off-label therapy with the anti-programmed death-1 antibody pembrolizumab after four infusions.
EVALuna2:34414

Eosinophil-cationic protein - a novel liquid prognostic biomarker in melanoma - Krueckel, Annika; Moreira, Alvaro; Froehlich, Waltraud; Schuler, Gerold; Heinzerling, Lucie (BMC Cancer, 2019)
BackgroundThe role of eosinophils in cancer is not yet completely understood, but patients with eosinophilia show a trend towards longer survival in several types of cancer, including melanoma. However, eosinophil count at initial diagnosis of metastatic melanoma does not predict survival. Since eosinophil cationic protein (ECP) mediates anticancer effects, such as tissue remodelling and cytotoxic activity, we investigated this marker as an early prognostic marker in metastatic melanoma.MethodsSerum of 56 melanoma patients was collected at the time of diagnosis of metastatic disease. ECP levels as measured by ELISA were correlated with overall survival (OS) in patients before systemic therapy with immunotherapy or chemotherapy. Statistical analyses were performed using the Log-Rank (Mantel-Cox) test.ResultsThe median OS for patients with high serum ECP above 12.2ng/ml was 12months (n=39), compared to 28months for patients with ECP below this threshold (n=17; p=0.0642). In patients with cutaneous melanoma, excluding patients with uveal and mucosal melanoma, the survival difference was even more striking (p=0.0393). ECP's effect size on OS was observed independently of the consecutive therapy. ECP levels were not correlated with LDH levels.ConclusionECP seems to be a novel prognostic serum marker for the outcome of melanoma patients, which is independent of LDH and easy to perform in clinical practice. The striking negative prognostic value of high ECP level is unanticipated and can guide patient management.
CRIS-Team WoS Importer:2019-03-22

Eosinophil-cationic protein: A novel liquid prognostic biomarker in melanoma - Moreira, Alvaro; Krueckel, Annika; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:203621

Eosinophilic count as a biomarker for prognosis of melanoma patients and its importance in the response to immunotherapy - Moreira, Alvaro; Leisgang, Waltraud; Schuler, Gerold; Heinzerling, Lucie (Immunotherapy, 2017)
AIM: The prognostic role of eosinophils in cancer has been controversial. Some entities such as gastrointestinal cancers show a better survival, while others such as Hodgkin's lymphoma a worse survival in patients with eosinophilia. Patients who exhibited an increase in eosinophils upon therapy with ipilimumab or pembrolizumab were shown to survive longer. We wanted to investigate whether eosinophilia is a prognostic marker in metastatic melanoma. METHODS: In total, 173 patients with metastatic melanoma from our data base (median age 60 years; n = 86 with immunotherapy, n = 87 without immunotherapy) were analyzed for eosinophil counts and survival over the course of 12 years. Eosinophilic count was detected by peripheral blood smear. The ethical committee had approved this retrospective study. RESULTS: Melanoma patients with eosinophilia at any point in their course of disease show a trend toward longer survival independently of their therapy. There is a statistically significant difference for the patients who survive at least 12 months (p < 0.005). In patients with checkpoint inhibitor therapy, survival was significantly prolonged in every patient with eosinophilia (p < 0.05). Furthermore, 69% of the patients treated with immunotherapy experienced at least once an eosinophilia of 5% or greater compared with 46% in the immunotherapy naive-group; for an eosinophilia of 10% values were 30 and 9%, respectively. Interestingly, in patients with more than 20% eosinophils (n = 7) survival was prolonged with a median of 35 months (range 19-60 months) as compared with 16 months (range 1-117 months). CONCLUSION: Eosinophilia is a prognostic marker in patients with metastatic melanoma.
EVALuna2:34325

Eosinophilic count as a biomarker for prognosis of melanoma patients - Moreira, Alvaro; Heinzerling, Lucie (2017)
EVALuna2:34330

Eosinophilic Fasciitis by Treatment with Checkpoint Inhibitors in metastatic Melanoma - Toussaint, Frédéric; Erdmann, M.; Moreira, Alvaro; Kirchberger, M. C.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34779

Evaluating HIV Prevention Programs: Herpes Simplex Virus Type 2 Antibodies as Biomarker for Sexual Risk Behavior in Young Adults in Resource-Poor Countries - Behling, Juliane; Chan, Adrienne K.; Zeh, Clement; Nekesa, Carolyne; Heinzerling, Lucie (PLoS ONE, 2015)
Measuring effectiveness of HIV prevention interventions is challenged by bias when using self-reported knowledge, attitude or behavior change. HIV incidence is an objective marker to measure effectiveness of HIV prevention interventions, however, because new infection rates are relatively low, prevention studies require large sample sizes. Herpes simplex virus type 2 (HSV-2) is similarly transmitted and more prevalent and could thus serve as a proxy marker for sexual risk behavior and therefore HIV infection.HSV-2 antibodies were assessed in a sub-study of 70,000 students participating in an education intervention in Western Province, Kenya. Feasibility of testing for HSV-2 antibodies was assessed comparing two methods using Fisher's exact test. Three hundred and ninety four students (aged 18 to 22 years) were randomly chosen from the cohort and tested for HIV, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis. Out of these, 139 students were tested for HSV-2 with ELISA and surveyed for sexual risk behavior and 89 students were additionally tested for HSV-2 with a point-of-contact (POC) test.Prevalence rates were 0.5%, 1.8%, 0.3% and 2.3% for HIV, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis, respectively. Prevalence of HSV-2 antibodies was 3.4 % as measured by POC test (n=89) and 14.4 % by ELISA (n=139). Specificity of the POC test compared with ELISA was 100%, and the sensitivity only 23.1%. Associations between self-reported sexual behavior and HSV-2 serostatus could not be shown.Associations between self-reported sexual risk behavior and HSV-2 serostatus could not be shown, probably due to social bias in interviews since its transmission is clearly linked. HSV-2 antibody testing is feasible in resource-poor settings and shows higher prevalence rates than other sexually transmitted diseases thus representing a potential biomarker for evaluation of HIV prevention interventions.
EVALuna2:19581

Experiences of In-Patients with Skin Cancer in a German University Hospital Setting: A Cross-Sectional Survey - Steeb, Theresa; Wessely, Anja; Merkl, Heike; Voskens, Caroline; Erdmann, Michael; Heinzerling, Lucie; Berking, Carola; Heppt, Markus (Patient Preference and Adherence, 2021)
Purpose: An important measure of hospital quality is the satisfaction of the patients receiving in-patient care. This cross-sectional study aimed to assess skin cancer patients' experiences in a university hospital setting as a measure of quality of cancer care.
CRIS-Team WoS Importer:2021-01-29

Expression of Senescence Markers - Is Predictive for Immune Therapy with Checkpoint Inhibitors? - Moreira, Alvaro; Gross, S.; Kirchberger, M. C.; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34778

Fear of cancer progression in patients with stage IA malignant melanoma - Wagner, Tobias; Augustin, Matthias; Blome, Christine; Forschner, Andrea; Garbe, Claus; Gutzmer, Ralf; Hauschild, Axel; Heinzerling, Lucie; Livingstone, Elisabeth; Loquai, Carmen; Schadendorf, Dirk; Terheyden, Patrick; et al. (European Journal of Cancer Care, 2018)
We aimed to determine the prevalence and importance of fear of cancer progression (FoP) in melanoma patients with stage IA tumours to assess psychosocial and demographic factors associated with severity of FoP and to determine the relationship of FoP and quality of life (QoL). One hundred and thirty-six patients with stage IA melanoma completed the short version of the Fear of Progression Questionnaire (FoP-Q-SF), the Hospital Anxiety and Depression Scale (HADS) and the EORTC-QLQ-C30. We found a mean FoP-Q-SF sum score of 30.2 points (±8.4 points SD). In this study, 33% of patients reported high FoP at or above the cutoff-value of 34 points. Higher FoP was found in women (p < 0.01), young (p = 0.03) and employed (p = 0.02) patients. Being confronted with a cancer diagnosis in closely related persons predicted higher FoP (p < 0.01). FoP correlated positively with the HADS anxiety (r = 0.50, p < 0.01) and depression scales (r = 0.26, p < 0.01) and negatively with the EORTC-QLQ-C30 global health state (r = -0.32, p < 0.01). FoP is considerably prevalent in low-risk melanoma patients and associated with reduced QoL, cancer in related persons, women sex and participation in working life. Considerably high levels of FoP, even in patients with low-risk malignancies, underline the need for psychosocial support and psychotherapeutic interventions for melanoma patients.
EVALuna2:34765

Fear of progression in patients with low-risk malignant melanoma - Wagner, T.; Augustin, M.; Blome, C.; Forschner, A.; Garbe, C.; Gutzmer, R.; Hauschild, A.; Heinzerling, Lucie; Livingstone, E.; Mueller-Brenne, T.; Loquai, C.; Schadendorf, D.; et al. (2017)
EVALuna2:34364

Federated Learning for Decentralized Artificial Intelligence in Melanoma Diagnostics - Haggenmüller, Sarah; Schmitt, Max; Krieghoff-Henning, Eva; Hekler, Achim; Maron, Roman C.; Wies, Christoph; Utikal, Jochen S.; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; et al. (JAMA Dermatology, 2024)
Importance: The development of artificial intelligence (AI)-based melanoma classifiers typically calls for large, centralized datasets, requiring hospitals to give away their patient data, which raises serious privacy concerns. To address this concern, decentralized federated learning has been proposed, where classifier development is distributed across hospitals. Objective: To investigate whether a more privacy-preserving federated learning approach can achieve comparable diagnostic performance to a classical centralized (ie, single-model) and ensemble learning approach for AI-based melanoma diagnostics. Design, Setting, and Participants: This multicentric, single-arm diagnostic study developed a federated model for melanoma-nevus classification using histopathological whole-slide images prospectively acquired at 6 German university hospitals between April 2021 and February 2023 and benchmarked it using both a holdout and an external test dataset. Data analysis was performed from February to April 2023. Exposures: All whole-slide images were retrospectively analyzed by an AI-based classifier without influencing routine clinical care. Main Outcomes and Measures: The area under the receiver operating characteristic curve (AUROC) served as the primary end point for evaluating the diagnostic performance. Secondary end points included balanced accuracy, sensitivity, and specificity. Results: The study included 1025 whole-slide images of clinically melanoma-suspicious skin lesions from 923 patients, consisting of 388 histopathologically confirmed invasive melanomas and 637 nevi. The median (range) age at diagnosis was 58 (18-95) years for the training set, 57 (18-93) years for the holdout test dataset, and 61 (18-95) years for the external test dataset; the median (range) Breslow thickness was 0.70 (0.10-34.00) mm, 0.70 (0.20-14.40) mm, and 0.80 (0.30-20.00) mm, respectively. The federated approach (0.8579; 95% CI, 0.7693-0.9299) performed significantly worse than the classical centralized approach (0.9024; 95% CI, 0.8379-0.9565) in terms of AUROC on a holdout test dataset (pairwise Wilcoxon signed-rank, P <.001) but performed significantly better (0.9126; 95% CI, 0.8810-0.9412) than the classical centralized approach (0.9045; 95% CI, 0.8701-0.9331) on an external test dataset (pairwise Wilcoxon signed-rank, P <.001). Notably, the federated approach performed significantly worse than the ensemble approach on both the holdout (0.8867; 95% CI, 0.8103-0.9481) and external test dataset (0.9227; 95% CI, 0.8941-0.9479). Conclusions and Relevance: The findings of this diagnostic study suggest that federated learning is a viable approach for the binary classification of invasive melanomas and nevi on a clinically representative distributed dataset. Federated learning can improve privacy protection in AI-based melanoma diagnostics while simultaneously promoting collaboration across institutions and countries. Moreover, it may have the potential to be extended to other image classification tasks in digital cancer histopathology and beyond..
CRIS-Team Scopus Importer:2024-02-23

Four cases of erysipelas-like inflammation in patients with metastatic melanoma treated with checkpoint inhibitors - Pföhler, Claudia; Hassel, Jessica C.; Heinzerling, Lucie; Müller, Cornelia S.L. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-10-16

FV03 MEK Inhibitors improved the Survival of NRAS-mutated Melanoma Patients by using Checkpoint Inhibitors: Results of a retrospective, multicenter Analysis of 364 Patients - Kirchberger, M. C.; Ugurel, S.; Mangana, J.; Heppt, M.; Eigentler, T.; Berking, C.; Schadendorf, D.; Schuler, Gerold; Dummer, R.; Heinzerling, Lucie (2018)
EVALuna2:34766

Global Circumferential and Radial Strain Among Patients With Immune Checkpoint Inhibitor Myocarditis - Quinaglia, Thiago; Gongora, Carlos; Awadalla, Magid; Hassan, Malek Z.O.; Zafar, Amna; Drobni, Zsofia D.; Mahmood, Syed S.; Zhang, Lili; Coelho-Filho, Otavio R.; Suero-Abreu, Giselle A.; Rizvi, Muhammad A.; Sahni, Gagan; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
Background: Global circumferential strain (GCS) and global radial strain (GRS) are reduced with cytotoxic chemotherapy. There are limited data on the effect of immune checkpoint inhibitor (ICI) myocarditis on GCS and GRS. Objectives: This study aimed to detail the role of GCS and GRS in ICI myocarditis. Methods: In this retrospective study, GCS and GRS from 75 cases of patients with ICI myocarditis and 50 ICI-treated patients without myocarditis (controls) were compared. Pre-ICI GCS and GRS were available for 12 cases and 50 controls. Measurements were performed in a core laboratory blinded to group and time. Major adverse cardiovascular events (MACEs) were defined as a composite of cardiogenic shock, cardiac arrest, complete heart block, and cardiac death. Results: Cases and controls were similar in age (66 ± 15 years vs 63 ± 12 years; P = 0.20), sex (male: 73% vs 61%; P = 0.20) and cancer type (P = 0.08). Pre-ICI GCS and GRS were also similar (GCS: 22.6% ± 3.4% vs 23.5% ± 3.8%; P = 0.14; GRS: 45.5% ± 6.2% vs 43.6% ± 8.8%; P = 0.24). Overall, 56% (n = 42) of patients with myocarditis presented with preserved left ventricular ejection fraction (LVEF). GCS and GRS were lower in myocarditis compared with on-ICI controls (GCS: 17.5% ± 4.2% vs 23.6% ± 3.0%; P < 0.001; GRS: 28.6% ± 6.7% vs 47.0% ± 7.4%; P < 0.001). Over a median follow-up of 30 days, 28 cardiovascular events occurred. A GCS (HR: 4.9 [95% CI: 1.6-15.0]; P = 0.005) and GRS (HR: 3.9 [95% CI: 1.4-10.8]; P = 0.008) below the median was associated with an increased event rate. In receiver-operating characteristic (ROC) curves, GCS (AUC: 0.80 [95% CI: 0.70-0.91]) and GRS (AUC: 0.76 [95% CI: 0.64-0.88]) showed better performance than cardiac troponin T (cTnT) (AUC: 0.70 [95% CI: 0.58-0.82]), LVEF (AUC: 0.69 [95% CI: 0.56-0.81]), and age (AUC: 0.54 [95% CI: 0.40-0.68]). Net reclassification index and integrated discrimination improvement demonstrated incremental prognostic utility of GRS over LVEF (P = 0.04) and GCS over cTnT (P = 0.002). Conclusions: GCS and GRS are lower in ICI myocarditis, and the magnitude of reduction has prognostic significance.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cardiovascular risk stratification; immune checkpoint inhibitors; myocarditis; strain modalities survival analysis

Global Longitudinal Strain and Cardiac Events in Patients With Immune Checkpoint Inhibitor-Related Myocarditis - Awadalla, Magid; Mahmood, Syed S.; Groarke, John D.; Hassan, Malek Z.O.; Nohria, Anju; Rokicki, Adam; Murphy, Sean P.; Mercaldo, Nathaniel D.; Zhang, Lili; Zlotoff, Daniel A.; Reynolds, Kerry L.; Alvi, Raza M.; et al. (Journal of the American College of Cardiology, 2020)
Background: There is a need for improved methods for detection and risk stratification of myocarditis associated with immune checkpoint inhibitors (ICIs). Global longitudinal strain (GLS) is a sensitive marker of cardiac toxicity among patients receiving standard chemotherapy. There are no data on the use of GLS in ICI myocarditis. Objectives: This study sought to evaluate the role of GLS and assess its association with cardiac events among patients with ICI myocarditis. Methods: This study retrospectively compared echocardiographic GLS by speckle tracking at presentation with ICI myocarditis (cases, n = 101) to that from patients receiving an ICI who did not develop myocarditis (control subjects, n = 92). Where available, GLS was also measured pre-ICI in both groups. Major adverse cardiac events (MACE) were defined as a composite of cardiogenic shock, arrest, complete heart block, and cardiac death. Results: Cases and control subjects were similar in age, sex, and cancer type. At presentation with myocarditis, 61 cases (60%) had a normal ejection fraction (EF). Pre-ICI, GLS was similar between cases and control subjects (20.3 ± 2.6% vs. 20.6 ± 2.0%; p = 0.60). There was no change in GLS among control subjects on an ICI without myocarditis (pre-ICI vs. on ICI, 20.6 ± 2.0% vs. 20.5 ± 1.9%; p = 0.41); in contrast, among cases, GLS decreased to 14.1 ± 2.8% (p < 0.001). The GLS at presentation with myocarditis was lower among cases presenting with either a reduced (12.3 ± 2.7%) or preserved EF (15.3 ± 2.0%; p < 0.001). Over a median follow-up of 162 days, 51 (51%) experienced MACE. The risk of MACE was higher with a lower GLS among patients with either a reduced or preserved EF. After adjustment for EF, each percent reduction in GLS was associated with a 1.5-fold increase in MACE among patients with a reduced EF (hazard ratio: 1.5; 95% confidence interval: 1.2 to 1.8) and a 4.4-fold increase with a preserved EF (hazard ratio: 4.4; 95% confidence interval: 2.4 to 7.8). Conclusions: GLS decreases with ICI myocarditis and, compared with control subjects, was lower among cases presenting with either a preserved or reduced EF. Lower GLS was strongly associated with MACE in ICI myocarditis presenting with either a preserved or reduced EF.
CRIS-Team Scopus Importer:2020-02-04
Keywords: global longitudinal strain; immune checkpoint inhibitors; major adverse cardiac events; myocarditis

Grade 4 Neutropenia Secondary to Immune Checkpoint Inhibition — A Descriptive Observational Retrospective Multicenter Analysis - Zaremba, Anne; Kramer, Rafaela; De Temple, Viola; Bertram, Stefanie; Salzmann, Martin; Gesierich, Anja; Reinhardt, Lydia; Baroudjian, Barouyr; Sachse, Michael M.; Mechtersheimer, Gunhild; Johnson, Douglas B.; Weppler, Alison M.; et al. (Frontiers in Oncology, 2021)
Introduction: Immune checkpoint inhibitors (ICI) are increasingly being used to treat numerous cancer types. Together with improved recognition of toxicities, this has led to more frequent identification of rare immune-related adverse events (irAE), for which specific treatment strategies are needed. Neutropenia is a rare hematological irAE that has a potential for a high mortality rate because of its associated risk of sepsis. Prompt recognition and timely treatment of this life-threatening irAE are therefore critical to the outcome of patients with immune-related neutropenia. Methods: This multicenter international retrospective study was conducted at 17 melanoma centers to evaluate the clinical characteristics, diagnostics, treatment, and outcomes of melanoma patients with grade 4 neutropenia (<500 neutrophils/µl blood) treated with ICI between 2014 and 2020. Some of these patients received metamizole in addition to ICI (ICI+/met+). Bone marrow biopsies (BMB) of these patients were compared to BMB from non-ICI treated patients with metamizole-induced grade 4 neutropenia (ICI-/met+). Results: In total, 10 patients (median age at neutropenia onset: 66 years; seven men) with neutropenia were identified, equating to an incidence of 0.14%. Median onset of neutropenia was 6.4 weeks after starting ICI (range 1.4–49.1 weeks). Six patients showed inflammatory symptoms, including fever (n=3), erysipelas (n=1), pharyngeal abscess (n=1), and mucositis (n=1). Neutropenia was diagnosed in all patients by a differential blood count and additionally performed procedures including BMB (n=5). Nine of 10 patients received granulocyte colony-stimulating factors (G-CSF) to treat their grade 4 neutropenia. Four patients received systemic steroids (including two in combination with G-CSF, and one in combination with G-CSF and additional ciclosporin A). Four patients were treated with one or more antibiotic treatment lines, two with antimycotic treatment, and one with additional antiviral therapy. Five patients received metamizole concomitantly with ICI. One fatal outcome was reported. BMB indicated a numerically lower CD4+ to CD8+ T cells ratio in patients with irNeutropenia than in those with metamizole-induced neutropenia. Conclusion: Grade 4 neutropenia is a rare but potentially life-threatening side effect of ICI treatment. Most cases were sufficiently managed using G-CSF; however, adequate empiric antibiotic, antiviral, and antimycotic treatments should be administered if neutropenic infections are suspected. Immunosuppression using corticosteroids may be considered after other causes of neutropenia have been excluded.
CRIS-Team Scopus Importer:2021-12-10
Keywords: adverse events; hematotoxicity; immune checkpoint inhibition; malignant melanoma; neutropenia

Health-related quality of life (EuroQol 5D-5L) in patients with autoimmunity in the context of immunotherapy: A large dataset comprising cancer patients after cessation of checkpoint inhibitor therapy and patients with autoimmune diseases - Schulz, Thomas U.; Zierold, Sarah; Sachse, Michael M.; Pesch, Giulia; Tomsitz, Dirk; Schilbach, Katharina; Kähler, Katharina C.; French, Lars E.; Heinzerling, Lucie (Data in Brief, 2022)
This dataset contains demographic, clinical, and health-related quality of life (HRQoL) data from 2905 patients including 200 cancer patients after immune checkpoint inhibitor (ICI) cessation and 2705 patients with a wide variety of autoimmune diseases. Within this multicenter, cross-sectional survey study data were collected questionnaire-based in cancer patients (ICI-patients) ≥ 18 years of age who had received at least one dose of ICI with ≥ 12 weeks since ICI discontinuation. Patients with autoimmune diseases (AI-patients) were ≥ 18 years, had at least one autoimmune disease and had never received ICI. ICI-patients were recruited in three skin cancer centers and via support groups. AI-patients were recruited in an outpatient clinic for internal medicine and via support groups. Specific questionnaires for ICI-patients/AI-patients were provided paper-based for patients from outpatient clinics and online for patients from support groups. Both questionnaires contained sections with demographic information, clinical data, and the standardized patient-reported outcome measure EuroQol 5D-5L (EQ-5D-5L) to assess HRQoL. Clinical data focused on autoimmunity and therapy of autoimmunity in (1) ICI-patients referring to particularly persistent immune-related adverse events (persistent irAEs) and in (2) AI-patients referring to respective autoimmune diseases. Additionally, specific items on cancer and cancer therapy were included in ICI-patients, and AI-patients were asked about the presence of acute exacerbations of autoimmune diseases. This dataset contains the raw data for ICI-patients and AI-patients, analyzed data on patient demographics, clinical characteristics and HRQoL scores among ICI-patients with/without persistent irAEs and among AI-patients. The data provide a basis for further investigations within the cohort of ICI-patients after ICI cessation and/or for AI-patients with different autoimmune diseases with regard to HRQoL, autoimmunity and therapy of autoimmunity.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Chronic toxicities; hypothyroidism; Long-term sequelae; Melanoma; Persistent immune-related adverse events (persistent irAEs); Sarcoidosis; Sjogren's syndrome; Vitiligo

Hematological immune related adverse events after treatment with immune checkpoint inhibitors - Kramer, Rafaela; Zaremba, Anne; Moreira, Alvaro; Ugurel, Selma; Johnson, Douglas B.; Hassel, Jessica C.; Salzmann, Martin; Gesierich, Anja; Weppler, Alison; Spain, Lavinia; Loquai, Carmen; Dudda, Milena; et al. (European Journal of Cancer, 2021)
Introduction: With the increasing use of checkpoint inhibitors, rare immune-related adverse events (irAE) are being identified. Haematological irAE (hem-irAE) are difficult to treat and have shown high mortality rates. In order to improve side-effect management for these potentially life-threatening events, we analysed frequency, severity and outcomes. Patients and methods: Patients who developed hem-irAE while being treated with immune checkpoint inhibitors (ICI) therapy were retrospectively identified from 18 international cancer centres. Results: In total, more than 7626 patients treated with ICI were screened, and 50 patients with hem-irAE identified. The calculated incidence amounts to 0.6% and median onset was 6 weeks after the ICI initiation (range 1–128 weeks). Thrombocytopenia and leucopaenia were the most frequent hem-irAE with 34% (17/50) and 34% (17/50), respectively, followed by anaemia 28% (14/50), hemophagocytic lymphohistiocytosis (4% (2/50)), aplastic anaemia (2% (1/50)), acquired haemophilia A (2% (1/50)) and coagulation deficiency (2% (1/50)). Simultaneous thrombocytopenia and neutropenia occurred in two patients, concurrent anaemia and thrombocytopenia in one patient. Other than cessation of ICI (in 60%) and corticosteroids (in 78%), treatment included second-line immunosuppression in 24% of cases. Events resolved in 78% (39/50), while 18% (9/50) had persistent changes, and 2% (1/50) had fatal outcomes (agranulocytosis). Conclusion: Hem-irAE can affect all haematopoietic blood cell lineages and may persist or even be fatal. Management may require immunosuppression beyond corticosteroids. Although these irAE are rare, treating physicians should be aware, monitor blood counts regularly and promptly act upon detection.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Anaemia; Anti-CTLA-4-Antibody; Anti-PD1-Antibody; Autoimmunity; Haematotoxicity; Hemophagocytic lymphohistiocytosis; Leucopaenia; Neutropenia; Side-effects; Thrombocytopenia

Hyponatremia and Nephritis - Rare Side Effects of Checkpoint Inhibitors in Patients with metastatic Melanoma - Mitzel-Rink, H.; Hassel, J.; Berking, C.; Gutzmer, R.; Heinzerling, Lucie; Majenka, P.; Meier, F.; Moreira, Alvaro; Terheyden, P.; Thoms, K. M.; Tietze, J.; Zimmer, L.; et al. (2018)
EVALuna2:34770

"I Feel I'm in Best Hands with You!": A Survey of Patient Satisfaction in a German University Skin Cancer Centre - Steeb, Theresa; Wessely, Anja; Merkl, Heike; Kirchberger, Michael; Bosch-Voskens, Caroline; Erdmann, Michael; Heinzerling, Lucie; Berking, Carola; Heppt, Markus (Acta Dermato-Venereologica, 2021)
An important measure of hospital quality is the satisfaction of patients. The aim of this cross-sectional study, performed in the dermato-oncology unit of the university hospital in Erlangen, Germany, was to assess skin cancer patients' degree of satisfaction with healthcare services. Self-administered questionnaires on patient satisfaction regarding contact with staff, need for information, and recommendation of the skin cancer centre were distributed in the day-care unit and the outpatient department to patients between April and June 2017. Results were reported descriptively and subgroup differences were explored using the Mann-Whitney U test, binary logistic regression, or χ2 test. Overall, 496 of 571 questionnaires were returned (86.9%). The median of all satisfaction items ranged between 1 (very good) and 2 (good). The majority of patients wanted more detailed information about skin cancer (46.7%, 142/304). Long waiting times were often criticized (22.8%; 80/351). Particular attention in addressing specific needs and fears may further increase patient satisfaction.
CRIS-Team Scopus Importer:2021-08-13
Keywords: cross-sectional study; melanoma; quality improvement; quality of care; skin cancer; patient satisfaction

Immune-Checkpoint-Blockade for Merkel Cell Carcinoma: Clinical and molecular Biomarker-Analysis - Spassova, I.; Ugurel, S.; Zimmer, L.; Schadendorf, D.; Terheyden, P.; Andtback, H. B.; Villabona, L.; Leiter-Stoeppke, U.; Eigentler, T.; Loquai, C.; Hassel, J. C.; Gambichler, T.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Immune checkpoint inhibition therapy for advanced skin cancer in patients with concomitant hematological malignancy: a retrospective multicenter DeCOG study of 84 patients - Leiter, Ulrike; Loquai, Carmen; Reinhardt, Lydia; Rafei-Shamsabadi, David; Gutzmer, Ralf; Kaehler, Katharina; Heinzerling, Lucie; Hassel, Jessica C.; Glutsch, Valerie; Sirokay, Judith; Schlecht, Nora; Rübben, Albert; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: Skin cancers are known for their strong immunogenicity, which may contribute to a high treatment efficacy of immune checkpoint inhibition (ICI). However, a considerable proportion of patients with skin cancer is immuno-compromised by concomitant diseases. Due to their previous exclusion from clinical trials, the ICI treatment efficacy is poorly investigated in these patients. The present study analyzed the ICI treatment outcome in advanced patients with skin cancer with a concomitant hematological malignancy. METHODS: This retrospective multicenter study included patients who were treated with ICI for locally advanced or metastatic melanoma (MM), cutaneous squamous cell carcinoma (cSCC), or Merkel cell carcinoma (MCC), and had a previous diagnosis of a hematological malignancy irrespective of disease activity or need of therapy at ICI treatment start. Comparator patient cohorts without concomitant hematological malignancy were extracted from the prospective multicenter skin cancer registry ADOREG. Treatment outcome was measured as best overall response, progression-free (PFS), and overall survival (OS). RESULTS: 84 patients (MM, n=52; cSCC, n=15; MCC, n=17) with concomitant hematological malignancy were identified at 20 skin cancer centers. The most frequent concomitant hematological malignancies were non-Hodgkin's lymphoma (n=70), with chronic lymphocytic leukemia (n=32) being the largest entity. While 9 patients received ICI in an adjuvant setting, 75 patients were treated for advanced non-resectable disease (55 anti-PD-1; 8 anti-PD-L1; 5 anti-CTLA-4; 7 combinations). In the latter 75 patients, best objective response (complete response+partial response) was 28.0%, disease stabilization was 25.3%, and 38.6% showed progressive disease (PD). Subdivided by skin cancer entity, best objective response was 31.1% (MM), 26.7% (cSCC), and 18.8% (MCC). Median PFS was 8.4 months (MM), 4.0 months (cSCC), and 5.7 months (MCC). 1-year OS rates were 78.4% (MM), 65.8% (cSCC), and 47.4% (MCC). Comparison with respective ADOREG patient cohorts without hematological malignancy (n=392) revealed no relevant differences in ICI therapy outcome for MM and MCC, but a significantly reduced PFS for cSCC (p=0.002). CONCLUSIONS: ICI therapy showed efficacy in advanced patients with skin cancer with a concomitant hematological malignancy. Compared with patients without hematological malignancy, the observed ICI therapy outcome was impaired in cSCC, but not in MM or MCC patients.
CRIS-Team Scopus Importer:2020-11-06
Keywords: immunotherapy; melanoma

IMMUNE PROFILING OF PATIENTS WITH ADVANCED SOLID TUMORS TREATED WITH INTRATUMORALLY ADMINISTERED CV8102 AS A SINGLE-AGENT OR IN COMBINATION WITH ANTI-PD-1 ANTIBODIES IN PHASE I CLINICAL TRIAL - Codo, Paula; Eigentler, Thomas; Heinzerling, Lucie; Krauss, Juergen; Weishaupt, Carsten; Ochsenreither, Sebastian; Lebbe, Celeste; Mohr, Peter; Oliva, Marc; Oberoi, Honey; Terheyden, Patrick; Perez, Jose Trigo; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
CV8102 is a non-coding, non-capped RNA complexed with a carrier peptide activating the innate (via TLR7/8, RIG-I) and adaptive immune system.1 2 An ongoing phase I trial is investigating the intratumoral (i.t.) administration of CV8102 in patients with advanced cutaneous melanoma (cMEL), squamous cell carcinoma of the skin (cSCC) or head and neck (hnSCC) and adenoid cystic carcinoma (ACC), either as a single agent or in combination with systemic anti-PD-1 antibodies. Preliminary immune profiling results will be reported.<br
CRIS-Team WoS Importer:2022-04-15

Immune signatures predict development of autoimmune toxicity in patients with cancer treated with immune checkpoint inhibitors - Nuñez, Nicolas Gonzalo; Berner, Fiamma; Friebel, Ekaterina; Unger, Susanne; Wyss, Nina; Gomez, Julia Martinez; Purde, Mette Triin; Niederer, Rebekka; Porsch, Maximilian; Lichtensteiger, Christa; Kramer, Rafaela; Erdmann, Michael; et al. (Med, 2023)
Background: Immune checkpoint inhibitors (ICIs) are among the most promising treatment options for melanoma and non-small cell lung cancer (NSCLC). While ICIs can induce effective anti-tumor responses, they may also drive serious immune-related adverse events (irAEs). Identifying biomarkers to predict which patients will suffer from irAEs would enable more accurate clinical risk-benefit analysis for ICI treatment and may also shed light on common or distinct mechanisms underpinning treatment success and irAEs. Methods: In this prospective multi-center study, we combined a multi-omics approach including unbiased single-cell profiling of over 300 peripheral blood mononuclear cell (PBMC) samples and high-throughput proteomics analysis of over 500 serum samples to characterize the systemic immune compartment of patients with melanoma or NSCLC before and during treatment with ICIs. Findings: When we combined the parameters obtained from the multi-omics profiling of patient blood and serum, we identified potential predictive biomarkers for ICI-induced irAEs. Specifically, an early increase in CXCL9/CXCL10/CXCL11 and interferon-γ (IFN-γ) 1 to 2 weeks after the start of therapy are likely indicators of heightened risk of developing irAEs. In addition, an early expansion of Ki-67+ regulatory T cells (Tregs) and Ki-67+ CD8+ T cells is also likely to be associated with increased risk of irAEs. Conclusions: We suggest that the combination of these cellular and proteomic biomarkers may help to predict which patients are likely to benefit most from ICI therapy and those requiring intensive monitoring for irAEs. Funding: This work was primarily funded by the European Research Council, the Swiss National Science Foundation, the Swiss Cancer League, and the Forschungsförderung of the Kantonsspital St. Gallen.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biomarkers for immunotherapy; cancer immunotherapy; checkpoint blockade; immune-related adverse events; Translation to patients

Impact of a preceding radiotherapy on the outcome of immune checkpoint inhibition in metastatic melanoma: a multicenter retrospective cohort study of the DeCOG - Knispel, Sarah; Stang, Andreas; Zimmer, Lisa; Lax, Hildegard; Gutzmer, Ralf; Heinzerling, Lucie; Weishaupt, Carsten; Pföhler, Claudia; Gesierich, Anja; Herbst, Rudolf; Kaehler, Katharina C.; Weide, Benjamin; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: Immune checkpoint inhibition (ICI) is an essential treatment option in melanoma. Its outcome may be improved by a preceding radiation of metastases. This study aimed to investigate the impact of a preceding radiotherapy on the clinical outcome of ICI treatment. METHODS: This multicenter retrospective cohort study included patients who received anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) or anti-programmed cell death protein 1 (PD-1) ICI with or without preceding radiotherapy for unresectable metastatic melanoma. ICI therapy outcome was measured as best overall response (BOR), progression-free (PFS) and overall survival (OS). Response and survival analyses were adjusted for confounders identified by directed acyclic graphs. Adjusted survival curves were calculated using inverse probability treatment weighting. RESULTS: 835 patients who received ICI (anti-CTLA-4, n=596; anti-PD-1, n=239) at 16 centers were analyzed, whereof 235 received a preceding radiotherapy of metastatic lesions in stage IV disease. The most frequent organ sites irradiated prior to ICI therapy were brain (51.1%), lymph nodes (17.9%) and bone (17.9%). After multivariable adjustment for confounders, no relevant differences in ICI therapy outcome were observed between cohorts with and without preceding radiotherapy. BOR was 8.7% vs 13.0% for anti-CTLA-4 (adjusted relative risk (RR)=1.47; 95% CI=0.81 to 2.65; p=0.20), and 16.5% vs 25.3% for anti-PD-1 (RR=0.93; 95% CI=0.49 to 1.77; p=0.82). Survival probabilities were similar for cohorts with and without preceding radiotherapy, for anti-CTLA-4 (PFS, adjusted HR=1.02, 95% CI=0.86 to 1.25, p=0.74; OS, HR=1.08, 95% CI=0.81 to 1.44, p=0.61) and for anti-PD-1 (PFS, HR=0.84, 95% CI=0.57 to 1.26, p=0.41; OS, HR=0.73, 95% CI=0.43 to 1.25, p=0.26). Patients who received radiation last before ICI (n=137) revealed no better survival than those who had one or more treatment lines between radiation and start of ICI (n=86). In 223 patients with brain metastases, we found no relevant survival differences on ICI with and without preceding radiotherapy. CONCLUSIONS: This study detected no evidence for a relevant favorable impact of a preceding radiotherapy on anti-CTLA-4 or anti-PD-1 ICI treatment outcome in metastatic melanoma.
CRIS-Team Scopus Importer:2020-05-19
Keywords: immunology; oncology; radiotherapy

Impact of radiotherapy and sequencing of systemic therapy on survival outcomes in melanoma patients with previously untreated brain metastasis: a multicenter DeCOG study on 450 patients from the prospective skin cancer registry ADOREG - Franklin, C.; Mohr, P.; Bluhm, L.; Grimmelmann, I.; Gutzmer, R.; Meier, F.; Garzarolli, M.; Weichenthal, M.; Herbst, R.; Pfohler, C.; Terheyden, P.; Utikal, J. S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Improved survival of advanced melanoma patients receiving immunotherapy with concomitant antithrombotic therapy - A multicenter study on 2419 patients from the prospective skin cancer registry ADOReg. - Kött, Julian; Zell, Tim; Zimmermann, Noah; Rünger, Alessandra; Smit, Daniel J.; Abeck, Finn; Geidel, Glenn; Hansen-Abeck, Inga; Heidrich, Isabel; Weichenthal, Michael; Ugurel, Selma; Leiter, Ulrike; et al. (European Journal of Cancer, 2025)
BACKGROUND: Cancer immunotherapy has revolutionized melanoma treatment, but the high number of non-responders still emphasizes the need for improvement of therapy. One potential avenue for enhancing anti-tumor treatment is through the modulation of coagulation and platelet activity. Both have been found to play an important role in the tumor microenvironment, tumor growth and metastasis. Preclinical studies indicate a beneficial effect, clinical data has been inconsistent. METHODS: We examined a cohort of advanced, non-resectable melanoma patients (n = 2419) derived from the German prospective multicenter skin cancer registry ADOReg, who were treated with immune checkpoint inhibitors (ICI). The patients were classified based on whether it was documented that they received platelet aggregation inhibition (PAI) (n = 137) (acetylsalicylic acid (ASA) or clopidogrel), anticoagulation (AC) (n = 185) (direct oral anticoagulation (DOAC), phenprocoumon, heparins) at the start of ICI or no antithrombotic medication (n = 2097) at any point during ICI treatment. The study endpoints were best overall response (BOR), progression-free survival (PFS) and overall survival (OS). RESULTS: A significantly improved PFS was observed in patients documented to receive ASA (15.1 vs 6.4 months, HR 0.67, 95 % CI: 0.5 to 0.88, p = 0.0047) as well as in patients to receive AC (15.1 vs. 6.4 months, HR 0.7, 95 % CI: 0.53 to 0.91, p = 0.01) compared to patients for whom no antithrombotic medication was documented. Multivariate analysis of OS showed significant risk reduction in patients who received DOAC (HR 0.68, 95 % CI: 0.49 to 0.92, p = 0.0170) or phenprocoumon (HR: 0.44, 95 % CI: 0.19 to 0.85, p = 0.0301). CONCLUSION: Our study indicates a positive prognostic effect of anticoagulant and antiplatelet concomitant medication in melanoma patients receiving ICI. Further studies are needed to confrim the cancer-related benefit of adding anticoagulation or platelet inhibition to ICI treatment.
EVALuna2:576539

Increased skin and mucosal toxicity in the combination of vemurafenib with radiation therapy - Merten, Ricarda; Hecht, Markus; Haderlein, Marlen; Distel, Luitpold; Fietkau, Rainer; Heinzerling, Lucie; Semrau, Sabine (Strahlentherapie und Onkologie, 2014)
Palliative radiotherapy is often required for patients with metastatic malignant melanoma in the case of bone or brain metastases. Since BRAF inhibitor therapy is highly efficient in V600-mutated melanomas, there is hesitation to stop it during radiotherapy. Consequently, radiotherapy under simultaneous vemurafenib treatment is frequently needed.We report the case of a patient receiving palliative radiotherapy of spinal bone metastases before and during vemurafenib therapy. The skin reactions were quantitatively scored using computer-assisted digital image evaluation.Radiotherapy without vemurafenib was tolerated very well, whereas radiotherapy under simultaneous vemurafenib treatment resulted in accentuated skin reactions. Furthermore, the patient developed dysphagia and had to be hospitalized for parenteral nutrition. In the quantitative analysis, there was a twofold increase in pigmentation and erythema of the irradiated skin area of the thoracic spine when vemurafenib was combined with radiotherapy compared with radiotherapy treatment alone. This is the first reported case of a patient showing no complications during radiotherapy without vemurafenib but remarkable skin and mucosal toxicity under concurrent vemurafenib therapy. Thus, a genetically conditioned individually elevated radiosensitivity can definitely be excluded. Compared with other reported cases, radiosensitization was not limited to the skin, but also affected the esophageal mucosa.Vemurafenib is a strong radiosensitizer. Patients receiving radiotherapy under simultaneous vemurafenib treatment should be monitored very closely.
EVALuna2:18209

Inflammatory markers in autoimmunity induced by checkpoint inhibitors - Husain, Beate; Kirchberger, Michael; Erdmann, Michael; Schüpferling, Sabine; Abolhassani, Amir Reza; Fröhlich, Waltraud; Berking, Carola; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose: Immune checkpoint inhibitors (ICI) are highly effective in several cancer entities, but also invoke a variety of immune-related adverse events (irAE). These are mostly reversible, but can be life-threatening or even fatal. Currently, the pathogenesis is not fully understood, but crucial for effective treatment. Prediction and early detection of irAE could be facilitated and treatment optimized if relevant biomarkers and effector mechanisms were better characterized. Methods: This study included a total of 45 irAE in patients with metastatic melanoma who were treated with ICI. All patients underwent a complete work-up with exclusion of other causes. Longitudinal blood samples were analyzed for a panel of soluble markers and compared to baseline and to patients who did not experience any irAE. Measurements included LDH, interleukin (IL)-6, IL-1β, IL-17, C-reactive protein (CRP) and tumor necrosis factor (TNF)-alpha as well as tumor markers S100 and melanoma inhibitory activity (MIA). Results: During the early onset of irAE increases in serum IL-6 (from mean 24.4 pg/ml at baseline to 51.0 pg/ml; p = 0.003) and CRP (from mean 7.0 mg/l at baseline to 17.7 mg/l; p = 0.001) and a decrease in MIA (from mean 5.4 pg/ml at baseline to 4.8 pg/ml; p = 0.035) were detected. No changes in IL-17 were noted. These effects were observed for irAE of different organ systems. Conclusion: Increases of a combination of IL-6 and CRP serum levels can be used for the early detection of irAE and tailored management. Interestingly, changes in MIA serum levels also correlate with irAE onset.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Cytokines; Immune checkpoint inhibitors; Immune-related adverse events; Melanoma

Influence of previous Radiotherapy on the Success of an immune-oncologic Therapy in metastatic Melanoma - a retrospective multicenter Study of ADO - Knispel, S.; Zimmer, L.; Gutzmer, R.; Heinzerling, Lucie; Weishaupt, C.; Pfoehler, C.; Gesierich, A.; Herbst, R.; Kaehler, K.; Weide, B.; Schlaak, M.; Loquai, C.; et al. (2018)
EVALuna2:34774

Influenza vaccination and myocarditis among patients receiving immune checkpoint inhibitors - Awadalla, Magid; Golden, Doll Lauren Alexandra; Mahmood, Syed S.; Alvi, Raza M.; Mercaldo, Nathaniel D.; Hassan, Malek Z. O.; Banerji, Dahlia; Rokicki, Adam; Mulligan, Connor; Murphy, Sean P. T.; Jones-O'Connor, Maeve; Cohen, Justine V.; et al. (Journal for ImmunoTherapy of Cancer, 2019)
BackgroundInfluenza vaccination (FV) is recommended for patients with cancer. Recent data suggested that the administration of the FV was associated with an increase in immune-related adverse events (irAEs) among patients on immune checkpoint inhibitors (ICIs). Myocarditis is an uncommon but serious complication of ICIs and may also result from infection with influenza. There are no data testing the relationship between FV and the development of myocarditis on ICIs.MethodsPatients on ICIs who developed myocarditis (n=101) (cases) were compared to ICI-treated patients (n=201) without myocarditis (controls). A patient was defined as having the FV if they were administered the FV from 6months prior to start of ICI to anytime during ICI therapy. Alternate thresholds for FV status were also tested. The primary comparison of interest was the rate of FV between cases and controls. Patients with myocarditis were followed for major adverse cardiac events (MACE), defined as the composite of cardiogenic shock, cardiac arrest, hemodynamically significant complete heart block and cardiovascular death.ResultsThe FV was administered to 25% of the myocarditis cases compared to 40% of the non-myocarditis ICI-treated controls (p=0.01). Similar findings of lower rates of FV administration were noted among myocarditis cases when alternate thresholds were tested. Among the myocarditis cases, those who were vaccinated had 3-fold lower troponin levels when compared to unvaccinated cases (FV vs. No FV: 0.12 [0.02, 0.47] vs. 0.40 [0.11, 1.26] ng/ml, p=0.02). Within myocarditis cases, those administered the FV also had a lower rate of other irAEs when compared to unvaccinated cases (36 vs. 55% p=0.10) including lower rates of pneumonitis (12 vs. 36%, p=0.03). During follow-up (175 [IQR 89, 363] days), 47% of myocarditis cases experienced a MACE. Myocarditis cases who received the FV were at a lower risk of cumulative MACE when compared to unvaccinated cases (24 vs. 59%, p=0.002).ConclusionThe rate of FV among ICI-related myocarditis cases was lower than controls on ICIs who did not develop myocarditis. In those who developed myocarditis related to an ICI, there was less myocardial injury and a lower risk of MACE among those who were administered the FV.
CRIS-Team WoS Importer:2019-03-06

Interdependence of coagulation with immunotherapy and BRAF/MEK inhibitor therapy: results from a prospective study - Beckmann, Malte; Schlüter, Julian; Erdmann, Michael; Kramer, Rafaela; Cunningham, Sarah; Hackstein, Holger; Zimmermann, Robert; Heinzerling, Lucie (Cancer Immunology, Immunotherapy, 2024)
Immune checkpoint inhibitor (ICI) therapies effectively treat a broadening spectrum of cancer entities but induce various immune-related side effects (irAEs). Recent reports suggest a correlation between ICI-induced systemic inflammation and thromboembolic events as well as an increased effectiveness by coadministration of anticoagulants. With cancer patients having a higher risk of thrombotic events per se, it is crucial to dissect and characterize the mechanisms that cause pro-coagulative effects induced by systemic tumor therapies and their potential interplay with anti-tumor response. A total of 31 patients with advanced skin cancer treated with either ICIs (n = 24) or BRAF/MEK inhibitors (n = 7) were longitudinally assessed for blood and coagulation parameters before as well as 7, 20 and 40 days after initiation of systemic tumor therapy. Changes were analyzed and compared between both groups. In addition, the influence of coagulation parameters on progression-free, recurrence-free and overall survival was investigated. The ICI cohort presented significantly increased factor VIII activity after one week of therapy (p 0.0225); while, protein S activity was reduced during the whole observation period. Additionally, von Willebrand factor activity and tissue factor concentrations increased under immunotherapy. Similar changes occurred under BRAF/MEK inhibitor therapy (BRAF/MEKi). Increased baseline levels of von Willebrand factor antigen and factor VIII:C before the start of ICI therapy correlated with a significantly higher risk of recurrence for patients receiving adjuvant immunotherapy. The findings suggest the induction of a pro-coagulant state under ICI and BRAF/MEKi and a role of coagulation parameters in the efficacy of ICI therapie
Keywords: Immune checkpoint inhibitors; BRAF/MEK inhibitors; Melanoma; Coagulation–fibrinolysis disorders; ICI-associated thrombosis; Predictive marker

Interest in tanning beds and sunscreen in German-speaking countries - Kirchberger, Michael C.; Kirchberger, Laura F.; Eigentler, Thomas K.; Reinhard, Raphael; Berking, Carola; Schuler, Gerold; Heinzerling, Lucie; Heppt, Markus V. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
BACKGROUND: The growing incidence of nearly all types of skin cancer can be attributed to increased exposure to natural or artificial ultraviolet (UV) radiation. However, there is a scarcity of statistical data on risk behavior or sunscreen use, which would be important for any prevention efforts. METHODS: Using the search engine Google® , we analyzed search patterns for the terms Solarium (tanning bed), Sonnencreme (sunscreen), and Sonnenschutz (sun protection) in Germany, Austria, and Switzerland between 2004 and 2016, and compared it to search patterns worldwide. For this purpose, "normalized search volumes" (NSVs) were calculated for the various search queries. The corresponding polynomial functions were then compared with each other over the course of time. RESULTS: Since 2001, there has been a marked worldwide decrease in the search queries for tanning bed, whereas those for sunscreen have steadily increased. In German-speaking countries, on the other hand, there have - for years - consistently been more search queries for tanning bed than for sunscreen. There is an annual periodicity of the queries, with the highest NSVs for tanning bed between March and May and those for sunscreen in the summer months around June. In Germany, the city-states of Hamburg and Berlin have particularly high NSVs for tanning bed. CONCLUSIONS: Compared to the rest of the world, German-speaking countries show a strikingly unfavorable search pattern. There is still great need for education and prevention with respect to sunscreen use and avoidance of artificial UV exposure.
EVALuna2:34311

Interleukin-2 and Checkpoint Inhibition as a successful Therapy Sequence for metastatic Melanoma: Case Report and retrospective Analysis in 52 Patients - Cosgarea; Zimmer, L.; Weide, B.; Gutzmer, R.; Heinzerling, Lucie; Weishaupt, C.; Pfoehler, C.; Gesierich, A.; Herbst, R.; Kaehler, K.; Schlaak, M.; Loquai, C.; et al. (2017)
EVALuna2:34331

Intratumorally administered CV8102 in patients with advanced solid tumors: Preliminary results from completed dose escalation in study 008 - Eigentler, T.; Heinzerling, Lucie; Krauss, J.; Weishaupt, C.; Ochsenreither, S.; Lebbe, C.; Mohr, P.; Oliva, M.; Oberoi, H. K.; Terheyden, P.; Perez, J. M. Trigo; Robert, C.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Intratumoral RNA-based TLR-7/-8 and RIG-I agonist CV8102 alone and in combination with anti-PD-1 in a Phase I dose-escalation and expansion trial in patients with advanced solid tumors - Eigentler, Thomas; Krauss, Juergen; Schreiber, Jutta; Weishaupt, Carsten; Terheyden, Patrick; Heinzerling, Lucie; Mohr, Peter; Weide, Benjamin; Gutzmer, Ralf; Becker, Juergen C.; Kiecker, Felix; Daehling, Angelika; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-15

Ipilimumab alone or in combination with nivolumab after progression on anti-PD-1 therapy in advanced melanoma - Zimmer, Lisa; Apuri, Susmitha; Eroglu, Zeynep; Kottschade, Lisa A.; Forschner, Andrea; Gutzmer, Ralf; Schlaak, Max; Heinzerling, Lucie; Krackhardt, Angela M.; Loquai, Carmen; Markovic, Svetomir N.; Joseph, Richard W.; et al. (European Journal of Cancer, 2017)
BACKGROUND: The anti-programmed cell death-1 (PD-1) inhibitors pembrolizumab and nivolumab alone or in combination with ipilimumab have shown improved objective response rates and progression-free survival compared to ipilimumab only in advanced melanoma patients. Anti-PD-1 therapy demonstrated nearly equal clinical efficacy in patients who had progressed after ipilimumab or were treatment-naïve. However, only limited evidence exists regarding the efficacy of ipilimumab alone or in combination with nivolumab after treatment failure to anti-PD-therapy. PATIENTS AND METHODS: A multicenter retrospective study in advanced melanoma patients who were treated with nivolumab (1 or 3 mg/kg) and ipilimumab (1 mg or 3 mg/kg) or ipilimumab (3 mg/kg) alone after treatment failure to anti-PD-1 therapy was performed. Patient, tumour, pre- and post-treatment characteristics were analysed. RESULTS: In total, 47 patients were treated with ipilimumab (ipi-group) and 37 patients with ipilimumab and nivolumab (combination-group) after treatment failure to anti-PD-1 therapy. Overall response rates for the ipi- and the combination-group were 16% and 21%, respectively. Disease control rate was 42% for the ipi-group and 33% for the combination-group. One-year overall survival rates for the ipi- and the combination-group were 54% and 55%, respectively. CONCLUSIONS: Ipilimumab should be considered as a viable treatment option for patients with failure to prior anti-PD-1 therapy, including those with progressive disease as best response to prior anti-PD-1. In contrast, the combination of ipilimumab and nivolumab appears significantly less effective in this setting compared to treatment-naïve patients.
EVALuna2:34335

Ipilimumab in metastatic melanoma patients with pre-existing autoimmune disorders - Kaehler, Katharina C.; Eigentler, Thomas K.; Gesierich, Anja; Heinzerling, Lucie; Loquai, Carmen; Meier, Friedegund; Meiss, Frank; Pfoehler, Claudia; Schlaak, Max; Terheyden, Patrick; Thoms, Kai M.; Ziemer, Mirjana; et al. (Cancer Immunology, Immunotherapy, 2018)
BACKGROUND: Ipilimumab and programmed death (PD) 1-antibodies are effective treatment options in metastatic melanoma. The safety and efficacy of ipilimumab in patients with pre-existing autoimmune disorders (AD) has only been evaluated in a selected number of patients. METHODS: We performed a retrospective analysis in 14 German skin cancer centers for patients with metastatic melanoma and pre-existing AD treated with ipilimumab. RESULTS: 41 patients with 44 pre-existing AD were treated with ipilimumab (thyroiditis n = 15, rheumatoid n = 11, dermatologic n = 10, Crohn's disease/ulcerative colitis n = 3, neurological n = 2, sarcoidosis n = 2, pancreatitis n = 1). 3 out of 41 patients had two AD, 11 patients required immunosuppressants at the time of induction of ipilimumab. 12 patients (29.2%) experienced a flare of their pre-existing AD, mainly patients with rheumatoid or dermatologic diseases. Additional immune-related adverse events (irAEs) occurred in 12 patients (29.2%). In 23 patients (56%) neither a change of their AD nor additional irAEs were observed. Objective responses were seen in five patients (one complete remission, four partial remissions, 12.1%). CONCLUSION: This is the largest series of patients with pre-existing AD and treatment with ipilimumab reported. Flares of pre-existing AD were observed but manageable. Response rates and occurrence of new irAEs were comparable to previous trials. Thus, in this patient subgroup, ipilimumab can be a treatment option after a thorough discussion of pros and cons and taking severity and activity of the preexisting AD into account.
EVALuna2:34383

Life-threatening Autoimmune Cardiomyopathy Reproducibly Induced in a Patient by Checkpoint Inhibitor Therapy - Tajmir-Riahi, Azadeh; Bergmann, Tanja; Schmid, Michael; Agaimy, Abbas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2018)
Checkpoint inhibitors induce a plethora of immune-related adverse events (irAEs) including autoimmune colitis, hepatitis, endocrinopathies, and rarer side effects like neuritis. Here, a case of autoimmune cardiomyopathy (grade 3 CTCAE) and myocarditis under combination therapy with nivolumab plus ipilimumab in a 72-year-old melanoma patient is reported. Treatment induced a partial response for 14 months. However, after 10 infusions the patient developed dyspnea, edema of the legs, ascites and a weight gain of 10 kg because of a decompensated heart insufficiency with a reduced ejection fraction from formerly 48%-50% to 15%. Ischemia and viral infections were ruled out. Histopathology showed hypertrophic myocarditis with interstitial lymphocytes. Prednisolone improved the patient's condition within 3 days, leading to a 25% and 30% ejection fraction after 2 and 8 weeks, respectively, and clinical symptoms subsided completely. Importantly, reinduction of anti-PD1 therapy resulted in a flare of myocarditis. Awareness for potentially life-threatening irAE of checkpoint inhibitors like autoimmune cardiomyopathy and myocarditis is crucial to rapidly initiate adequate treatment.
EVALuna2:34413

Limited Effect of Anti-PD-1 in advanced Skin Tumors of Patients with hemato-oncological Primary Disease: A retrospective multi-center Study of ADO - Leiter-Stoeppke, U.; Loquai, C.; Meier, F.; Rafei-Shamsabadi, D.; Hassel, J.; Glutsch, V.; Sirokay, J.; Schlecht, N.; Ruebben, A.; Gutzmer, R.; Kaehler, K.; Gambichler, T.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Lipase elevation and type 1 diabetes mellitus related to immune checkpoint inhibitor therapy – A multicentre study of 90 patients from the German Dermatooncology Group - Grimmelmann, Imke; Momma, Michael; Zimmer, Lisa; Hassel, Jessica C.; Heinzerling, Lucie; Pföhler, Claudia; Loquai, Carmen; Ruini, Cristel; Utikal, Jochen; Thoms, Kai Martin; Kähler, Katharina C.; Eigentler, Thomas; et al. (European Journal of Cancer, 2021)
Aim: Immune checkpoint inhibition (ICI) triggers immune-related adverse events (irAEs). The relevance of lipase elevation remains unclear. Patients and methods: Skin cancer patients with newly detected serum lipase elevation (at least twofold upper normal limit) or newly diagnosed type I diabetes mellitus upon ICI therapy were retrospectively collected at 14 German skin cancer centres. Results: We identified 68 patients with lipase elevation occurring after a median time of 19 (range 1–181) weeks on ICI, 15 (22%) thereof had symptoms consistent with pancreatitis. Forty-seven patients (73%) had other irAE, mainly colitis. Discontinuation (n = 24, 35%) or interruption (n = 26, 38%) of ICI resulted in decrease of lipase after reinduction of ICI lipase levels increased again in 12 of 24 patients. In 18 patients (27%), ICI was continued unchanged, and in 12 (67%) of them, lipase levels normalised. Twenty-two patients were identified with newly diagnosed type I diabetes mellitus related to ICI, and 12 (55%) thereof had also lipase elevation mainly shortly before or after the diagnosis of diabetes. Fourteen (64%) patients had other irAE, mainly thyroiditis. Irrespective of lipase elevation, patients frequently showed a rapid onset with ketoacidosis, decreased c-peptide, and strongly increased blood glucose levels. Conclusion: Increased serum lipase during ICI is often not associated with pancreatitis but with other irAE as possible cause. Therefore, it might be sufficient to regularly monitor blood glucose levels and perform further workup only in case of signs or symptoms of pancreatitis and/or exocrine pancreas insufficiency.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Diabetes; Diabetes mellitus; Immune checkpoint inhibitors; Immune-related adverse events; Ipilimumab; Lipase; Nivolumab; Pancreatitis; PD-1 inhibitor; Pembrolizumab

Lipase Elevations and Diabetes under Checkpoint Inhibition - Experience in 80 Patients - Weihkopf, D.; Satzger, I.; Zimmer, L.; Eigentler, T.; Haessel, J.; Heinzerling, Lucie; Herbst, R.; Kahler, K.; Loquai, C.; Meier, F.; Pfoehler, C.; Ruini, C.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Major Adverse Cardiovascular Events and the Timing and Dose of Corticosteroids in Immune Checkpoint Inhibitor-Associated Myocarditis - Zhang, Lili; Zlotoff, Daniel A.; Awadalla, Magid; Mahmood, Syed S.; Nohria, Anju; Hassan, Malek Z.O.; Thuny, Franck; Zubiri, Leyre; Chen, Carol L.; Sullivan, Ryan J.; Alvi, Raza M.; Rokicki, Adam; et al. (Circulation, 2020)
CRIS-Team Scopus Importer:2020-06-26
Keywords: corticosteroid; immunotherapy; myocarditis

Management of side effects of immune checkpoint blockade by anti-CTLA-4 and anti-PD-1 antibodies in metastatic melanoma - Kaehler, Katharina C.; Hassel, Jessica C.; Heinzerling, Lucie; Loquai, Carmen; Moessner, Rotraut; Ugurel, Selma; Zimmer, Lisa; Gutzmer, Ralf (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
CTLA-4 and PD-1 are potential targets for tumor-induced downregulation of lymphocytic immune responses. Immune checkpoint-modifying monoclonal antibodies oppose these effects, inducing T cell-mediated immune responses to various tumors including melanoma. Both anti-CTLA-4 and anti-PD-1 antibodies modify the interaction between tumor, antigen-presenting cells, and T lymphocytes. With respect to overall survival, clinical studies have shown a major benefit for the anti-CTLA-4 antibody ipilimumab as well as the two anti-PD-1 antibodies nivolumab and pembrolizumab. Following approval of ipilimumab in 2011, the latter two achieved market authorization in the summer of 2015. Immune responses thus induced and enhanced inevitably entail autoimmune phenomena, affecting various organs to varying degrees. Knowledge of these side effects is crucial with regard to prevention and management by treating physicians. Typically occurring early on and presenting with pronounced and persistent diarrhea, colitis represents a major and severe side effect. Other immune-mediated disorders include dermatitis, hypophysitis, thyroiditis, hepatitis, iridocyclitis as well as other less common autoimmune phenomena. Early recognition and initiation of treatment can reduce risks and sequelae for patients. This review describes the mechanisms of action of immune checkpoint blockade as well as its clinical effects in metastatic melanoma, with a detailed focus on the spectrum of adverse events and their therapeutic management.
EVALuna2:19628

Managing toxicities of immunotherapies - a side effect register for rare and severe side effects of checkpoint Inhibitor therapy - Heinzerling, Lucie; Schuler, Gerold (2018)
EVALuna2:34408

MAPK blockade, toxicities, pathogenesis and management - Moreira, Alvaro; Lebbe, Celeste; Heinzerling, Lucie (Current Opinion in Oncology, 2021)
Purpose of review BRAF/MEK inhibitor has changed the treatment landscape in patients with advanced and metastatic melanoma with prolonged overall survival and progression-free survival. Since three treatment combinations exist with similar efficacy therapy decisions are often made based on the side effect profile. Additionally, on-target side effects or class effects have to be properly managed to ensure treatment adherence. Recent findings Sequential treatment with BRAF/MEK inhibition and immunotherapy might increase toxicity with a sepsis-like syndrome and triple therapy with concomitant BRAF/MEK inhibition and anti-PD1/PD-L1 antibody therapy induces severe side effects in the vast majority of patients. Toxicity of combination therapy with BRAF/MEK inhibitors is generally manageable, reversible and infrequently associated with treatment discontinuation. In case of persisting off-target effects the change to another combination therapy can resolve side effects.
CRIS-Team WoS Importer:2021-02-26

MEK inhibition may increase survival of NRAS-mutated melanoma patients treated with checkpoint blockade: Results of a retrospective multicentre analysis of 364 patients - Kirchberger, Michael Constantin; Ugurel, Selma; Mangana, Johanna; Heppt, Markus Valentin; Eigentler, Thomas Kurt; Berking, Carola; Schadendorf, Dirk; Schuler, Gerold; Dummer, Reinhard; Heinzerling, Lucie (European Journal of Cancer, 2018)
BACKGROUND: Melanoma harbours genetic alterations in genes such as BRAF, NRAS and KIT. Activating NRAS mutations are present in about 20% of melanomas. Even though BRAF mutations can be effectively targeted with specific inhibitors, this approach has proven more challenging in cases of NRAS mutations. Previous reports suggested that immunotherapy might be more successful in NRAS-mutated compared to BRAF-mutated or BRAF/NRAS wildtype melanoma. PATIENTS AND METHODS: In this study, overall survival and response to anti-PD-1 (nivolumab, pembrolizumab) and anti-CTLA-4 (ipilimumab) therapy of 364 patients with metastatic melanoma were assessed comparing 236 NRAS-mutated patients with 128 NRAS wildtype patients. Subtyping of NRAS mutation in 211 cases revealed 12 different genotypes of which Q61 mutations were predominant (95%). RESULTS: Patients with NRAS mutant melanoma showed similar response rates to checkpoint inhibitor therapy compared to NRAS wildtype patients with 15% versus 13% for ipilimumab (P = 0.731), 21% versus 13% for anti-PD-1 monotherapy (P = 0.210) and 40% versus 39% for ipilimumab and anti-PD-1 therapy in combination or sequence (P = 0.859). Nevertheless, median overall survival of patients with NRAS mutant melanoma was significantly lower with 21 months compared to 33 months in NRAS wildtype melanoma patients (P = 0.034). Therapy with oral MEK inhibitors before or after checkpoint inhibitor therapy showed a trend toward a survival benefit in patients with NRAS mutant melanoma. CONCLUSIONS: Immune checkpoint inhibition shows comparable response rates in NRAS-mutated and NRAS wildtype melanoma even though survival is less favourable in case of NRAS mutation. Additional MEK inhibition might improve clinical benefit.
EVALuna2:34376

Melanoma 2.0. Skin cancer as a paradigm for emerging diagnostic technologies, computational modelling and artificial intelligence - Vera, Julio; Lai, Xin; Baur, Andreas; Erdmann, Michael; Gupta, Shailendra; Gutta, Cristiano; Heinzerling, Lucie; Heppt, Markus; Kazmierczak, Philipp Maximilian; Kunz, Manfred; Lischer, Christopher; Putzer, Brigitte M.; et al. (Briefings in Bioinformatics, 2022)
We live in an unprecedented time in oncology. We have accumulated samples and cases in cohorts larger and more complex than ever before. New technologies are available for quantifying solid or liquid samples at the molecular level. At the same time, we are now equipped with the computational power necessary to handle this enormous amount of quantitative data. Computational models are widely used helping us to substantiate and interpret data. Under the label of systems and precision medicine, we are putting all these developments together to improve and personalize the therapy of cancer. In this review, we use melanoma as a paradigm to present the successful application of these technologies but also to discuss possible future developments in patient care linked to them. Melanoma is a paradigmatic case for disruptive improvements in therapies, with a considerable number of metastatic melanoma patients benefiting from novel therapies. Nevertheless, a large proportion of patients does not respond to therapy or suffers from adverse events. Melanoma is an ideal case study to deploy advanced technologies not only due to the medical need but also to some intrinsic features of melanoma as a disease and the skin as an organ. From the perspective of data acquisition, the skin is the ideal organ due to its accessibility and suitability for many kinds of advanced imaging techniques. We put special emphasis on the necessity of computational strategies to integrate multiple sources of quantitative data describing the tumour at different scales and levels.
CRIS-Team WoS Importer:2022-11-04

Merkel Cell Carcinoma of the Head and Neck Compared to Other Anatomical Sites in a Real-World Setting: Importance of Surgical Therapy for Facial Tumors - Kirchberger, Michael; Heppt, Markus V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie (Facial Plastic Surgery, 2019)
Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin tumor with a high propensity for nodal involvement, local recurrence, and distant metastases. Up to 50% of MCC arises on head and neck (HN), which may impede oncological treatment due to insufficiently wide excisions and a lower rate of sentinel lymph node detection due to more complicated lymph drainage. Several studies have compared the clinical outcome of HN-MCC with those of non-head and neck (NHN) MCC yielding inconsistent results. This single-center, retrospective analysis compared the clinical outcome of 26 HN-MCC patients with 30 NHN-MCC patients. Overall survival (OS) and disease-free survival (DFS) were calculated with the Kaplan-Meier method assuming proportional hazards. The mean resection margins were 1.6 and 2.0 cm for the HN and NHN cohort, respectively. Local relapses were more frequently observed in patients with HN-MCC (19 vs. 10%). Patients with HN-MCC had a median OS of 4.3 years compared with 7.5 years in patients with NHN-MCC (p = 0.277). The median OS by tumor stage was 11, 3, 2, and 3 years in stage I, II, III, and IV disease, respectively (p = 0.009). The median DFS in HN-MCC was 10 years and not reached in the cohort with NHN-MCC patients (p = 0.939). Our data suggest a trend toward poorer outcomes of HN-MCC compared with NHN-MCC. Patients with MCC on the head and neck carry a higher risk for local relapse, requiring resolute surgical treatment also in facial localizations at early stages.
EVALuna2:212830

Monitoring skin metastases during immuno- and targeted therapy using total-body 3D photography - Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Berking, Carola; Schliep, S. (Journal of the European Academy of Dermatology and Venereology, 2020)
CRIS-Team Scopus Importer:2020-08-14

Mycophenolate Mofetil for the Treatment of Ipilimumab-induced Autoimmune Colitis in Patients with metastatic Melanoma - Naoum, C.; Majenka, P.; Loquai, C.; Kaehler, K.; Heinzerling, Lucie; Dudda, M.; Hassel, J. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Myocardial T1 and T2 Mapping by Magnetic Resonance in Patients With Immune Checkpoint Inhibitor–Associated Myocarditis - Thavendiranathan, Paaladinesh; Zhang, Lili; Zafar, Amna; Drobni, Zsofia D.; Mahmood, Syed S.; Cabral, Marcella; Awadalla, Magid; Nohria, Anju; Zlotoff, Daniel A.; Thuny, Franck; Heinzerling, Lucie; Barac, Ana; et al. (Journal of the American College of Cardiology, 2021)
Background: Myocarditis is a potentially fatal complication of immune checkpoint inhibitor (ICI) therapy. Data on the utility of cardiovascular magnetic resonance (CMR) T1 and T2 mapping in ICI myocarditis are limited. Objectives: This study sought to assess the value of CMR T1 and T2 mapping in patients with ICI myocarditis. Methods: In this retrospective study from an international registry of patients with ICI myocarditis, clinical and CMR findings (including T1 and T2 maps) were collected. Abnormal T1 and T2 were defined as 2 SD above site (vendor/field strength specific) reference values and a z-score was calculated for each patient. Major adverse cardiovascular events (MACE) were a composite of cardiovascular death, cardiogenic shock, cardiac arrest, and complete heart block. Results: Of 136 patients with ICI myocarditis with a CMR, 86 (63%) had T1 maps and 79 (58%) also had T2 maps. Among the 86 patients (66.3 ± 13.1 years of age), 36 (41.9%) had a left ventricular ejection fraction <55%. Across all patients, mean z-scores for T1 and T2 values were 2.9 ± 1.9 (p < 0.001) and 2.2 ± 2.1 (p < 0.001), respectively. On Siemens 1.5-T scanner (n = 67), native T1 (1,079.0 ± 55.5 ms vs. 1,000.3 ± 22.1 ms; p < 0.001) and T2 (56.2 ± 4.9 ms vs. 49.8 ± 2.2 ms; p < 0.001) values were elevated compared with reference values. Abnormal T1 and T2 values were seen in 78% and 43% of the patients, respectively. Applying the modified Lake Louise Criteria, 95% met the nonischemic myocardial injury criteria and 53% met the myocardial edema criteria. Native T1 values had excellent discriminatory value for subsequent MACE, with an area under the curve of 0.91 (95% confidence interval: 0.84 to 0.98). Native T1 values (for every 1-unit increase in z-score, hazard ratio: 1.44; 95% confidence interval: 1.12 to 1.84; p = 0.004) but not T2 values were independently associated with subsequent MACE. Conclusions: The use of T1 mapping and application of the modified Lake Louise Criteria provides important diagnostic value, and T1 mapping provides prognostic value in patients with ICI myocarditis.
CRIS-Team Scopus Importer:2021-03-26
Keywords: cardiovascular magnetic resonance; immune checkpoint inhibitor; Lake Louise Criteria; major adverse cardiovascular event; myocarditis; T1 mapping; T2 mapping

Myocarditis in Patients Treated With Immune Checkpoint Inhibitors - Mahmood, Syed S.; Fradley, Michael G.; Cohen, Justine V.; Nohria, Anju; Reynolds, Kerry L.; Heinzerling, Lucie; Sullivan, Ryan J.; Damrongwatanasuk, Rongras; Chen, Carol L.; Gupta, Dipti; Kirchberger, Michael C.; Awadalla, Magid; et al. (Journal of the American College of Cardiology, 2018)
BACKGROUND: Myocarditis is an uncommon, but potentially fatal, toxicity of immune checkpoint inhibitors (ICI). Myocarditis after ICI has not been well characterized. OBJECTIVES: The authors sought to understand the presentation and clinical course of ICI-associated myocarditis. METHODS: After observation of sporadic ICI-associated myocarditis cases, the authors created a multicenter registry with 8 sites. From November 2013 to July 2017, there were 35 patients with ICI-associated myocarditis, who were compared to a random sample of 105 ICI-treated patients without myocarditis. Covariates of interest were extracted from medical records including the occurrence of major adverse cardiac events (MACE), defined as the composite of cardiovascular death, cardiogenic shock, cardiac arrest, and hemodynamically significant complete heart block. RESULTS: The prevalence of myocarditis was 1.14% with a median time of onset of 34 days after starting ICI (interquartile range: 21 to 75 days). Cases were 65 ± 13 years of age, 29% were female, and 54% had no other immune-related side effects. Relative to controls, combination ICI (34% vs. 2%; p < 0.001) and diabetes (34% vs. 13%; p = 0.01) were more common in cases. Over 102 days (interquartile range: 62 to 214 days) of median follow-up, 16 (46%) developed MACE; 38% of MACE occurred with normal ejection fraction. There was a 4-fold increased risk of MACE with troponin T of ≥1.5 ng/ml (hazard ratio: 4.0; 95% confidence interval: 1.5 to 10.9; p = 0.003). Steroids were administered in 89%, and lower steroids doses were associated with higher residual troponin and higher MACE rates. CONCLUSIONS: Myocarditis after ICI therapy may be more common than appreciated, occurs early after starting treatment, has a malignant course, and responds to higher steroid doses.
EVALuna2:34388

Myocarditis in the Setting of Cancer Therapeutics Proposed Case Definitions for Emerging Clinical Syndromes in Cardio-Oncology - Bonaca, Marc P.; Olenchock, Benjamin A.; Salem, Joe-Elie; Wiviott, Stephen D.; Ederhy, Stephane; Cohen, Ariel; Stewart, Garrick C.; Choueiri, Toni K.; Di Carli, Marcelo; Allenbach, Yves; Kumbhani, Dharam J.; Heinzerling, Lucie; et al. (Circulation, 2019)
Recent developments in cancer therapeutics have improved outcomes but have also been associated with cardiovascular complications. Therapies harnessing the immune system have been associated with an immune-mediated myocardial injury described as myocarditis. Immune checkpoint inhibitors are one such therapy with an increasing number of case and cohort reports describing a clinical syndrome of immune checkpoint inhibitor-associated myocarditis. Although the full spectrum of immune checkpoint inhibitor-associated cardiovascular disease still needs to be fully defined, described cases of myocarditis range from syndromes with mild signs and symptoms to fatal events. These observations in the clinical setting stand in contrast to outcomes from randomized clinical trials in which myocarditis is a rare event that is investigator reported and lacking in a specific case definition. The complexities associated with diagnosis, as well as the heterogeneous clinical presentation of immune checkpoint inhibitor-associated myocarditis, have made ascertainment and identification of myocarditis with high specificity challenging in clinical trials and other data sets, limiting the ability to better understand the incidence, outcomes, and predictors of these rare events. Therefore, establishing a uniform definition of myocarditis for application in clinical trials of cancer immunotherapies will enable greater understanding of these events. We propose an operational definition of cancer therapy-associated myocarditis that may facilitate case ascertainment and report and therefore may enhance the understanding of the incidence, outcomes, and risk factors of this novel clinical syndrome.
CRIS-Team WoS Importer:2019-07-26

Myositis and neuromuscular side-effects induced by immune checkpoint inhibitors - Moreira, Alvaro; Loquai, Carmen; Pfoefer, Claudia; Kaehler, Katharina C.; Knauss, Samuel; Heppt, Markus V.; Gutzmer, Ralf; Dimitriou, Florentia; Meier, Friedegund; Mitzel-Rink, Heidrun; Schuler, Gerold; Terheyden, Patrick; et al. (European Journal of Cancer, 2019)
AIM: To characterise clinical presentation, laboratory and histopathologic characteristics and assess the treatment and outcome of neuromuscular side-effects of checkpoint therapy. METHODS: The side-effect registry and the institutional database from ten skin cancer centres were queried for reports on myositis and neuromuscular side-effects induced by checkpoint inhibitors. In total, 38 patients treated with ipilimumab, tremelimumab, nivolumab and pembrolizumab for metastatic skin cancer were evaluated and characterised. RESULTS: Myositis was the most frequent neuromuscular adverse event. In 32% of cases, myositis was complicated by concomitant myocarditis. Furthermore, cases of isolated myocarditis, myasthenia gravis, polymyalgia rheumatica, radiculoneuropathy and asymptomatic creatine kinase elevation were reported. The onset of side-effects ranged from the first week of treatment to 115 weeks after the start of therapy. Most of the cases were severe (49% grade III-IV Common Terminology Criteria for Adverse Events), and there were two fatalities (5%) due to myositis and myositis with concomitant myocarditis. Only half of the cases (50%) completely resolved, whereas the rest was either ongoing or had sequelae. Steroids were given in 80% of the resolved cases and in 40% of the unresolved cases. CONCLUSION: Immune-mediated neuromuscular side-effects of checkpoint inhibitors greatly vary in presentation and differ from their idiopathic counterparts. These side-effects can be life threatening and may result in permanent sequelae. Occurrence of these side-effects must be taken into consideration for patient information, especially when considering adjuvant immunotherapy with anti-programmed cell-death protein 1 (PD-1) antibodies and monitoring, which should include regular surveillance of creatine kinase.
EVALuna2:36556

NanoString technology distinguishes anti-TIF-1γ+ from anti-Mi-2+ dermatomyositis patients - Preusse, Corinna; Eede, Pascale; Heinzerling, Lucie; Freitag, Kiara; Koll, Randi; Froehlich, Waltraud; Schneider, Udo; Allenbach, Yves; Benveniste, Olivier; Schaenzer, Anne; Goebel, Hans-Hilmar; Stenzel, Werner; et al. (Brain Pathology, 2021)
Dermatomyositis (DM) is a systemic idiopathic inflammatory disease affecting skeletal muscle and skin, clinically characterized by symmetrical proximal muscle weakness and typical skin lesions. Recently, myositis-specific autoantibodies (MSA) became of utmost importance because they strongly correlate with distinct clinical manifestations and prognosis. Antibodies against transcription intermediary factor 1γ (TIF-1γ) are frequently associated with increased risk of malignancy, a specific cutaneous phenotype and limited response to therapy in adult DM patients. Anti-Mi-2 autoantibodies, in contrast, are typically associated with classic DM rashes, prominent skeletal muscle weakness, better therapeutic response and prognosis, and less frequently with cancer. Nevertheless, the sensitivity of autoantibody testing is only moderate, and alternative reliable methods for DM patient stratification and prediction of cancer risk are needed. To further investigate these clinically distinct DM subgroups, we herein analyzed 30 DM patients (n = 15 Mi-2+ and n = 15 TIF-1 γ+) and n = 8 non-disease controls (NDC). We demonstrate that the NanoString technology can be used as a very sensitive method to clearly differentiate these two clinically distinct DM subgroups. Using the nCounter PanCancer Immune Profiling Panel™, we identified a set of significantly dysregulated genes in anti-TIF-1γ+ patient muscle biopsies including VEGFA, DDX58, IFNB1, CCL5, IL12RB2, and CD84. Investigation of type I IFN-regulated transcripts revealed a striking type I interferon signature in anti-Mi-2+ patient biopsies. Our results help to stratify both subgroups and predict, which DM patients require an intensified diagnostic procedure and might have a poorer outcome. Potentially, this could also have implications for the therapeutic approach.
CRIS-Team Scopus Importer:2021-06-11
Keywords: dermatomyositis; Mi-2; myositis-specific antibody; NanoString; skeletal muscle; TIF-1γ

Nebenwirkungsmanagement bei Immun-Checkpoint-Blockade durch CTLA-4- und PD-1-Antikörper beim metastasierten Melanom – ein Update - Kähler, Katharina C.; Hassel, Jessica C.; Heinzerling, Lucie; Loquai, Carmen; Thoms, Kai Martin; Ugurel, Selma; Zimmer, Lisa; Gutzmer, Ralf (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-06-16

Neurological, respiratory, musculoskeletal, cardiac and ocular side-effects of anti-PD-1 therapy - Zimmer, Lisa; Goldinger, Simone M.; Hofmann, Lars; Loquai, Carmen; Ugurel, Selma; Thomas, Ioannis; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death 1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma and other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects can involve skin, gastrointestinal tract, liver, the endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centres were treated with pembrolizumab or nivolumab. Two hundred forty two side-effects in 138 patients have been analysed. In 77 of the 138 patients side-effects affected the nervous system, respiratory tract, musculoskeletal system, heart, blood and eyes. Not yet reported side-effects such as meningo-(radiculitis), polyradiculitis, cardiac arrhythmia, asystolia, and paresis have been observed. Rare and difficult to manage side-effects such as myasthenia gravis are described in detail.Anti-PD-1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19571

Neurological side effects of checkpoint inhibitors - Knauss, S.; Roque, L. Ginesta; Huehnchen, P.; Heinzerling, Lucie; Boehmerle, W.; Endres, M. (Der Nervenarzt, 2019)
Background. In recent years the treatment of many tumor entities has been revolutionized by the use of modern immunotherapies with checkpoint inhibitors; however, good response rates are contrasted by many immune-mediated side effects. Neurological immune-mediated side effects are rare but often severe complications of checkpoint inhibitor treatment.
CRIS-Team WoS Importer:2019-02-27

Neuromuscular Side Effects of Immune Checkpoint Inhibitors - Moreira, Alvaro; Loquai, C.; Knauss, S.; Gutzmer, R.; Dimitriou, F.; Meier, F.; Heppt, M.; Mitzel-Rink, H.; Schuler, Gerold; Terheyden, P.; Thoms, K. M.; Zimmer, L.; et al. (2018)
EVALuna2:34768

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

Outcome of melanoma patients with elevated LDH treated with first-line targeted therapy or PD-1-based immune checkpoint inhibition - Knispel, Sarah; Gassenmaier, Maximilian; Menzies, Alexander M.; Loquai, Carmen; Johnson, Douglas B.; Franklin, Cindy; Gutzmer, Ralf; Hassel, Jessica C.; Weishaupt, Carsten; Eigentler, Thomas; Schilling, Bastian; Schummer, Patrick; et al. (European Journal of Cancer, 2021)
Background: Elevated lactate dehydrogenase (LDH) is a known predictive and prognostic factor for a poor outcome in patients with metastatic melanoma. It is unclear whether first-line targeted therapy (TT) or immune checkpoint inhibition (ICI) is more beneficial in melanoma patients with elevated LDH because prospective studies in this area are lacking. Methods: This multicentre retrospective cohort study was conducted at 25 melanoma centres worldwide to analyse progression-free survival (PFS) and overall survival (OS) among melanoma patients with elevated LDH. The role of confounders was addressed by using inverse probability of treatment weighting. Results: Among 173 BRAFV600-mutant patients, PFS at 12 months in the TT group was 22% compared with 52% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.6, 95% CI 0.4–1.0, p = 0.07) and 18% in the anti-PD-1 monotherapy group (HR 1.8, 95% CI 1.2–2.8, p = 0.003). Twelve months' OS was 48% in the TT group compared with 83% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.5, 95% CI 0.3–1.0, p = 0.03) and 50% in the anti-PD-1 monotherapy group (HR 1.2, 95% CI 0.8–2.0, p = 0.37). The ORR in the TT group was 63%, compared with 55% and 20% in the combined anti-PD-1 and anti-CTLA-4 and anti-PD-1 monotherapy group, respectively. Among 314 patients receiving ICI first-line, PFS at 12 months was 33% in the anti-PD-1 group versus 38% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.8, 95% CI 0.6–1.0; p = 0.07). OS at 12 months was 54% in the anti-PD-1 group versus 66% in the combined ICI group (HR 0.7, 95% CI 0.5–1.0; p = 0.03). The ORR was 30% in the anti-PD-1 monotherapy group and 43% in the combined anti-PD-1 and anti-CTLA-4 group. Results from multivariate analysis confirmed the absence of qualitative confounding. Conclusions: Among BRAF-mutant patients with elevated LDH, combined anti-PD-1 and anti-CTLA-4 blockade seems to be associated with prolonged OS compared with first-line TT. Among patients receiving ICI as a first-line treatment, OS appears to be longer for the combination of anti-PD-1 and anti-CTLA-4 than for anti-PD-1 alone.
CRIS-Team Scopus Importer:2021-03-26
Keywords: CTLA-4; Immune checkpoint inhibition; LDH; Melanoma; PD-1; Progression; Response; Survival; Targeted therapy

Outcome on 560 metastatic melanoma (MM) patients treated with pembrolizumab during the German Expanded Access Program (EAP) - Hassel, J.; Forschner, A.; Bluhm, L.; Heinzerling, Lucie; Zimmer, L.; Utikal, J.; Kaehler, K.; Schlaak, M.; Loquai, C.; Gutzmer, R.; Kieker, F.; Berking, C.; et al. (2016)
EVALuna2:33940

Palbociclib Induces Senescence in Melanoma and Breast Cancer Cells and Leads to Additive Growth Arrest in Combination With Irradiation - Jost, Tina; Heinzerling, Lucie; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (Frontiers in Oncology, 2021)
Introduction: Several kinase inhibitors (KI) bear the potential to act as radiosensitizers. Little is known of the radiosensitizing effects of a wide range of other KI like palbociclib, which is approved in ER+/HER2- metastatic breast cancer. Method: In our study, we used healthy donor fibroblasts and breast cancer and skin cancer cells to investigate the influence of a concomitant KI + radiation therapy. Cell death and cell cycle distribution were studied by flow cytometry after Annexin-V/7-AAD and Hoechst staining. Cellular growth arrest was studied in colony-forming assays. Furthermore, we used C12-FDG staining (senescence) and mRNA expression analysis (qPCR) to clarify cellular mechanisms. Results: The CDK4/6 inhibitor palbociclib induced a cell cycle arrest in the G0/G1 phase. Cellular toxicity (cell death) was only slightly increased by palbociclib and not enhanced by additional radiotherapy. As the main outcome of the colony formation assays, we found that cellular growth arrest was induced by palbociclib and improved by radiotherapy in an additive manner. Noticeably, palbociclib treatment clearly induced senescence not only in breast cancer and partly in melanoma cells, but also in healthy fibroblasts. According to these findings, the downregulation of senescence-related FOXM1 might be an involved mechanism of the senescence-induction potential of palbociclib. Conclusion: The effect on cellular growth arrest of palbociclib and radiotherapy is additive. Palbociclib induces permanent G0/G1 cell cycle arrest by inducing senescence in fibroblasts, breast cancer, and melanoma cells. Direct cell death induction is only a minor secondary mechanism of action. Concomitant KI and radiotherapy is a strategy worth studying in clinical trials.
CRIS-Team Scopus Importer:2021-11-12
Keywords: breast cancer; kinase inhibitor; melanoma; palbociclib; radiotherapy; senescence

PARP inhibitors combined with ionizing radiation induce different effects in melanoma cells and healthy fibroblasts - Weigert, Verena; Jost, Tina; Hecht, Markus; Knippertz, Ilka; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (BMC Cancer, 2020)
BACKGROUND: PARP inhibitors niraparib and talazoparib are FDA approved for special cases of breast cancer. PARP is an interesting repair protein which is frequently affected in cancer cells. We studied the combined action of talazoparib or niraparib with ionizing radiation in melanoma cells and healthy fibroblasts. METHODS: Homologous recombination (HR) status in six different melanoma cell lines and healthy fibroblasts was assessed. Cell cultures were treated with PARP inhibitors talazoparib or niraparib and ionizing radiation (IR). Apoptosis, necrosis and cell cycle distribution was analyzed via flow cytometry. Cell migration was studied by scratch assays. RESULTS: Studied melanoma cell cultures are HR deficient. Studied healthy fibroblasts are HR proficient. Talazoparib and niraparib have congruent effects within the same cell cultures. In all cell cultures, combined treatment increases cell death and G2/M arrest compared to IR. Combined treatment in melanoma cells distinctly increases G2/M arrest. Healthy fibroblasts are less affected by G2/M arrest. Treatment predominantly decelerates or does not modify migration. In two cell cultures migration is enhanced under the inhibitors. CONCLUSIONS: Although the two PARP inhibitors talazoparib and niraparib appear to be suitable for a combination treatment with ionizing radiation in our in vitro studies, a combination treatment cannot generally be recommended. There are clear interindividual differences in the effect of the inhibitors on different melanoma cells. Therefore, the effect on the cancer cells should be studied prior to a combination therapy. Since melanoma cells increase more strongly than fibroblasts in G2/M arrest, the fractional application of combined treatment should be further investigated.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Cell cycle; Cell death; Homologous recombination; Ionizing radiation; Kinase inhibitor; PARP1/PARP2; Radiosensitivity

Pathogenetic Implications of BRAF Mutation Distribution in Stage IV Melanoma Patients - Baiter, Mirjam; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine; Heinzerling, Lucie (Dermatology, 2015)
BRAF mutation frequencies in melanoma subtypes have clinical implications and offer pathogenetic clues.To characterize BRAF mutation status in melanoma of unknown primary (MUP) patients, in histological melanoma subtypes and by localization of primary tumors.In 179 patients with stage IV metastatic melanoma, BRAF mutation status, histological subtype and localization of primary (except for 29 MUP patients) were analyzed.BRAF mutations were found in 44.3%, of which 80.5% were BRAF V600E and 19.5% showed non-V600E BRAF mutations. BRAF mutation frequency depended on histological subtype (57.4% superficial spreading melanoma, 54.7% nodular melanoma, 11.1% mucosal melanoma, 28.6% acral lentiginous melanoma) and concerning non-V600E BRAF mutations on localization of primary. In MUP the BRAF mutation pattern resembled superficial spreading and nodular melanomas.BRAF mutation frequencies depend on histological subtype and localization of primary melanoma. Non-V600E BRAF mutations mostly occur in patients with primaries on 'head and neck' as well as 'trunk' but not on 'extremities'.
EVALuna2:6729

Patient preferences of German and Swiss melanoma patients with regard to life-threatening side effects in the context of adjuvant immunotherapy - a qualitative GerMelaTox-A substudy - Peters, W.; Maul, L. V.; Huning, S.; Hassel, J. C.; Heinzerling, Lucie; Loquai, C.; Gutzmer, R.; Sachse, M. M.; Blome, C.; Kah-Ler, K. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Patterns of care and follow-up care of patients with uveal melanoma in German-speaking countries: a multinational survey of the German Dermatologic Cooperative Oncology Group (DeCOG) - Steeb, Theresa; Wessely, Anja; Alter, Mareike; Bayerl, Christiane; Bender, Armin; Bruning, Guido; Dabrowski, Evelyn; Debus, Dirk; Devereux, Nina; Dippel, Edgar; Drexler, Konstantin; Dücker, Pia; et al. (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: Uveal melanoma (UM) is an orphan cancer of high unmet medical need. Current patterns of care and surveillance remain unclear as they are situated in an interdisciplinary setting. Methods: A questionnaire addressing the patterns of care and surveillance in the management of patients with uveal melanoma was distributed to 70 skin cancer centers in Austria, Germany and Switzerland. Frequency distributions of responses for each item of the questionnaire were calculated. Results: 44 of 70 (62.9%) skin cancer centers completed the questionnaire. Thirty-nine hospitals were located in Germany (88.6%), three in Switzerland (6.8%) and two in Austria (4.5%). The majority (68.2%) represented university hospitals. Most patients with metastatic disease were treated in certified skin cancer centers (70.7%, 29/41). Besides, the majority of patients with UM were referred to the respective skin cancer center by ophthalmologists (87.2%, 34/39). Treatment and organization of follow-up of patients varied across the different centers. 35.1% (14/37) of the centers stated to not perform any screening measures. Conclusion: Treatment patterns of patients with uveal melanoma in Germany, Austria and Switzerland remain extremely heterogeneous. A guideline for the treatment and surveillance is urgently needed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Background; Cross-sectional study; Follow-up; Ocular melanoma; Patterns of care; Surveillance; Treatment patterns; Uveal melanoma

Persistent immune-related adverse events after cessation of checkpoint inhibitor therapy: Prevalence and impact on patients' health-related quality of life - Schulz, Thomas U.; Zierold, Sarah; Sachse, Michael M.; Pesch, Giulia; Tomsitz, Dirk; Schilbach, Katharina; Kähler, Katharina C.; French, Lars E.; Heinzerling, Lucie (European Journal of Cancer, 2022)
Background: Immune checkpoint inhibitors (ICIs) may induce persistent immune-related adverse events (irAEs). We investigated persistent irAEs and implications on patients' lives compared to non-ICI-induced autoimmune diseases (AIs). Methods: The multicentre, cross-sectional study comprised 200 patients with cancer ≥12 weeks after ICI cessation (ICI-patients) and 2705 patients with AIs (AI-patients), recruited in German outpatient clinics and support groups. The prevalence of persistent irAEs subdivided in long-term (12 weeks to <12 months) and chronic irAEs (≥12 months) since ICI discontinuation, health-related quality of life (HRQoL) using the EuroQol 5D-5L (EQ-Index/VAS score), and burden of autoimmune symptoms and respective therapies were assessed. Results: Long-term/chronic irAEs occurred in 51.9%/35.5% of outpatient ICI-patients, including arthralgia (16.7%/16.1%), myalgia (13.0%/14.0%), hypothyroidism (11.1%/10.8%), xerostomia (7.4%/8.6%), vitiligo (13.0%/7.5%) and hypophysitis (9.3%/7.5%). ICI-patients with long-term/chronic irAEs reported clinically significantly reduced HRQoL compared to ICI-patients without long-term/chronic irAEs (EQ-Index score: 0.767/0.752 versus 0.920/0.923, p < 0.001/0.001; EQ-VAS score: 52.2/52.0 versus 63.6/74.7, p =/< 0.040/0.001). Multiple linear regression analyses confirmed clinically significant reductions in HRQoL scores by chronic irAEs (EQ-Index/VAS score: −0.163/−23.4, p < 0.001/0.001). HRQoL, burden of autoimmune symptoms and burden of respective therapies in ICI-patients with chronic irAEs were similar to AI-patients with non-exacerbated AIs. Patients with chronic irAEs felt inadequately informed about side-effects compared to patients without chronic irAEs (p < 0.001). Conclusion: Persistent irAEs impose a significant burden on patients after ICI cessation. Especially in early tumour stages, risk-benefit ratios must be carefully evaluated, and patients need to be informed about potential long-term sequelae.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Autoimmunity; Cancer survivors; Chronic immune-related adverse events (chronic irAEs); Health-related quality of life (HRQoL); Immune checkpoint inhibitors (ICIs); Immunotherapy; Long-term sequelae; Melanoma; Persistent toxicities; Prevalence

Phase I dose-escalation and expansion study of intratumoral CV8102, a RNA-based TLR- nd RIG-1 agonist in patients with advanced solid tumors - Terheyden, P.; Weishaupt, C.; Heinzerling, Lucie; Klinkhardt, U.; Krauss, J.; Mohr, P.; Kiecker, F.; Becker, J. C.; Submitter, A. Daehling; Doener, F.; Heidenreich, R.; Scheel, B.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Pigmented lesions of the mucosa - Heppt, Markus; Heinzerling, Lucie (Die Dermatologie, 2022)
Background Pigmented lesions of the mucosa are a common reason to consult a dermatologist. They have heterogeneous etiologies and comprise a wide range of differential diagnoses. Both practitioners and patients are often uncertain about the malignancy of the lesions. Materials and methods Review and demonstration of the most common pigmentation disorders of the mucous membranes, including discussion of clinical findings and underlying causes. Results Pigmented mucosal lesions can be classified as either focal or multifocal-diffuse. Focal hyperpigmentation encompasses melanotic macules, nevi, deposition of exogenous materials or pigments, and oral melanoacanthoma. They are mostly benign but must be discerned from mucosal melanoma with an aggressive course and poor prognosis. Multifocal or diffuse hyperpigmentation may be drug-induced or indicative of an underlying medical condition. Importantly, as part of hereditary syndromes further diagnostic work-up is required. Conclusion Specific knowledge of the distribution and causes of pigmented mucosal lesions helps in clinical assessment between benign findings and those requiring further work-up and histologic clarification.
CRIS-Team WoS Importer:2022-09-09

Predicting the response of uveal melanoma to immunotherapy with MRI assessments - Moreira, Alvaro; Saake, Marc; Schuler, Gerold; Heinzerling, Lucie (CANCER IMMUNOLOGY RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Predicting the response to anti-PD1 therapy in metastatic melanoma - Heinzerling, Lucie; Kirchberger, Michael Constantin; Walter, Lisa; Schuler, Gerold (TRANSLATIONAL CANCER RESEARCH, 2016)

Predictive value of PD-L1 based on mRNA level in the treatment of stage IV melanoma with ipilimumab - Brueggemann, C.; Kirchberger, M. C.; Goldinger, S. M.; Weide, B.; Konrad, A.; Erdmann, M.; Schadendorf, D.; Croner, R. S.; Krahenbuhl, L.; Kaehler, K. C.; Hafner, C.; Leisgang, W.; et al. (Journal of Cancer Research and Clinical Oncology, 2017)
PD-L1 is established as a predictive marker for therapy of non-small cell lung cancer with pembrolizumab. Furthermore, PD-L1 positive melanoma has shown more favorable outcomes when treated with anti-PD1 antibodies and dacarbazine compared to PD-L1 negative melanoma. However, the role of PD-L1 expression with regard to response to checkpoint inhibition with anti-CTLA-4 is not clear, yet. In addition, the lack of standardization in the immunohistochemical assessment of PD-L1 makes the comparison of results difficult. In this study, we investigated the PD-L1 gene expression with a new fully automated technique via RT-PCR and correlated the findings with the response to the anti-CTLA-4 antibody ipilimumab.Within a retrospective multi-center trial, PD-L1 gene expression was evaluated in 78 melanoma patients in a total of 111 pre-treatment tumor samples from 6 skin cancer centers and analyzed with regard to response to ipilimumab. For meaningful statistical analysis, the cohort was enriched for responders with 30 responders and 48 non-responders. Gene expression was assessed by quantitative RT-PCR after extracting mRNA from formalin-fixed paraffin embedded tumor tissue and correlated with results from immunohistochemical (IHC) stainings.The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab. The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab.
EVALuna2:15289

Preferences of German melanoma patients for interferon (IFN) ?-2b toxicities (the DeCOG "GERMELATOX survey") versus melanoma recurrence to quantify patients' relative values for adjuvant therapy - Kaehler, Katharina C.; Blome, Christine; Forschner, Andrea; Gutzmer, Ralf; Haalck, Thomas; Heinzerling, Lucie; Kornek, Thomas; Livingstone, Elisabeth; Loquai, Carmen; Maul, Lara Valeska; Lang, Berenice M.; Schadendorf, Dirk; et al. (Medicine, 2016)
Currently interferon alfa-2b (IFN?-2b) is an approved adjuvant drug for high-risk melanoma patients that leads to an improvement in disease-free survival (DFS). However, it is unclear whether it also impacts overall survival. Widespread use of adjuvant high-dose IFN? has been tempered by its significant toxicity and its limited efficacy. Current therapeutic strategies like immune checkpoint blockade or targeted therapy may also be useful in the adjuvant setting. Therefore, it is important to weigh the trade-offs between possible side effects and therapeutic benefit.We assessed patient utilities for health states associated with IFN therapy. Utilities are measures of preference for a specific health state on a scale of 0 (death) to 1 (perfect health).Utilities were determined for health states associated with adjuvant IFN among 130 German low-risk melanoma patients using the standard gamble technique. Four IFN?-2b toxicity scenarios and the following 3 posttreatment outcomes were assessed: disease-free health and melanoma recurrence (with or without previous use of IFN?-2b) resulting in cancer death. Patients were asked to trade-off the improvement in 5-year DFS and the IFN-related side effects.Utilities for melanoma recurrence (mean 0.60) were significantly lower than for all IFN?-2b toxicity scenarios (mean 0.81-0.90). Patients were willing to tolerate mild-to-moderate and severe toxicity for a 50% and 75% chance of 5-year DFS, respectively. Both utilities and threshold benefits were mostly independent from patient characteristics like gender, income, and social situation. Significant impact was only observed by age and previous personal experience with cancer.On average, German patients were willing to trade even severe IFN?-2b toxicity for reducing the rate of melanoma recurrence. This result points out the importance of a relapse-free survival for melanoma patients. The utilities measured in our study can be applied to decision-making processes in clinical trials of new adjuvant drugs.
EVALuna2:19621

Prognosis of Patients With Stage III Melanoma According to American Joint Committee on Cancer Version 8: A Reassessment on the Basis of 3 Independent Stage III Melanoma Cohorts - Garbe, Claus; Keim, Ulrike; Suciu, Stefan; Amaral, Teresa; Eigentler, Thomas K.; Gesierich, Anja; Hauschild, Axel; Heinzerling, Lucie; Kiecker, Felix; Schadendorf, Dirk; Stadler, Rudolf; Sunderkötter, Cord; et al. (Journal of Clinical Oncology, 2020)
PURPOSE: Three new therapies have been approved recently for the adjuvant treatment of stage III melanoma, substantially reducing the risk of tumor recurrences. This study evaluates 3 independent data sets to clarify the survival probabilities of patients with stage III melanoma. PATIENTS AND METHODS: The Central Malignant Melanoma Registry (CMMR) evaluated 1,553 patients with a primary diagnosis of stage III melanoma from 2000 to 2012. Studies from the European Organisation for Research and Treatment of Cancer (EORTC), of 573 patients in the observation arm of the 18991 study and 445 patients in the placebo arm of the 18071 study, were evaluated as reference cohorts. The survival outcomes were compared with the published American Joint Committee on Cancer version 8 (AJCCv8) stage III survival data. RESULTS: For the CMMR stage III cohort versus the AJCCv8 cohort, the melanoma-specific survival (MSS) rates at 5 years were 67% versus 77%, and at 10 years were 56% versus 69%, respectively. For stage IIIA, the MSS rates at 5 years were 80% versus 93%, and at 10 years were 71% versus 88%; for stage IIIB, the MSS rates at 5 years were 75% versus 83%, and at 10 years were 61% versus 77%. The MSS rates of the EORTC studies either overlapped with or were lower than, the CMMR data. CONCLUSION: The MSS rates in the CMMR and EORTC cohorts over the entire stage III are less favorable than those published in AJCCv8. This is particularly true for substages IIIA and IIIB.
CRIS-Team Scopus Importer:2020-08-14

Prognostic factors and outcomes in metastatic uveal melanoma treated with PD-1 or combined PD-1 / CTLA-4 inhibition - Heppt, M.; Heinzerling, Lucie; Kaehler, K.; Forschner, A.; Kirchberger, M.; Loquai, C.; Meissner, M.; Meier, F.; Terheyden, P.; Schell, B.; Herbst, R.; Goeppner, D.; et al. (2017)
EVALuna2:34329

Prognostic factors and outcomes in metastatic uveal melanoma treated with programmed cell death-1 or combined PD-1/cytotoxic T-lymphocyte antigen-4 inhibition - Heppt, Markus V.; Heinzerling, Lucie; Kaehler, Katharina C.; Forschner, Andrea; Kirchberger, Michael C.; Loquai, Carmen; Meissner, Markus; Meier, Friedegund; Terheyden, Patrick; Schell, Beatrice; Herbst, Rudolf; Goeppner, Daniela; et al. (European Journal of Cancer, 2017)
BACKGROUND: Uveal melanoma (UM) is an ocular malignancy with high potential for metastatic spread. In contrast to cutaneous melanoma, immunotherapy has not yet shown convincing efficacy in patients with UM. Combined immune checkpoint blockade with checkpoint programmed cell death-1 (PD-1) and checkpoint cytotoxic T-lymphocyte antigen-4 (CTLA-4) inhibition has not been systematically assessed for UM to date. PATIENTS AND METHODS: Patients with metastatic UM treated with either PD-1 inhibitor monotherapy or combined PD-1 inhibitor and ipilimumab (an anti-CTLA-4 monoclonal antibody) were included from 20 German skin cancer centres. Records from 96 cases were analysed for treatment outcomes. Clinical and blood parameters associated with overall survival (OS) or treatment response were identified with multivariate Cox regression and binary logistic regression. RESULTS: Eighty-six patients were treated with PD-1 inhibitors only (n = 54 for pembrolizumab, n = 32 for nivolumab) with a centrally confirmed response rate of 4.7%. Median OS was 14 months for pembrolizumab-treated and 10 months for nivolumab-treated patients (p = 0.765). Fifteen patients were treated with combined immune checkpoint blockade with partial response observed in two cases. Median OS was not reached in this group. Multivariate Cox regression identified Eastern Cooperative Oncology Group (ECOG) performance status (p = 0.002), elevated serum levels of lactate dehydrogenase (LDH) (p = 0.002) and C-reactive protein (CRP) (p = 0.001), and a relative eosinophil count (REC) <1.5% (p = 0.002) as independent risk factors for poor survival. Patients with elevated CRP and LDH and a REC <1.5% were at highest risk for disease progression and death (p = 0.001). CONCLUSIONS: Blood markers predict survival in metastatic UM treated with immune checkpoint blockade. Normal serum levels of LDH and CRP and a high REC may help identify patients with better prognosis.
EVALuna2:34328

Prognostic factors and treatment outcomes in 444 patients with mucosal melanoma - Heppt, Markus V.; Roesch, Alexander; Weide, Benjamin; Gutzmer, Ralf; Meier, Friedegund; Loquai, Carmen; Kaehler, Katharina C.; Gesierich, Anja; Meissner, Markus; Von Bubnoff, Dagmar; Goeppner, Daniela; Schlaak, Max; et al. (European Journal of Cancer, 2017)
BACKGROUND: Mucosal melanoma (MM) is a rare but diverse cancer entity. Prognostic factors are not well established for Caucasians with MM. PATIENTS AND METHODS: We analysed the disease course of 444 patients from 15 German skin cancer centres. Disease progression was determined with the cumulative incidence function. Survival times were estimated with the Kaplan-Meier method. Prognostic parameters were identified with multivariate Cox regression analysis. RESULTS: Common anatomic sites of primary tumours were head and neck (MMHN, 37.2%), female genital tract (MMFG, 30.4%) and anorectal region (MMAN, 21.8%). MMAN patients showed the highest vertical tumour thickness (p = 0.001), had a more advanced nodal status (p = 0.014) and a higher percentage of metastatic disease (p = 0.001) at diagnosis. Mutations of NRAS (13.8%), KIT (8.6%) and BRAF (6.4%) were evenly distributed across all tumour site groups. Local relapses were observed in 32.4% and most commonly occurred in the MMHN group (p = 0.016). Male gender (p = 0.047), advanced tumour stage (p = 0.001), nodal disease (p = 0.001) and incomplete resection status (p = 0.001) were independent risk factors for disease progression. Overall survival (OS) was highest in the MMFG group (p = 0.030) and in patients without ulceration (p = 0.004). Multivariate risk factors for OS were M stage at diagnosis (p = 0.002) and incomplete resection of the primary tumour (p = 0.001). CONCLUSION: In this large series of MM patients in a European population, anorectal MM was associated with the poorest prognosis.
EVALuna2:34332

Programmed cell death protein-1 (PD-1) inhibitor therapy in patients with advanced melanoma and preexisting autoimmunity or ipilimumab-triggered autoimmunity - Gutzmer, Ralf; Koop, Anika; Meier, Friedegund; Hassel, Jessica C.; Terheyden, Patrick; Zimmer, Lisa; Heinzerling, Lucie; Ugurel, Selma; Pfoehler, Claudia; Gesierich, Anja; Livingstone, Elisabeth; Satzger, Imke; et al. (European Journal of Cancer, 2017)
AIM: Programmed cell death protein 1 (PD-1) inhibitors are a common treatment strategy for metastatic melanoma and other tumour entities. Clinical trials usually exclude patients with preexisting autoimmune diseases, thus experience with PD-1 inhibitor (PD-1i) in this patient population is limited. PATIENTS AND METHODS: Metastatic melanoma patients with preexisting autoimmune disorders or previous ipilimumab-triggered immune-related adverse events (irAE) undergoing treatment with PD-1i from seven German skin cancer centres were evaluated retrospectively with regard to flare of the preexisting autoimmunity and development of new, not preexisting irAE as well as response to PD-1i therapy. RESULTS: In total, 41 patients had either preexisting autoimmunity (n=19, group A, including two patients with additional ipilimumab-triggered autoimmune colitis) or ipilimumab-triggered irAE (n=22, group B). At PD-1i therapy initiation, six patients in group A and two patients in group B required immunosuppressive therapy. In group A, a flare of preexisting autoimmune disorders was seen in 42% of patients, new irAE in 16%. In group B, 4.5% of patients showed a flare of ipilimumab-triggered irAE and 23% new irAE. All flares of preexisting autoimmune disorders or irAE were managed by immunosuppressive and/or symptomatic therapy and did not require termination of PD-1i therapy. tumour responses (32% in group A and 45% in group B) were unrelated to occurrence of autoimmunity. CONCLUSION: While preexisting autoimmunity commonly showed a flare during PD-1i therapy, a flare of ipilimumab-triggered irAE was rare. Response rates were above 30% and unrelated to irAE. PD-1i therapy can be considered in patients with autoimmune disorders depending on severity and activity of autoimmunity.
EVALuna2:34334

Real world experience in low-dose ipilimumab in combination with PD-1 blockade in advanced melanoma patients - Kirchberger, Michael Constantin; Moreira, Alvaro; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (Oncotarget, 2018)
Dual immune-checkpoint blockade with the anti-PD-1 antibody nivolumab (1 mg/kg) and standard-dose ipilimumab (3 mg/kg) is the mainstay of immunotherapy in advanced melanoma and it is approved since 2016. However, severe side effects (grade 3/4) occur in up to 60% of the patients. Recently, clinical trials have shown similar anti-tumor activity with a more favorable toxicity profile in patients treated with low-dose ipilimumab (1 mg/kg) and standard-dose pembrolizumab (2 mg/kg). In this study we report on the real-world experience of this dosing regime in advanced melanoma patients not eligible for clinical trials. A total of 33 patients with metastatic melanoma (24 with cutaneous and 9 with uveal melanoma) were assessed, retrospectively. Brain metastases were present in 33% of the patients and lactate dehydrogenase was elevated in 70%. Overall response rates were 38% and 0% in cutaneous melanoma and uveal melanoma respectively. Median overall survival was not reached in cutaneous melanoma and was 18 months in uveal melanoma. In 18% of the patients at least one treatment-related severe adverse event was observed. Our observation that the combination of standard dose pembrolizumab and low-dose ipilimumab has a favorable toxicity profile yet anti-tumor activity comparable to the approved standard-dose combination regime in advanced patients not suitable for enrollment in clinical trials is encouraging.
EVALuna2:34415

Reply: Intra-patient heterogeneity of BRAF mutation status: fact or fiction? - Heinzerling, Lucie; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine (British Journal of Cancer, 2014)
EVALuna2:6657

Schlusswort - Heinzerling, Lucie (Deutsches Ärzteblatt international, 2019)
CRIS-Team Scopus Importer:2019-06-25

Senescence markers: Predictive for response to checkpoint inhibitors - Moreira, Alvaro; Gross, Stefanie; Kirchberger, Michael Constantin; Erdmann, Michael; Schuler, Gerold; Heinzerling, Lucie (International Journal of Cancer, 2019)
Recent studies suggest that the age-related remodeling of the immune system, known as immunosenescence, could impact the efficacy of immune checkpoint inhibitors in leukemia or nonsmall cell lung cancer. We investigated whether senescence markers can predict response to checkpoint inhibitor therapy in melanoma patients. The peripheral blood of patients with newly diagnosed, untreated metastatic melanoma was analyzed by flow cytometry to correlate the frequency of senescence markers with clinical response as measured by RECIST after 12 weeks of treatment with immune checkpoint inhibitors. The loss of surface markers CD27 and CD28 or the expression of Tim-3 and CD57 on T cells was associated with resistance to checkpoint inhibitor blockade, presenting these phenotypes as possible predictive biomarkers for checkpoint inhibitor therapy. Immunosenescence seems to impact on the response to checkpoint inhibitor therapy in melanoma patients. Thus, lymphocyte phenotyping for senescence markers, with the introduction of immunosenescence panels, could be predictive for checkpoint inhibitor response.
CRIS-Team Scopus Importer:2019-05-21
Keywords: biomarker; immune checkpoint inhibitors; immunosenescence; melanoma

Sensitive allele-specific real-time PCR test for mutations in BRAF codon V600 in skin melanoma - Pisareva, Ekaterina; Gutkina, Nadezhda; Kovalenko, Sergei; Kuehnapfel, Sarah; Hartmann, Arndt; Heinzerling, Lucie; Schneider-Stock, Regine; Lyubchenko, Lyudmila; Shamanin, Vladimir A. (Melanoma Research, 2014)
Mutations at BRAF codon V600 are used as predictive biomarkers for targeted therapy of skin melanoma. Here, a simple sensitive test to detect mutations of BRAF-V600 was developed using real-time PCR with allele-specific primers and TaqMan probes. Two versions of the test using sense and antisense allele-specific primers were designed and evaluated. The test detected 1% mutant allele V600E/K in 10 ng DNA standard made from wild-type human DNA spiked with BRAF-V600E or the V600K plasmid. The test was validated on clinical formalin-fixed paraffin-embedded samples of skin melanoma using pyrosequencing as a reference method. In the clinical samples, we detected the common mutation V600E, as well as the rare mutations V600K, V600E2 (codon GAA), V600E2 K601del, V600D-K601del, and V600R. In comparison with pyrosequencing, both versions of the test had 100% specificity with sensitivities of 97 and 86% for sense and antisense allele-specific primers, respectively. Using the PCR test with sense allele-specific primers, mutations in V600 were found in 33 of 51 Russian patients (64.7%) with cutaneous melanoma. This closed-tube real-time PCR test can be used as a simple and sensitive assay for mutations of BRAF-V600 in cutaneous melanoma.
EVALuna2:6621

Sequence-dependent cross-resistance of combined radiotherapy plus BRAF(V600E) inhibition in melanoma - Shannan, B.; Matschke, J.; Chauvistre, H.; Vogel, F.; Klein, D.; Meier, F.; Westphal, D.; Bruns, J.; Rauschenberg, R.; Utikal, J.; Forschner, A.; Berking, C.; et al. (European Journal of Cancer, 2019)
Introduction: Treatment of patients with metastatic melanoma is hampered by drug-resistance and often requires combination with radiotherapy as last-resort option. However, also after radiotherapy, clinical relapses are common. Methods & results: Our preclinical models indicated a higher rate of tumour relapse when melanoma cells were first treated with BRAF V600E inhibition (BRAFi) followed by radiotherapy as compared to the reverse sequence. Accordingly, retrospective follow-up data from 65 stage-IV melanoma patients with irradiated melanoma brain metastases confirmed a shortened duration of local response of mitogen-activated protein kinase (MAPK)-inhibitor–pretreated compared with MAPK-inhibitor–naïve intracranial metastases. On the molecular level, we identified JARID1B/KDM5B as a cellular marker for cross-resistance between BRAFi and radiotherapy. JARID1B high cells appeared more frequently under upfront BRAFi as compared with upfront radiation. JARID1B favours cell survival by transcriptional regulation of genes controlling cell cycle, DNA repair and cell death. Conclusion: The level of cross-resistance between combined MAPK inhibition and radiotherapy is dependent on the treatment sequence. JARID1B may represent a novel therapy-overarching resistance marker.
CRIS-Team WoS Importer:2019-03-06
Keywords: Cross-resistance; JARID1B/KDM5B; Melanoma; Radiotherapy; Repopulation; Resistance; Slow-cycling cells; Targeted therapy; Therapy sequencing

SERIO - Side Effect Registry Immuno-Oncology Side Effect Registry for rare, severe and complex Side Effects of Immunotherapy - Kramer, Rafaela; Mentzer, D.; Erdmann, M.; Knauss, S.; Broeckelmann, P. J.; Hassel, J. C.; Ugurel, S.; Pavel, Marianne Ellen; Nickel, Franziska; Landendinger, M.; Fuchs, Friederike; Meidenbauer, Norbert; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Serio - Side Effect Registry in Immuno-Oncology - Koutzamanidis, Rafaela; Mentzer, Dirk; Knauss, Samuel; Broeckelmann, Paul J.; Hassel, Jessica Cecile; Ugurel-Becker, Selma; Pavel, Marianne Ellen; Nickel, Florian; Landendinger, Melanie; Fuchs, Florian; Meidenbauer, Norbert; Jefremow, Andre; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Serositis in Association with System Therapy with Checkpoint Inhibitors - More frequent than thought? - An Evaluation of the SERIO Adverse Event Registry - Zierold, S.; Kramer, R.; Erdmann, Michael; Akcetin, S. L.; Maier, A. M.; Koenig, A.; Theurich, S.; French, L. E.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Side effect management during immune checkpoint blockade using CTLA-4 and PD-1 antibodies for metastatic melanoma - an update - Kaehler, Katharina C.; Hassel, Jessica C.; Heinzerling, Lucie; Loquai, Carmen; Thoms, Kai-Martin; Ugurel, Selma; Zimmer, Lisa; Gutzmer, Ralf (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CTLA-4 and PD-1 play a key role in tumor-induced downregulation of lymphocytic immune responses. Immune checkpoint inhibitors have been shown to alter the immune response to various cancer types. Anti-CTLA-4 and anti-PD-1 antibodies affect the interaction between tumor, antigen-presenting cells and T lymphocytes. Clinical studies of the anti-CTLA-4 antibody ipilimumab and the anti-PD-1 antibodies nivolumab and pembrolizumab have provided evidence of their positive effects on overall survival in melanoma patients. Combined treatment using ipilimumab and nivolumab has been shown to achieve five-year survival rates of 52 %. Such enhancement of the immune response is inevitably associated with adverse events. Knowledge of the spectrum of side effects is essential, both in terms of prevention and management. Adverse events include colitis, dermatitis, hypophysitis, thyroiditis, hepatitis and other, less common autoimmune phenomena. In recent years, considerable progress has been made in the detection and treatment of the aforementioned immune-related adverse events. However, early diagnosis of rare neurological or cardiac side effects, which may be associated with increased mortality, frequently pose a challenge. The present update highlights our current understanding as well as new insights into the spectrum of side effects associated with checkpoint inhibitors and their management.
CRIS-Team WoS Importer:2020-06-16

Skin Cancer in Childhood and Adolescents: Treatment and Implications for the Long-Term Follow-Up - Heinzerling, Lucie; Eigentler, Thomas Kurt (Springer International Publishing, 2020)
Skin cancer in childhood and adolescence is rare. Most young patients with cutaneous malignancies have underlying risk factors like a hereditary predisposition or immunosuppression. Rarely, patients present with spontaneous melanoma which can arise from congenital nevi. Treatment for skin cancer is being performed as in adults with the use of the paediatric support structures in addition to dermatooncological care. For medical therapies, e.g. systemic therapy of melanoma, basal or squamous cell carcinoma counselling on fertility has to be implemented as is standard for the younger adults. Since primary skin cancer is often associated with secondary skin cancers, patient education on preventive measures as well as regular clinical controls is crucial to ensure early detection.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Congenital; Excision; Fertility; Melanoma; Non-melanoma skin cancer; Squamous cell carcinoma

Spätfolgen nach Immuntherapie: Immunvermittelte Nebenwirkungen von Checkpointinhibitoren - Duong, Sophie L.; Zierold, Sarah; Kramer, Rafaela; Reincke, Martin; Kerl-French, Katrin; Boehmerle, Wolfgang; Pavel, Marianne Ellen; Weckbach, Ludwig; French, Lars E.; Knauss, Samuel; Heinzerling, Lucie (Onkologe, 2021)
Background: Immune checkpoint inhibitors (ICIs) are potent immunotherapeutic agents for many tumor entities. However, ICIs can induce immune-related adverse events (irAE) that can potentially affect any organ system, causing life-changing sequelae or even death. These irAEs can occur months after termination of immunotherapy and long-term effects may persist for years after finishing therapy. Due to expanding clinical indications for ICIs including therapy in earlier tumor stages, the risk–benefit analysis needs to take into account these long-term side effects. Objectives: The sequelae of ICI therapy are reviewed and the international online registry Side Effect Registry Immuno-Oncology (SERIO) for the unified collection and characterization of irAEs is introduced. Materials and methods: We analyzed data from SERIO and performed a selective literature search in the databases PubMed, Cochrane Central Register of Controlled Trials and Google Scholar to characterize, analyze and summarize long-term sequelae of irAE induced by ICI therapy. Results: The most commonly observed irAEs with long-term sequelae involve the skin (leucotrichia, melanoma-associated hypopigmentation) and endocrine irAEs (thyroiditis, hypophysitis, adrenalitis and diabetes). While the former is especially stigmatizing, endocrine irAEs usually require long-term hormone substitution. Neurologic and cardiologic irAEs are relatively rare, but they are associated with severe complications leading to increased morbidity and mortality. Conclusions: Until now, prospective data about long-term consequences of irAEs are lacking. The SERIO registry addresses this need as irAEs are collected to enable long-term follow-up and optimized management.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Benefit-risk assessment; Data collection; Hypopigmentation; Neoplasms; Registries

Stereotactic radiosurgery and combined immune checkpoint therapy with ipilimumab and nivolumab in patients with melanoma brain metastases: A retrospective monocentric toxicity analysis - Bodensohn, Raphael; Werner, Simone; Reis, Jonas; Pazos Escudero, Montserrat; Kaempfel, Anna Lena; Hadi, Indrawati; Forbrig, Robert; Manapov, Farkhad; Corradini, Stefanie; Belka, Claus; Theurich, Sebastian; Heinzerling, Lucie; et al. (Clinical and Translational Radiation Oncology, 2023)
Purpose and objective: Adding stereotactic radiosurgery (SRS) to combined immune checkpoint therapy with ipilimumab and nivolumab (IPI + NIVO) has led to promising results for patients with melanoma brain metastases (MBM). This study retrospectively analyzes the toxicity profile depending on the timing of SRS with regard to IPI + NIVO. Materials and methods: For this study, the clinical database was searched for all patients with MBM who were treated with SRS and IPI + NIVO. The patients were separated into three groups: group A completed IPI + NIVO (usually up to four cycles) >14 days before SRS, in group B IPI + NIVO was initiated>14 days after SRS, and group C received SRS concurrently to IPI + NIVO. Treatment related toxicity was obtained from clinical and neuroradiological records. Analyses were performed using the Fisher-Yates-test. Results: 31 patients were assessed including six (19.4 %), seven (22.6 %) and 18 (58.1 %) patients, in groups A, B and C, respectively. Baseline prognostic markers between groups were balanced. In total, five (16.1 %) patients experienced neurological grade 3 toxicities related to SRS. All of these five patients were in group C, which was near-significantly correlated with a risk for grade 3 toxicities (p = 0.058). Post-hoc analyses showed that a maximum time period of seven days between SRS and IPI + NIVO was significantly correlated with grade 3 toxicity (p = 0.048). Conclusion: Application of SRS to IPI + NIVO within a seven-day span was related to higher toxicity rates in this retrospective analysis. After previous studies focused on immune checkpoint monotherapies with SRS and declared it as safe, this study indicates that concomitant application of IPI + NIVO and SRS might increase side effects. Prospective validation is warranted to corroborate these findings.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Checkpoint inhibition; Intracranial hemorrhage; Ipilimumab; Nivolumab; Radiation necrosis; Side effects; Stereotactic radiosurgery

Successful Treatment of a primary cutaneous aggressive epidermotropic CD8+T-cell Lymphoma with Nivolumab - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schuler, Gerold; Schliep, S.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Surveillance of patients with conjunctival melanoma in German-speaking countries: A multinational survey of the German dermatologic cooperative oncology group - Wessely, Anja; Steeb, Theresa; Berking, Carola; Schlaak, Max; Heppt, Markus; Alter, Mareike; Bayerl, Christiane; Bender, Armin; Bruning, Guido; Dabrowski, Evelyn; Debus, Dirk; Devereux, Nina; et al. (European Journal of Cancer, 2021)
CRIS-Team Scopus Importer:2020-12-11

Survival of metastatic melanoma patients after dendritic cell vaccination correlates with expression of leukocyte phosphatidylethanolamine-binding protein 1/Raf kinase inhibitory protein - Buschow, Sonja I.; Ramazzotti, Matteo; Reinieren-Beeren, Inge M. J.; Heinzerling, Lucie; Westdorp, Harm; Stefanini, Irene; Beltrame, Luca; Hato, Stanleyson V.; Ellebaek, Eva; Gross, Stefanie; Van Anh Nguyen; Weinlich, Georg; et al. (Oncotarget, 2017)
Immunotherapy for metastatic melanoma offers great promise but, to date, only a subset of patients have responded. There is an urgent need to identify ways of allocating patients to the most beneficial therapy, to increase survival and decrease therapy-associated morbidity and costs. Blood-based biomarkers are of particular interest because of their straightforward implementation in routine clinical care. We sought to identify markers for dendritic cell (DC) vaccine-based immunotherapy against metastatic melanoma through gene expression analysis of peripheral blood mononuclear cells. A large-scale microarray analysis of 74 samples from two treatment centers, taken directly after the first round of DC vaccination, was performed. We found that phosphatidylethanolamine binding protein 1 (PEBP1)/Raf Kinase inhibitory protein (RKIP) expression can be used to identify a significant proportion of patients who performed poorly after DC vaccination. This result was validated by q-PCR analysis on blood samples from a second cohort of 95 patients treated with DC vaccination in four different centers. We conclude that low PEBP1 expression correlates with poor overall survival after DC vaccination. Intriguingly, this was only the case for expression of PEBP1 after, but not prior to, DC vaccination. Moreover, the change in PEBP1 expression upon vaccination correlated well with survival. Further analyses revealed that PEBP1 expression positively correlated with genes involved in T cell responses but inversely correlated with genes associated with myeloid cells and aberrant inflammation including STAT3, NOTCH1, and MAPK1. Concordantly, PEBP1 inversely correlated with the myeloid/lymphoid-ratio and was suppressed in patients suffering from chronic inflammatory disease.
EVALuna2:34315

Sustainable responses in metastatic melanoma patients with and without brain metastases after elective discontinuation of anti-PD1-based immunotherapy due to complete response - Dimitriou, Florentia; Zaremba, Anne; Allayous, Clara; Kähler, Katharina C.; Gerard, Camille L.; Festino, Lucia; Schäfer, Sarah; Toussaint, Frédéric; Heinzerling, Lucie; Hassel, Jessica C.; Ascierto, Paolo A.; Michielin, Olivier; et al. (European Journal of Cancer, 2021)
Background: Anti-PD1–based immunotherapy is currently used in most patients with advanced melanoma. Despite the remarkable data regarding overall survival, the optimal treatment duration is still unknown. Methods: We evaluated the outcome of 125 patients with advanced melanoma with and without brain metastases (MBM), treated either with anti-PD1 monotherapy (N = 97) or combined with anti-CTLA4 (N = 28) after elective treatment discontinuation due to complete response (CR) (group A, N = 86), or treatment-limiting toxicity (N = 33) and investigator's decision (ID, N = 6) (group B) with subsequent CR. Results: For group A, median duration of treatment (mDoT) was 22 months (range 5–49) and median time to CR 9 months (range 2–47). Accordingly, mDoT for group B was 3 months (range 0–36) and median time to CR 7 months (range 1–32). Seven patients from group A and three from group B experienced disease recurrence. Off-treatment survival was not reached. Median off-treatment response time (mOTRt) was 19 months (range 0–42) and 25 months (range 0–66), respectively. For MBM, mOTRt was 17 months (range 7–41) and 28 months (range 9–39), respectively. After a median follow-up of 38 months (range 9–70), seven (5.6%) patients had deceased, one (0.8%) due to melanoma. Conclusions: Treatment discontinuation is feasible also in patients with MBM. Efficacy outcomes seemed to be similar in both groups of patients who achieved CR, regardless of reason for discontinuation. In patients who experienced disease relapse, treatment re-challenge with anti-PD1 resulted in subsequent renewed response.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anti-PD1 treatment; Brain metastases; Discontinuation; Immunotherapy; Melanoma

T Cell Costimulation Molecules CD80/86 Inhibit Osteoclast Differentiation by Inducing the IDO/Tryptophan Pathway - Bozec, Aline; Zaiss, Mario; Kagwiria, Rosebeth; Voll, Reinhard; Rauh, Manfred; Chen, Zhu; Müller-Schmucker, Sandra; Kroczek, Richard A.; Heinzerling, Lucie; Moser, Muriel; Mellor, Andrew L.; David, Jean-Pierre; et al. (Science Translational Medicine, 2014)
Bone resorption is seminal for the physiological remodeling of bone during life. However, this process needs to be strictly controlled; excessive bone resorption results in pathologic bone loss, osteoporosis, and fracture. We describe a control mechanism of bone resorption by the adaptive immune system. CD80/86, a pair of molecules expressed by antigen-presenting cells and involved in T cell costimulation, act as negative regulator for the generation of bone-resorbing osteoclasts. CD80/86-deficient mice were osteopenic because of increased osteoclast differentiation. CD80/86-deficient osteoclasts escaped physiological inhibition by CTLA-4 or regulatory T cells. Mechanistically, engagement of CD80/86 by CTLA-4 induced activation of the enzyme indoleamine 2,3-dioxygenase (IDO) in osteoclast precursors, which degraded tryptophan and promoted apoptosis. Concordantly, IDO-deficient mice also showed an osteopenic bone phenotype with higher numbers of osteoclast precursors and osteoclasts. Also, IDO-deficient mononuclear cells escaped the anti-osteoclastogenic effect of CTLA-4. This molecular mechanism was also present in humans because targeting CD80/86 by abatacept, a CTLA-4-immunoglobulin fusion protein, reduced, whereas blockade of CTLA-4 by ipilimumab antibody enhanced, the frequency of peripheral osteoclast precursors and osteoclastogenesis. In summary, these data show an important role of the adaptive immune system, in particular T cell CD80/86 costimulation molecules, in the physiological regulation of bone resorption and preservation of bone mass, as well as affect the understanding of the function of current and future drugs fostering or blocking the effects of CTLA-4 in humans.
EVALuna2:12912

The neurotrophin Neuritin1 (cpg15) is involved in melanoma migration, attachment independent growth, and vascular mimicry - Boßerhoff, Anja Katrin; Schneider, Nadja; Ellmann, Lisa; Heinzerling, Lucie; Kuphal, Silke (Oncotarget, 2017)
The neurotrophin Neuritin1 (NRN1; cpg15) belongs to the candidate plasticity gene (CPG) family and is expressed in postmitotic-differentiating neurons of the developmental nervous system and neuronal structures associated with plasticity in the brain of human adult.Our newest findings document that NRN1 deregulation could contribute also to disease development and have impact on malignant melanoma. Our analyses displayed the over-expression of NRN1 in melanoma in vitro and in vivo, shown by immunohistochemistry and qRT-PCR on microdissected melanoma tissue; furthermore, soluble NRN1 was detectable in tissue culture supernatant and serum of melanoma patients.To investigate the role of NRN1 in melanoma we performed knockdown, over-expression and recombinant-NRN1-treatment experiments affiliated by functional assays. Our results show that migration, attachment independent growth and vasculogenesis were affected after manipulation of NRN1 on endogenous and extrinsic level. Interestingly, high NRN1 serum levels correlate with low MIA serum levels (< 10ng/ml). Therefore, we speculate that NRN1 could be a marker for early melanoma stages, in particular.In summary, we detected an overexpression of NRN1 in melanoma patient. In functional cell culture experiments we found a correlation between NRN1 expression and the cancerous behavior of melanoma cells.
EVALuna2:4752

The outweigh of toxicity versus risk of recurrence for adjuvant interferon therapy: a survey in German melanoma patients and their treating physicians - Kähler, Katharina C.; Blome, Christine; Forschner, Andrea; Gutzmer, Ralf; Hauschild, Axel; Heinzerling, Lucie; Livingstone, Elisabeth; Loquai, Carmen; Müller-Brenne, Tina; Schadendorf, Dirk; Utikal, Jochen; Wagner, Tobias; et al. (Oncotarget, 2018)
After more than two decades with interferon alfa-2a and 2b (IFN) as the only approved drugs in the adjuvant setting for melanoma, new treatment approaches like immune checkpoint inhibitors and BRAF-MEK inhibitors improve the progression free survival (PFS) and also the overall survival (OS). We compared physicians' preferences ("utilities") for health states associated with IFN therapy to their patients' preferences. Utilities describe a preference for a specific health state on a scale of 0 (as bad as death) to 1.0 (perfect health). Setting: We assessed utilities for health states associated with adjuvant IFN using the standard gamble technique in 108 physicians and 130 melanoma patients. Four IFN toxicity scenarios and three outcome scenarios were given to the participants. Both groups were asked for the 5-year disease free survival (DFS) they would need to accept the described IFN-related side effects. Results: In both groups, utilities for melanoma relapse were significantly lower than for IFN side effects, showing that toxicity was more acceptable than relapse. Physicians indicated higher utilities for each scenario and needed lower 5-year DFS both in case of mild-to-moderate and severe side effects. Patients were willing to tolerate mild-to-moderate and severe toxicity for a 50% and 75% chance of 5-year DFS, while physicians only required a chance of 40% and 50%, respectively. Conclusion: Both physicians and patients rated melanoma recurrence much lower than even severe IFN side effects. In direct comparison, physicians rated cancer-related scenarios more positively and accepted IFN toxicity for an even lower treatment benefit.
EVALuna2:34416

The Quality of Guidelines for the Treatment of Cutaneous Melanoma: A methodological Assessment - Steeb, Theresa; Wessely, A.; Drexler, K.; Salzmann, M.; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, M.; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The quality of practice guidelines for melanoma: A methodologic appraisal with the agree ii and agree-rex instruments - Steeb, Theresa; Wessely, Anja; Drexler, Konstantin; Salzmann, Martin; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, Markus; Berking, Carola; Heppt, Markus (Cancers, 2020)
Multiple guidelines on cutaneous melanoma (CM) are available from several consortia and countries. To provide up-to-date guidance in the rapidly changing field of melanoma treatment, guideline developers have to provide regular updates without compromises of quality. We performed a systematic search in guideline databases, Medline and Embase to identify guidelines on CM. The methodological quality of the identified guidelines was independently assessed by five reviewers using the instruments “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). We performed descriptive analysis, explored subgroup differences using the Kruskal–Wallis (H) test and examined the relationship between distinct domains and items of the instruments with Spearman’s correlation. Six guidelines by consortia from Australia, France, Germany, Scotland, Spain and the United States of America were included. The German guideline fulfilled 71%–98% of criteria in AGREE II and 78%–96% for AGREE-REX, obtaining the highest scores. Deficiencies in the domains of “applicability” and “values and preferences” were observed in all guidelines. The German and Spanish guidelines significantly differed from each other in most of the domains. The domains “applicability” and “values and preferences” were identified as methodological weaknesses requiring careful revision and improvement in the future.
CRIS-Team Scopus Importer:2020-06-26
Keywords: AGREE; Cutaneous melanoma; Level of evidence; Melanoma treatment; Practice guideline

Therapy preferences in melanoma treatment - willingness to pay and preference of quality versus length of life of patients, physicians and healthy controls - Krammer, Ramona; Heinzerling, Lucie (PLoS ONE, 2014)
New melanoma therapies, like e.g. ipilimumab, improve survival. However, only a small subset of patients benefits while 60% encounter side effects. Furthermore, these marginal benefits come at a very high price of EUR110'000 per treatment. This study examines attitudes towards melanoma therapy options of physicians, healthy individuals and patients, their willingness to pay and preference of quality versus length of life.Based on findings from a focus group questionnaires were developed and pretested. After obtaining ethical approval and informed consent surveys were conducted in a total of 90 participants (n = 30 for each group). Statistical analyses were conducted using R.Attitudes vastly differed between healthy participants, physicians and melanoma patients. Whereas melanoma patients show a high willingness to endure side effects despite very small survival gains (down to 1 extra week) or even only hope with no survival benefit, healthy controls are more critical, while physicians are the most therapy adverse. Consequently, if given EUR100'000 and the free decision what to spend the money on the willingness to pay for therapy was much higher in the patient group (68%) compared to 28% of healthy controls and only 43% of the physicians, respectively. When lowering the amount of cash that could be received instead of ipilimumab to EUR50'000 or EUR10'000 to test price sensitivity 69% (+1%) and 76% (+8%) of melanoma patients, respectively, preferred ipilimumab over cash. When judging on societal spending even melanoma patients opted for spending on ipilimumab in only 21%.The judgment about the benefits of new treatment options largely differs between groups, physicians being the most critical against therapy. Price elasticity was low.
EVALuna2:19509

Therapy preferences in melanoma treatment—Willingness to pay and preference of quality versus length of life of patients, physicians, healthy individuals and physicians with oncological disease - Weiß, Julia; Kirchberger, Michael; Heinzerling, Lucie (Cancer Medicine, 2020)
Background: In recent years, monoclonal antibodies such as ipilimumab, nivolumab, and pembrolizumab have made a significant impact on the treatment of advanced melanoma. Combination of immune checkpoint inhibitors leads to improved survival and response rates of 58%-61% as compared to monotherapy (36%-44%). However, the price for the better response rates is also a higher frequency of severe adverse events (59%) as compared to monotherapy (17%-21%). This study examines attitudes towards melanoma therapy options of physicians, healthy individuals, melanoma patients, and physicians with oncological disease, their willingness to pay, and preference of quality versus length of life. Methods: After obtaining ethical approval and informed consent surveys were conducted in 111 participants divided into four groups: melanoma patients (n = 30), healthy individuals as controls (n = 30), physicians (n = 27), and physicians with oncological disease (n = 24). Statistical analyses were conducted using SPSS statistics (version 25, IBM), applying the Pearson´s chi-squared test, Spearman correlation coefficient, Wilcoxon-Mann-Whitney test, and Kruskal-Wallis test. Results: Life prolongation is more valued by melanoma patients and physicians with oncological disease compared to healthy controls and healthy physicians. In total, 30% of melanoma patients opt for a life prolonging therapy in all cases, even if this life prolongation is only marginal. Physicians are the strongest proponents of combination immunotherapy. Conclusion: The valuation of the different treatment options differs in the four study groups with affected people valuing life prolongation much more. The individual value of cancer therapies is high, but differs from the societal standpoint.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cancer management; clinical guidelines; immunology; quality of life

The role of immune checkpoint blockade in uveal melanoma - Wessely, Anja; Steeb, Theresa; Erdmann, Michael; Heinzerling, Lucie; Vera, Julio; Schlaak, Max; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2020)
Uveal melanoma (UM) represents the most common intraocular malignancy in adults and accounts for about 5% of all melanomas. Primary disease can be effectively controlled by several local therapy options, but UM has a high potential for metastatic spread, especially to the liver. Despite its clinical and genetic heterogeneity, therapy of metastatic UM has largely been adopted from cutaneous melanoma (CM) with discouraging results until now. The introduction of antibodies targeting CTLA-4 and PD-1 for immune checkpoint blockade (ICB) has revolutionized the field of cancer therapy and has achieved pioneering results in metastatic CM. Thus, expectations were high that patients with metastatic UM would also benefit from these new therapy options. This review provides a comprehensive and up-to-date overview on the role of ICB in UM. We give a summary of UM biology, its clinical features, and how it differs from CM. The results of several studies that have been investigating ICB in metastatic UM are presented. We discuss possible reasons for the lack of efficacy of ICB in UM compared to CM, highlight the pitfalls of ICB in this cancer entity, and explain why other immune-modulating therapies could still be an option for future UM therapies.
CRIS-Team Scopus Importer:2020-02-14
Keywords: CTLA-4; Cytotoxic T lymphocyte-associated antigen; Immune checkpoint blockade; Ipilimumab; Nivolumab; Ocular melanoma; PD-1; Pembrolizumab; Programmed death 1; Uveal melanoma

The tanning habits and interest in sunscreen of Google users: what happened in 12 years? - Kirchberger, Michael C.; Heppt, Markus V.; Eigentler, Thomas K.; Kirchberger, Markus A.; Schuler, Gerold; Heinzerling, Lucie (Photodermatology Photoimmunology & Photomedicine, 2017)
BACKGROUND: The incidence of melanoma has been rising worldwide. One possible reason for this is natural and artificial UV exposure. Only little data on actual consumer statistics from tanning studios and the usage of sunscreen are available. Therefore, it is difficult to describe trends for both and identify the impact of preventive measures. METHODS: To gain knowledge about the popularity of 'tanning bed' and 'sunscreen', normalized search volumes for both search queries were obtained from Google Trends for 11 countries between January 2004 and June 2016. RESULTS: With few exceptions, worldwide interest in 'tanning bed' has been declining, whereas interest in 'sunscreen' has been increasing. The assessed countries from the Southern Hemisphere showed minor interest in tanning compared to the Northern Hemisphere. Both search queries were observed to fluctuate in a seasonal pattern. Skin cancer prevention measures influence the interest in tanning beds and sunscreen. CONCLUSION: Google Trends data can act as a first surrogate marker to evaluate the influence of skin cancer campaigns on the popularity of tanning beds and sunscreen. Fine-tuning of skin cancer campaigns according to seasonal and geographic trends and behaviors may help to maximize their success.
EVALuna2:34324

Tolerability and efficacy of BRAF and MEK inhibitors for metastasized melanoma after intra-class switch: a multicenter, retrospective study - Salzmann, M.; Wald, A.; Stege, H.; Loquai, C.; Zimmer, L.; Hayani, K.; Heinzerling, Lucie; Gutzmer, R.; Enk, A.; Hassel, J. C. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Tolerability of BRAF/MEK inhibitor combinations: Adverse event evaluation and management - Heinzerling, Lucie; Eigentler, Thomas K.; Fluck, Michael; Hassel, Jessica C.; Heller-Schenck, Daniela; Leipe, Jan; Pauschinger, Mathias; Vogel, Arndt; Zimmer, Lisa; Gutzmer, Ralf (ESMO Open, 2019)
The inhibition of the mitogen-activated protein kinases signalling pathway through combined use of BRAF and MEK inhibitors (BRAFi+MEKi) represents an established therapeutic option in patients with BRAF-mutated, advanced melanoma. These efficient therapies are well tolerated with mostly moderate and reversible side effects and a discontinuation rate due to adverse events of 11.5%-15.7%. Median duration of therapy ranges between 8.8 and 11.7 months. Based on data from confirmatory trials, safety profiles of three BRAFi+MEKi combinations were reviewed, that is, dabrafenib plus trametinib, vemurafenib plus cobimetinib and encorafenib plus binimetinib. Many adverse events are class effects, such as cutaneous, gastrointestinal, ocular, cardiac and musculoskeletal events; some adverse events are substance associated. Fever (dabrafenib) and photosensitivity (vemurafenib) are the most common and clinically prominent examples. Other adverse events are less frequent and the association to one substance is less strong such as anaemia, facial paresis (encorafenib), neutropenia (dabrafenib), skin rash, QTc prolongation and increased liver function tests (vemurafenib). This narrative review provides recommendations for monitoring, adverse event evaluation and management focusing on the clinically relevant side effects of the three regimens.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adverse events; BRAF; MEK; melanoma; safety

Transient response to nivolumab and relapse after infliximab in a patient with primary cutaneous CD8-positive aggressive epidermotropic cytotoxic T-cell lymphoma - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schliep, S.; Schuler, Gerold; Dummer, R.; Heinzerling, Lucie (British Journal of Dermatology, 2020)
CRIS-Team WoS Importer:2020-10-02

Trial watch : the gut microbiota as a tool to boost the clinical efficacy of anticancer immunotherapy - Daillere, Romain; Derosa, Lisa; Bonvalet, Melodie; Segata, Nicola; Routy, Bertrand; Gariboldi, Manuela; Budinska, Eva; De Vries, I. Jolanda M.; Naccarati, Alessio Gordon; Zitvogel, Valerie; Caldas, Carlos; Engstrand, Lars; et al. (OncoImmunology, 2020)
Accumulating evidence demonstrates the decisive role of the gut microbiota in determining the effectiveness of anticancer therapeutics such as immunogenic chemotherapy or immune checkpoint blockade in preclinical tumor models, as well as in cancer patients. In synthesis, it appears that a normal intestinal microbiota supports therapeutic anticancer responses, while a dysbiotic microbiota that lacks immunostimulatory bacteria or contains overabundant immunosuppressive species causes treatment failure. These findings have led to the design of clinical trials that evaluate the capacity of modulation of the gut microbiota to synergize with treatment and hence limit tumor progression. Along the lines of this Trial Watch, we discuss the rationale for harnessing the gut microbiome in support of cancer therapy and the progress of recent clinical trials testing this new therapeutic paradigm in cancer patients.
CRIS-Team WoS Importer:2020-06-26

Tumour stage distribution and survival of malignant melanoma in Germany 2002-2011 - Schoffer, Olaf; Schuelein, Stefanie; Arand, Gerlinde; Arnholdt, Hans; Baaske, Dieter; Bargou, Ralf C.; Becker, Nikolaus; Beckmann, Matthias; Bodack, Yves; Boehme, Beatrix; Bozkurt, Tayfun; Breitsprecher, Regine; et al. (BMC Cancer, 2016)
Over the past two decades, there has been a rising trend in malignant melanoma incidence worldwide. In 2008, Germany introduced a nationwide skin cancer screening program starting at age 35. The aims of this study were to analyse the distribution of malignant melanoma tumour stages over time, as well as demographic and regional differences in stage distribution and survival of melanoma patients.Pooled data from 61 895 malignant melanoma patients diagnosed between 2002 and 2011 and documented in 28 German population-based and hospital-based clinical cancer registries were analysed using descriptive methods, joinpoint regression, logistic regression and relative survival.The number of annually documented cases increased by 53.2% between 2002 (N = 4 779) and 2011 (N = 7 320). There was a statistically significant continuous positive trend in the proportion of stage UICC I cases diagnosed between 2002 and 2011, compared to a negative trend for stage UICC II. No trends were found for stages UICC III and IV respectively. Age (OR 0.97, 95% CI 0.97-0.97), sex (OR 1.18, 95% CI 1.11-1.25), date of diagnosis (OR 1.05, 95% CI 1.04-1.06), 'diagnosis during screening' (OR 3.24, 95% CI 2.50-4.19) and place of residence (OR 1.23, 95% CI 1.16-1.30) had a statistically significant influence on the tumour stage at diagnosis. The overall 5-year relative survival for invasive cases was 83.4% (95% CI 82.8-83.9%).No distinct changes in the distribution of malignant melanoma tumour stages among those aged 35 and older were seen that could be directly attributed to the introduction of skin cancer screening in 2008.
EVALuna2:19618

Twelve-year survival and immune correlates in dendritic cell-vaccinated melanoma patients - Gross, Stefanie; Erdmann, Michael; Haendle, Ina; Voland, Steve; Berger, Thomas; Schultz, Erwin; Strasser, Erwin; Dankerl, Peter; Janka, Rolf Matthias; Schliep, Stefan; Heinzerling, Lucie; Sotlar, Karl; et al. (JCI Insight, 2017)
BACKGROUND: Reports on long-term (≥10 years) effects of cancer vaccines are missing. Therefore, in 2002, we initiated a phase I/II trial in cutaneous melanoma patients to further explore the immunogenicity of our DC vaccine and to establish its long-term toxicity and clinical benefit after a planned 10-year followup. METHODS: Monocyte-derived DCs matured by TNFα, IL-1β, IL-6, and PGE2 and then loaded with 4 HLA class I and 6 class II-restricted tumor peptides were injected intradermally in high doses over 2 years. We performed serial immunomonitoring in all 53 evaluable patients. RESULTS: Vaccine-specific immune responses including high-affinity, IFNγ-producing CD4+ and lytic polyfunctional CD8+ T cells were de novo induced or boosted in most patients. Exposure of mature DCs to trimeric soluble CD40 ligand, unexpectedly, did not further enhance such immune responses, while keyhole limpet hemocyanin (KLH) pulsing to provide unspecific CD4+ help promoted CD8+ T cell responses - notably, their longevity. An unexpected 19% of nonresectable metastatic melanoma patients are still alive after 11 years, a survival rate similar to that observed in ipilimumab-treated patients and achieved without any major (>grade 2) toxicity. Survival correlated significantly with the development of intense vaccine injection site reactions, and with blood eosinophilia after the first series of vaccinations, suggesting that prolonged survival was a consequence of DC vaccination. CONCLUSIONS: Long-term survival in advanced melanoma patients undergoing DC vaccination is similar to ipilimumab-treated patients and occurs upon induction of tumor-specific T cells, blood eosinophilia, and strong vaccine injection site reactions occurring after the initial vaccinations. TRIAL REGISTRATION: ClinicalTrials.gov NCT00053391. FUNDING: European Community, Sixth Framework Programme (Cancerimmunotherapy LSHC-CT-2006-518234; DC-THERA LSHB-CT-2004-512074), and German Research Foundation (CRC 643, C1, Z2).
EVALuna2:14632

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Using multiple real-world dermoscopic photographs of one lesion improves melanoma classification via deep learning - Hekler, Achim; Maron, Roman C.; Haggenmüller, Sarah; Schmitt, Max; Wies, Christoph; Utikal, Jochen S.; Meier, Friedegund; Hobelsberger, Sarah; Gellrich, Frank F.; Sergon, Mildred; Hauschild, Axel; French, Lars E.; et al. (Journal of the American Academy of Dermatology, 2024)
CRIS-Team Scopus Importer:2024-02-16
Keywords: artificial intelligence; deep learning; dermatology; dermoscopy; diagnosis; diagnostic accuracy; melanoma; robustness; uncertainty estimation

Vaccination with dendritic Cells for metastasized Uveal Melanoma: immunological and clinical Responses - Moreira, Alvaro; Gross, S.; Uslu, Ugur; Dörrie, Jan; Kummer, Mirko; Schliep, S.; Sponagl, F.; Lischer, Christopher; Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Vier Fälle einer Erysipel-ähnlichen Entzündung bei Patienten mit metastasiertem Melanom unter Therapie mit Checkpoint-Inhibitoren. - Pföhler, Claudia; Hassel, Jessica C.; Heinzerling, Lucie; Müller, Cornelia S.L. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
EVALuna2:470343

Willingness to pay for a cure of low-risk melanoma patients in Germany - Augustin, Matthias; Blome, Christine; Forschner, Andrea; Gutzmer, Ralf; Hauschild, Axel; Heinzerling, Lucie; Livingstone, Elisabeth; Loquai, Carmen; Schadendorf, Dirk; Utikal, Jochen; Wagner, Tobias; Wilden, Sophia; et al. (PLoS ONE, 2018)
Malignant melanoma is potentially life-threatening but in most cases curable if detected early. Willingness to pay (WTP) is a preference-based construct that reflects burden of disease by assessment of the monetary value for a hypothetical cure from disease. Since WTP (directly as total amount of money) has not been assessed so far in patients with low risk melanoma, it was interesting to gain insights in this patient population and then, in a second step, compare it directly with the WTP of their treating dermato-oncologists. WTP was assessed in 125 patients with low-risk melanoma and additionally in 105 treating physicians, asking for the one-time and continuous payments they would be willing to make for a sustainable cure, both as absolute sums and as percentages of monthly income. The median WTP based on one-time payment was €10,000 for patients and €100,000 for physicians; relative numbers were 100% versus 300% of monthly income. For continuous monthly payments, WTP was €500 for patients and €1000 for physicians, relative numbers 25% and 50% of income, respectively. Even after controlling for income differences, there was a significantly higher WTP in physicians for all four questions. Compared to patients with chronic skin diseases such as vitiligo, rosacea, atopic eczema and psoriasis, patients with low-risk melanoma showed a significantly higher WTP. Our data suggest that there is a relevant burden of disease even in patients with low-risk tumors. Higher WTP of physicians underlines the prevalence of differences in disease perception.
EVALuna2:34380